Silk-hyaluronic acid based tissue fillers and methods of using the same
Patent Information
- Application Number
- JP2024192754
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-03-09
- Filing Date
- 2024-11-01
- Publication Date
- 2025-10-07
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 62 / 525,131, filed June 26, 2017, and U.S. Provisional Patent Application No. 62 / 641,095, filed March 9, 2018, the entire contents of each of which are incorporated herein by reference. [Background technology]
[0002] Silk is a natural polymer produced by various insects and spiders. Silk contains a filamentous core protein, silk fibroin, and a colloidal coating composed of a nonfilamentous protein, sericin. Silk has historically been investigated for use in the medical field. Hyaluronic acid (hyaluronan) is a glycosaminoglycan distributed throughout the body and present in connective and epithelial tissues. Due to its biocompatibility and structural advantages, it is a useful component in medical devices and implant materials.
[0003] The soft tissues of the human body owe their structure in part to the extracellular matrix, which includes collagen, elastin, and glycosaminoglycans. Soft tissue defects can occur that result in distortion, deformation, or other changes to the soft tissue structure. Such structure can be restored by using tissue fillers that can be deposited at the defect site and improve the defect. For example, tissue fillers can be placed at the site of facial wrinkles to smooth the wrinkles.
[0004] However, there is a need in the art for new tissue fillers that improve many tissue defects while providing tunable properties that can enable application of the tissue filler to specific tissue defects. Summary of the Invention
[0005] In one embodiment, the present invention relates to a biocompatible tissue filler comprising a glycosaminoglycan selected from the group consisting of hyaluronic acid (HA), carboxymethylcellulose (CMC), starch, alginate, chondroitin-4-sulfate, chondroitin-6-sulfate, xanthan gum, chitosan, pectin, agar, carrageenan, and guar gum; and an active agent selected from the group consisting of enzyme inhibitors, anesthetics, medicinal neurotoxins, antioxidants, anti-infectives, anti-inflammatory agents, ultraviolet (UV) light blocking agents, dyes, hormones, immunosuppressants, and anti-inflammatory agents, wherein a portion of the glycosaminoglycan is crosslinked with crosslinking moieties comprising one or more of an alkane or alkyl chain, an ether group, and a secondary alcohol, and the crosslinking is achieved using a crosslinking agent, crosslinking precursor, or activator. In some embodiments, the glycosaminoglycan is hyaluronic acid (HA). In some embodiments, the amount of crosslinked HA relative to the total amount of HA (% w / w) is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 9 2%, approximately 23%, approximately 24%, approximately 25%, approximately 26%, approximately 27%, approximately 28%, approximately 29%, approximately 30%, approximately 31%, approximately 32%, approximately 33%, approximately 34%, approximately 35%, approximately 36%, approximately 37%, approximately 38%, approximately 39%, approximately 40%, approximately 41%, approximately 42%, approximately 43%, approximately 44%, approximately 45%, approximately 46%, approximately 47%, approximately 48%, Approximately 49%, approximately 50%, approximately 51%, approximately 52%, approximately 53%, approximately 54%, approximately 55%, approximately 56%, approximately 57%, approximately 58%, approximately 59%, approximately 60%, approximately 61%, approximately 62%, approximately 63%, approximately 64%, approximately 65%, approximately 66%, approximately 67%, approximately 68%, approximately 69%, approximately 70%, approximately 71%, approximately 72%, approximately 73%, approximately 74%, approximately 75% %, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%. In some embodiments, the degree of crosslinking of the crosslinked HA is from about 1% to about 100%.In some embodiments, the degree of crosslinking of the crosslinked HA is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, about 100%, about 4%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50% 0%, approx. 51%, approx. 52%, approx. 53%, approx. 54%, approx. 55%, approx. 56%, approx. 57%, approx. 58%, approx. 59%, approx. 60%, approx. 61%, approx. 62%, approx. 63%, approx. 64%, approx. 65%, approx. 66%, approx. 67%, approx. 68%, approx. 69%, approx. 70%, approx. 71%, approx. 72%, approx. 73%, approx. 74%, approx. 75%, approx. The degree of cross-linking of the cross-linked HA is about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%. In some embodiments, the degree of cross-linking of the cross-linked HA is about 1% to about 15%. In some embodiments, the degree of cross-linking of the cross-linked HA is one or more of about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, and about 15%.
[0006] In some embodiments, the crosslinked HA comprises crosslinking moieties comprising polyethylene glycol (PEG) chains. In some embodiments, the crosslinking agent and / or crosslinking precursor comprises epoxy groups. In some embodiments, crosslinking is achieved by polyepoxy linker, diepoxy linker, polyepoxy-PEG, diepoxy-PEG, polyglycidyl-PEG, diglycidyl-PEG, polyacrylate PEG, diacrylate PEG, 1,4-bis(2,3-epoxypropoxy)butane, 1,4-bisglycidyloxybutane, divinyl sulfone (DVS), 1,4-butanediol diglycidyl ether (BDDE), UV light, glutaraldehyde, 1,2-bis(2,3-epoxypropoxy)ethylene. The crosslinker may be obtained using a crosslinker, crosslink precursor, or activator selected from the group consisting of bis(sulfosuccinimidyl) suberate (BS), hexamethylenediamine (HMDA), 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane, carbodiimide, and any combination thereof. In some embodiments, the crosslinking is achieved using a multifunctional epoxy compound selected from the group consisting of 1,4-butanediol diglycidyl ether (BDDE), ethylene glycol diglycidyl ether (EGDGE), 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, polyglycerol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, pentaerythritol polyglycidyl ether, and sorbitol polyglycidyl ether.In some embodiments, the crosslinking is achieved using a crosslinker and / or crosslink precursor selected from the group consisting of polyethylene glycol diglycidyl ether, diepoxy PEG, PEG diglycidyl ether, polyoxyethylene bis-glycidyl ether, PEGDE, and PEGDGE. In some embodiments, the crosslinking has an average M of about 500, about 1000, about 2000, or about 6000. n In some embodiments, crosslinking is achieved using a polyethylene glycol diglycidyl ether having 2 to 25 ethylene glycol groups. In some embodiments, crosslinking is achieved using a crosslinker and / or crosslinking precursor selected from the group consisting of a polyepoxy silk fibroin linker, a diepoxy silk fibroin linker, a polyepoxy silk fibroin fragment linker, a diepoxy silk fibroin fragment linker, a polyglycidyl silk fibroin linker, a diglycidyl silk fibroin linker, a polyglycidyl silk fibroin fragment linker, and a diglycidyl silk fibroin fragment linker.
[0007] In some embodiments, the present invention relates to a tissue filler further comprising an organic compound and / or an inorganic compound. In some embodiments, the inorganic compound comprises calcium hydroxyapatite. In some embodiments, the calcium hydroxyapatite is formulated as particles having a diameter of about 1 μm to about 100 μm, about 1 μm to about 10 μm, about 2 μm to about 12 μm, about 3 μm to about 10 μm, about 4 μm to about 15 μm, about 8 μm to about 12 μm, about 5 μm to about 10 μm, about 6 μm to about 12 μm, about 7 μm to about 20 μm, about 9 μm to about 18 μm, or about 10 μm to about 25 μm. In some embodiments, the concentration of calcium hydroxyapatite is about 0.001% to about 5%. In some embodiments, the concentration of calcium hydroxyapatite is about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.011%, about 0.012%, about 0.013%, about 0.014%, about 0.015%, about 0.016%, about 0.017%, about 0.018%, about 0.019%, or about 0.02%. In some embodiments, the concentration of calcium hydroxyapatite is about 0.05%, about 0.1%, about 0.15%, about 0.2%, about 0.25%, about 0.3%, about 0.35%, about 0.4%, about 0.45%, about 0.5%, about 0.55%, about 0.6%, about 0.65%, about 0.7%, about 0.75%, about 0.8%, about 0.85%, about 0.9 %, about 0.95%, about 1%, about 1.05%, about 1.1%, about 1.15%, about 1.2%, about 1.25%, about 1.3%, about 1.35%, about 1.4%, about 1.45%, about 1.5%, about 1.55%, about 1.6%, about 1.65%, about 1.7%, about 1.75%, about 1.8%, about 1.85%, about 1.9%, about 1.95%, or about 2%. In some embodiments, the organic compound comprises an amino acid selected from the group consisting of glycine, L-proline, alanine, arginine, asparagine, aspartic acid, cysteine, glutamic acid, glutamine, histidine, isoleucine, leucine, lysine, methionine, phenylalanine, proline, serine, threonine, tryptophan, tyrosine, and valine.
[0008] In some embodiments, the present invention relates to a tissue filler comprising HA, wherein the HA is obtained from Streptococcus or Bacillus subtilis.
[0009] In one embodiment, the present invention relates to a biocompatible tissue filler comprising a glycosaminoglycan selected from the group consisting of hyaluronic acid (HA), carboxymethylcellulose (CMC), starch, alginate, chondroitin-4-sulfate, chondroitin-6-sulfate, xanthan gum, chitosan, pectin, agar, carrageenan, and guar gum; and an anesthetic, wherein a portion of the glycosaminoglycan is crosslinked with a crosslinking moiety comprising one or more of an alkane or alkyl chain, an ether group, and a secondary alcohol, and the crosslinking is achieved using a crosslinking agent, crosslinking precursor, or activator. In some embodiments, the anesthetic is lidocaine. In some embodiments, the concentration of the anesthetic in the tissue filler is about 0.001% to about 5%. In some embodiments, the concentration of lidocaine in the tissue filler is about 0.3%.
[0010] In one embodiment, the present invention relates to a biocompatible tissue filler comprising a glycosaminoglycan selected from the group consisting of hyaluronic acid (HA), carboxymethylcellulose (CMC), starch, alginate, chondroitin-4-sulfate, chondroitin-6-sulfate, xanthan gum, chitosan, pectin, agar, carrageenan, and guar gum; and an anesthetic, wherein a portion of the glycosaminoglycan is crosslinked with a crosslinking moiety comprising one or more of an alkane or alkyl chain, an ether group, and a secondary alcohol, the crosslinking being achieved using a crosslinking agent, crosslinking precursor, or activator, and the tissue filler is a gel. In some embodiments, the tissue filler is a hydrogel. In some embodiments, the tissue filler further comprises water. In some embodiments, the total concentration of HA in the tissue filler is about 10 mg / mL to about 50 mg / mL. In some embodiments, the total concentration of HA in the tissue filler is about 15 mg / mL, about 16 mg / mL, 17 mg / mL, about 18 mg / mL, about 19 mg / mL, about 20 mg / mL, about 21 mg / mL, about 22 mg / mL, about 23 mg / mL, about 24 mg / mL, about 25 mg / mL, about 26 mg / mL, about 27 mg / mL, about 28 mg / mL, about 29 mg / mL, or about 30 mg / mL. In some embodiments, the concentration of crosslinked HA in the tissue filler is about 10 mg / mL to about 50 mg / mL. In some embodiments, the concentration of crosslinked HA in the tissue filler is about 15 mg / mL, about 16 mg / mL, about 17 mg / mL, about 18 mg / mL, about 19 mg / mL, about 20 mg / mL, about 21 mg / mL, about 22 mg / mL, about 23 mg / mL, about 24 mg / mL, about 25 mg / mL, about 26 mg / mL, about 27 mg / mL, about 28 mg / mL, about 29 mg / mL, or about 30 mg / mL.
[0011] In one embodiment, the present invention relates to a biocompatible tissue filler comprising a glycosaminoglycan selected from the group consisting of hyaluronic acid (HA), carboxymethylcellulose (CMC), starch, alginate, chondroitin-4-sulfate, chondroitin-6-sulfate, xanthan gum, chitosan, pectin, agar, carrageenan, and guar gum; and an anesthetic, wherein a portion of the glycosaminoglycan is crosslinked with a crosslinking moiety comprising one or more of an alkane or alkyl chain, an ether group, and a secondary alcohol, and the crosslinking is achieved using a crosslinking agent, crosslinking precursor, or activator, and the tissue filler comprises silk protein or silk protein fragment (SPF). In some embodiments, the silk protein is silk fibroin. In some embodiments, the silk protein is silk fibroin substantially free of sericin. In some embodiments, the SPF has an average weight-average molecular weight ranging from about 1 kDa to about 250 kDa. In some embodiments, the SPF has an average weight average molecular weight ranging from about 5 kDa to about 150 kDa. In some embodiments, the SPF has an average weight average molecular weight ranging from about 6 kDa to about 17 kDa. In some embodiments, the SPF has an average weight average molecular weight ranging from about 17 kDa to about 39 kDa. In some embodiments, the SPF has an average weight average molecular weight ranging from about 39 kDa to about 80 kDa. In some embodiments, the SPF has a low molecular weight. In some embodiments, the SPF has a medium molecular weight. In some embodiments, the SPF has a high molecular weight. In some embodiments, the silk protein fragment (SPF) has a polydispersity of about 1.5 to about 3.0. In some embodiments, the SPF has a crystallinity of up to 60%. In some embodiments, the SPF is partially crosslinked.In some embodiments, the amount of crosslinked SPF relative to the total amount of SPF (% w / w) is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21% ,approximately 22%,approximately 23%,approximately 24%,approximately 25%,approximately 26%,approximately 27%,approximately 28%,approximately 29%,approximately 30%,approximately 31%,approximately 32%,approximately 33%,approximately 34%,approximately 35%,approximately 36%,approximately 37%,approximately 38%,approximately 39%,approximately 40%,approximately 41%,approximately 42%,approximately 43%,approximately 44%,approximately 45%,approximately 46%,approximately 47%,approximately 48 %,approximately 49%,approximately 50%,approximately 51%,approximately 52%,approximately 53%,approximately 54%,approximately 55%,approximately 56%,approximately 57%,approximately 58%,approximately 59%,approximately 60%,approximately 61%,approximately 62%,approximately 63%,approximately 64%,approximately 65%,approximately 66%,approximately 67%,approximately 68%,approximately 69%,approximately 70%,approximately 71%,approximately 72%,approximately 73%,approximately 74%,approximately 75% 5%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%. In some embodiments, the degree of crosslinking of the crosslinked SPF is about 1% to about 100%.In some embodiments, the degree of crosslinking of the crosslinked SPF is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, approximately 25%, approximately 26%, approximately 27%, approximately 28%, approximately 29%, approximately 30%, approximately 31%, approximately 32%, approximately 33%, approximately 34%, approximately 35%, approximately 36%, approximately 37%, approximately 38%, approximately 39%, approximately 40%, approximately 41%, approximately 42%, approximately 43%, approximately 44%, approximately 45%, approximately 46%, approximately 47%, approximately 48%, approximately 49%, approximately 50%, approximately 51%, approximately 52%, approximately 53%, approximately 54%, approximately 55%, approximately 56%, approximately 57%, approximately 58%, approximately 59%, approximately 60%, approximately 61%, approximately 62%, approximately 63%, approximately 64%, approximately 65%, approximately 66%, approximately 67%, approximately 68%, approximately 69%, approximately 70%, approximately 71%, approximately 72%, approximately 73%, approximately 74%, approximately 75%, approximately The crosslinking degree of the crosslinked SPF is 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%. In some embodiments, the crosslinking degree of the crosslinked SPF is about 1% to about 15%. In some embodiments, the crosslinking degree of the crosslinked SPF is one or more of about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, and about 15%.
[0012] In one embodiment, the present invention relates to a biocompatible tissue filler comprising a glycosaminoglycan selected from the group consisting of hyaluronic acid (HA), carboxymethylcellulose (CMC), starch, alginate, chondroitin-4-sulfate, chondroitin-6-sulfate, xanthan gum, chitosan, pectin, agar, carrageenan, and guar gum; and an anesthetic, wherein a portion of the glycosaminoglycan is crosslinked with crosslinking moieties comprising one or more of an alkane or alkyl chain, an ether group, and a secondary alcohol, the crosslinking being achieved using a crosslinking agent, crosslinking precursor, or activator; the tissue filler comprises silk protein or silk protein fragment (SPF), and a portion of the SPF is crosslinked. In some embodiments, the crosslinked SPF comprises a crosslinking moiety comprising an alkane or alkyl chain and / or an ether group. In some embodiments, the crosslinked SPF comprises a crosslinking moiety comprising a polyethylene glycol (PEG) chain. In some embodiments, the crosslinked SPF comprises a crosslinking moiety comprising a secondary alcohol. In some embodiments, crosslinking is achieved using a crosslinking agent, crosslinking precursor, or activator. In some embodiments, the crosslinking agent and / or crosslinking precursor comprises an epoxy group. In some embodiments, crosslinking is achieved using a polyepoxy linker, a diepoxy linker, polyepoxy-PEG, diepoxy-PEG, polyglycidyl-PEG, diglycidyl-PEG, polyacrylate PEG, diacrylate PEG, 1,4-bis(2,3-epoxypropoxy)butane, 1,4-bisglycidyloxybutane, divinyl sulfone (DVS), 1,4-butanediol diglycidyl ether (BDDE), UV light, glutaraldehyde, 1,2-bis(2,3-epoxypropoxy)ethylene. The crosslinker may be obtained using a crosslinker, crosslink precursor, or activator selected from the group consisting of bis(sulfosuccinimidyl) suberate (BS), hexamethylenediamine (HMDA), 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane, carbodiimide, and any combination thereof.In some embodiments, crosslinking is achieved using a multifunctional epoxy compound selected from the group consisting of 1,4-butanediol diglycidyl ether (BDDE), ethylene glycol diglycidyl ether (EGDGE), 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, polyglycerol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, pentaerythritol polyglycidyl ether, and sorbitol polyglycidyl ether. In some embodiments, crosslinking is achieved using a crosslinker and / or crosslinking precursor selected from the group consisting of polyethylene glycol diglycidyl ether, diepoxy PEG, PEG diglycidyl ether, polyoxyethylene bis-glycidyl ether, PEGDE, and PEGDGE. In some embodiments, the crosslinks have an average M of about 500, about 1000, about 2000, or about 6000. nIn some embodiments, crosslinking is achieved using a polyethylene glycol diglycidyl ether having 2 to 25 ethylene glycol groups. In some embodiments, crosslinking is achieved using a crosslinker and / or crosslinking precursor selected from the group consisting of a polyepoxy silk fibroin linker, a diepoxy silk fibroin linker, a polyepoxy silk fibroin fragment linker, a diepoxy silk fibroin fragment linker, a polyglycidyl silk fibroin linker, a diglycidyl silk fibroin linker, a polyglycidyl silk fibroin fragment linker, and a diglycidyl silk fibroin fragment linker. In some embodiments, a portion of the SPF is crosslinked to the HA. In some embodiments, a portion of the SPF is crosslinked to the SPF. In some embodiments, the tissue filler is a gel. In some embodiments, the tissue filler is a hydrogel. In some embodiments, the tissue filler further comprises water. In some embodiments, the total concentration of the SPF in the tissue filler is about 0.1 mg / mL to about 15 mg / mL. In some embodiments, the total concentration of SPF in the tissue filler is about 0.1 mg / mL, about 0.5 mg / mL, about 1 mg / mL, about 1.5 mg / mL, about 2 mg / mL, about 2.5 mg / mL, about 3 mg / mL, about 3.5 mg / mL, about 4 mg / mL, about 4.5 mg / mL, about 5 mg / mL, about 5.5 mg / mL, about 6 mg / mL, about 6.5 mg / mL, about 7 mg / mL, about 7.5 mg / mL, about 8 mg / mL, about 8.5 mg / mL, about 9 mg / mL, about 9.5 mg / mL, about 10 mg / mL, about 10.5 mg / mL, about 11 mg / mL, about 11.5 mg / mL, about 12 mg / mL, about 12.5 mg / mL, about 13 mg / mL, about 13.5 mg / mL, about 14 mg / mL, about 14.5 mg / mL, or about 15 mg / mL. In some embodiments, the concentration of the cross-linked SPF in the tissue filler is from about 0.1 mg / mL to about 15 mg / mL.In some embodiments, the concentration of the crosslinked SPF in the tissue filler is about 0.1 mg / mL, about 0.5 mg / mL, about 1 mg / mL, about 1.5 mg / mL, about 2 mg / mL, about 2.5 mg / mL, about 3 mg / mL, about 3.5 mg / mL, about 4 mg / mL, about 4.5 mg / mL, about 5 mg / mL, about 5.5 mg / mL, about 6 mg / mL, about 6.5 mg / mL, about 7 mg / mL, about 7.5 mg / mL, about 8 mg / mL, about 8.5 mg / mL, about 9 mg / mL, about 9.5 mg / mL, about 10 mg / mL, about 10.5 mg / mL, about 11 mg / mL, about 11.5 mg / mL, about 12 mg / mL, about 12.5 mg / mL, about 13 mg / mL, about 13.5 mg / mL, about 14 mg / mL, about 14.5 mg / mL, or about 15 mg / mL.
[0013] In one embodiment, the present invention relates to a biocompatible tissue filler comprising a glycosaminoglycan selected from the group consisting of hyaluronic acid (HA), carboxymethylcellulose (CMC), starch, alginate, chondroitin-4-sulfate, chondroitin-6-sulfate, xanthan gum, chitosan, pectin, agar, carrageenan, and guar gum; and an anesthetic, wherein a portion of the glycosaminoglycan is crosslinked with a crosslinking moiety comprising one or more of an alkane or alkyl chain, an ether group, and a secondary alcohol, the crosslinking being achieved using a crosslinking agent, crosslinking precursor, or activator, and the tissue filler optionally comprises silk protein or silk protein fragment (SPF), wherein a portion of the SPF is crosslinked. In some embodiments, the tissue filler is a dermal filler. In some embodiments, the tissue filler is biodegradable. In some embodiments, the tissue filler is injectable. In some embodiments, the tissue filler has a storage modulus (G') of about 25 Pa to about 1500 Pa.In some embodiments, the tissue filler has a viscosity of about 25 Pa, about 26 Pa, about 27 Pa, about 28 Pa, about 29 Pa, about 30 Pa, about 31 Pa, about 32 Pa, about 33 Pa, about 34 Pa, about 35 Pa, about 36 Pa, about 37 Pa, about 38 Pa, about 39 Pa, about 40 Pa, about 41 Pa, about 42 Pa, about 43 Pa, about 44 Pa, about 45 Pa, about 46 Pa, about 47 Pa, about 48 Pa, about 49 Pa Pa, approximately 50Pa, approximately 51Pa, approximately 52Pa, approximately 53Pa, approximately 54Pa, approximately 55Pa, approximately 56Pa, approximately 57Pa, approximately 58Pa, approximately 59Pa, approximately 60Pa, approximately 61Pa, approximately 62Pa, approximately 6 3Pa, about 64Pa, about 65Pa, about 66Pa, about 67Pa, about 68Pa, about 69Pa, about 70Pa, about 71Pa, about 72Pa, about 73Pa, about 74Pa, about 75Pa, about 76Pa, about 7 7 Pa, approximately 78 Pa, approximately 79 Pa, approximately 80 Pa, approximately 81 Pa, approximately 82 Pa, approximately 83 Pa, approximately 84 Pa, approximately 85 Pa, approximately 86 Pa, approximately 87 Pa, approximately 88 Pa, approximately 89 Pa, approximately 90 Pa, approximately 91 Pa, approximately 92 Pa, approximately 93 Pa, approximately 94 Pa, approximately 95 Pa, approximately 96 Pa, approximately 97 Pa, approximately 98 Pa, approximately 99 Pa, approximately 100 Pa, approximately 101 Pa, approximately 102 Pa, approximately 103 Pa, approximately 10 The polymer has a storage modulus (G') of about 4 Pa, about 10 Pa, about 10 Pa, about 10 Pa, about 10 Pa, about 10 Pa, about 10 Pa, about 110 Pa, about 111 Pa, about 112 Pa, about 113 Pa, about 114 Pa, about 115 Pa, about 116 Pa, about 117 Pa, about 118 Pa, about 119 Pa, about 120 Pa, about 121 Pa, about 122 Pa, about 123 Pa, about 124 Pa, or about 125 Pa. In some embodiments, G' is measured using an oscillatory stress of about 0.1 to about 10 Hz. In some embodiments, G' is measured using an oscillatory stress of about 1 Hz. In some embodiments, G' is measured using an oscillatory stress of about 5 Hz. In some embodiments, G' is measured using an oscillatory stress of about 10 Hz. In some embodiments, the tissue filler has a complex viscosity of about 1 Pa·s to about 10 Pa·s.In some embodiments, the tissue filler has a complex viscosity of about 1 Pa·s, about 1.5 Pa·s, about 2 Pa·s, about 2.5 Pa·s, about 3 Pa·s, about 3.5 Pa·s, about 4 Pa·s, about 4.5 Pa·s, about 5 Pa·s, about 5.5 Pa·s, about 6 Pa·s, about 6.5 Pa·s, about 7 Pa·s, about 7.5 Pa·s, about 8 Pa·s, about 8.5 Pa·s, about 9 Pa·s, about 9.5 Pa·s, or about 10 Pa·s. In some embodiments, the complex viscosity is measured using an oscillatory stress of about 0.1 to about 10 Hz. In some embodiments, the complex viscosity is measured using an oscillatory stress of about 1 Hz. In some embodiments, the complex viscosity is measured using an oscillatory stress of about 5 Hz.
[0014] In one embodiment, the present invention relates to a method of treating a condition in a subject in need thereof and / or a method of cosmetic treatment in a subject in need thereof, comprising administering to the subject a therapeutically effective amount of a biocompatible tissue filler, wherein the biocompatible tissue filler comprises a glycosaminoglycan selected from the group consisting of hyaluronic acid (HA), carboxymethylcellulose (CMC), starch, alginate, chondroitin-4-sulfate, chondroitin-6-sulfate, xanthan gum, chitosan, pectin, agar, carrageenan, and guar gum; and an anesthetic, wherein a portion of the glycosaminoglycan is crosslinked with crosslinking moieties comprising one or more of an alkane or alkyl chain, an ether group, and a secondary alcohol, wherein the crosslinking is achieved using a crosslinking agent, a crosslinking precursor, or an activator, and optionally the tissue filler comprises silk protein or silk protein fragment (SPF), wherein a portion of the SPF is crosslinked. In some embodiments, the condition is a skin condition. In some embodiments, the skin condition is selected from the group consisting of skin dehydration, lack of skin elasticity, rough skin, lack of skin firmness, skin stretch lines, skin stretch marks, skin paleness, dermal divots, sunken cheeks, thin lips, retro-orbital defects, facial creases, and wrinkles. In some embodiments, the tissue filler is administered to the dermal region of the subject. In some embodiments, the method is augmentation, reconstruction, treatment of disease, treatment of disorder, treatment of a defect or imperfection in a body part, portion, or region. In some embodiments, the method is facial augmentation, facial reconstruction, treatment of facial disease, treatment of facial disorder, treatment of facial defect, or treatment of facial imperfection. In some embodiments, the tissue filler resists biodegradation, bioerosion, bioabsorption, and / or bioresorption for at least about 3 days, about 7 days, about 14 days, about 21 days, about 28 days, about 1 month, about 2 months, about 3 months, about 4 months, about 5 months, or about 6 months.In some embodiments, administration of the tissue filler to a subject reduces an inflammatory response compared to the inflammatory response induced by a control tissue filler comprising polysaccharides and lidocaine but not silk protein fragments (SPF), hi some embodiments, administration of the tissue filler to a subject increases collagen production compared to the collagen production induced by a control tissue filler comprising polysaccharides and lidocaine but not silk protein fragments (SPF).
[0015] In one embodiment, the present invention relates to a biocompatible tissue filler comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide. In some embodiments, the polysaccharide is hyaluronic acid (HA). In embodiments, the present invention includes a tissue filler that can be prepared from silk and hyaluronic acid.
[0016] In some embodiments, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having an average molecular weight ranging from about 1 kDa to about 250 kDa. In some embodiments, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having an average molecular weight ranging from about 5 kDa to about 150 kDa. In some embodiments, the SPF has an average molecular weight ranging from about 6 kDa to about 17 kDa. In some embodiments, the SPF has an average molecular weight ranging from about 17 kDa to about 39 kDa. In some embodiments, the SPF has an average molecular weight ranging from about 39 kDa to about 80 kDa. In some embodiments, the SPF has an average molecular weight ranging from about 80 kDa to about 150 kDa.
[0017] In some embodiments, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) crosslinked to about 0% to 100% of the SPF. In some embodiments, the SPF is crosslinked to the SPF using a crosslinker such as BDDE or one of the other crosslinkers described herein. In some embodiments, the degree of crosslinking is up to about 100%.
[0018] In one embodiment, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and hyaluronic acid (HA), wherein up to about 0% to 100% of the SPF is crosslinked with the SPF, and the SPF is crosslinked with a crosslinker such as BDDE or one of the other crosslinkers described herein, wherein the degree of crosslinking of the SPF is up to about 100%.
[0019] In one embodiment, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and hyaluronic acid (HA), wherein up to 100% of the HA is crosslinked with the HA using a crosslinker such as BDDE or one of the other crosslinkers described herein. In some embodiments, up to about 100% of the SPF is crosslinked with the SPF, wherein the SPF is crosslinked with a crosslinker such as BDDE or one of the other crosslinkers described herein, and the degree of crosslinking of the SPF is up to about 100%.
[0020] In one embodiment, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and hyaluronic acid (HA), wherein 0% to 100% of the HA is uncrosslinked. In some embodiments, up to about 100% of the SPF is crosslinked, and the SPF is crosslinked with a crosslinker such as BDDE or one of the other crosslinkers described herein, resulting in up to about 100% crosslinking of the SPF. In some embodiments, all of the HA is uncrosslinked.
[0021] In one embodiment, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and hyaluronic acid (HA), wherein 0% to 100% of the SPF is crosslinked with the HA. In some embodiments, the SPF and HA are crosslinked using a crosslinker such as BDDE or one of the other crosslinkers described herein. In some embodiments, the degree of crosslinking of the SPF-HA is up to about 100%. In some embodiments, up to 100% of the HA is crosslinked with the HA. In some embodiments, the HA is crosslinked with the HA using a crosslinker such as BDDE or one of the other crosslinkers described herein. In some embodiments, at least 0.1% of the HA is uncrosslinked. In some embodiments, all of the HA is uncrosslinked.
[0022] In one embodiment, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and hyaluronic acid (HA), wherein at least 0.1% of the HA is uncrosslinked. In some embodiments, up to about 100% of the SPF is crosslinked, and the SPF is crosslinked with a crosslinker such as BDDE or one of the other crosslinkers described herein, such that the degree of crosslinking of the SPF is up to about 100%. In some embodiments, all of the HA is uncrosslinked.
[0023] In one embodiment, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and hyaluronic acid (HA), wherein at least 0.1% of the SPF is crosslinked with the HA. In some embodiments, the SPF and HA are crosslinked using a crosslinker such as BDDE or one of the other crosslinkers described herein. In some embodiments, the SPF-HA has a degree of crosslinking of up to about 100%. In some embodiments, up to 100% of the HA is crosslinked with the HA. In some embodiments, the HA is crosslinked with the HA using a crosslinker such as BDDE or one of the other crosslinkers described herein. In some embodiments, at least 0.1% of the HA is uncrosslinked. In some embodiments, all of the HA is uncrosslinked.
[0024] In one embodiment, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and hyaluronic acid (HA), wherein the SPF is substantially devoid of sericin.
[0025] In one embodiment, the present invention relates to a biocompatible gel tissue filler comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide.
[0026] In one embodiment, the present invention relates to a biocompatible hydrogel tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide.
[0027] In one embodiment, the present invention relates to a biocompatible gel tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0, a polysaccharide, and water.
[0028] In one embodiment, the present invention relates to a biocompatible tissue filler comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a crystallinity of about 0% to about 60%.
[0029] In one embodiment, the present invention relates to a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0, a polysaccharide, and an active agent. In some embodiments, the active agent can be an enzyme inhibitor, an anesthetic, a medicinal neurotoxin, an antioxidant, an anti-infective, a vasodilator, a reflective agent, an anti-inflammatory agent, an ultraviolet (UV) light blocking agent, a dye, a hormone, an immunosuppressant, or an anti-inflammatory agent. In one embodiment, the anesthetic is lidocaine.
[0030] In one embodiment, the present invention relates to an injectable biocompatible tissue filler comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide.
[0031] In one embodiment, the present invention relates to a biocompatible tissue filler comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide. In some embodiments, G' is measured using an oscillatory stress of about 0.1 to about 10 Hz. In one embodiment, G' is measured using an oscillatory stress of about 1 Hz.
[0032] In one embodiment, the present invention relates to a method for producing a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, the method comprising providing an SPF solution and adding to the solution a gelation promoter, which can be a proton-donating species.
[0033] In one embodiment, the present invention relates to a method for producing a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, the method comprising providing an SPF solution and subjecting the solution to mechanical excitation.
[0034] In one embodiment, the present invention relates to a method of treating a condition in a subject in need thereof, comprising administering to the subject a therapeutically effective amount of a biocompatible tissue filler comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide. In some embodiments, the condition is a skin condition. In some embodiments, the skin condition can be skin dehydration, lack of skin elasticity, rough skin, lack of skin firmness, skin stretch lines, skin stretch marks, skin pallor, skin divots, sunken cheeks, sunken temples, thin lips, retro-orbital defects, facial creases, and wrinkles.
[0035] In one embodiment, the present invention relates to a method of cosmetic treatment in a subject in need thereof, comprising administering to the subject an effective amount of a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide.
[0036] In some embodiments, the methods of the present invention include administering to a skin area of a subject a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide.
[0037] In one embodiment, the method of the present invention, comprising administering a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, can be for augmentation, reconstruction, treatment of disease, treatment of a disorder, treatment of a defect or imperfection in a part, portion, or region of the body.
[0038] In one embodiment, the method of the present invention comprising administering a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide can be facial augmentation, facial reconstruction, treatment of a facial disease, treatment of a facial disorder, treatment of a facial defect, or treatment of a facial imperfection.
[0039] In one embodiment, a biocompatible tissue filler comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide resists biodegradation, bioabsorption, and / or bioresorption for at least about 3 days after administration.
[0040] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is crosslinked. In some embodiments, a portion of the SPF is crosslinked with the polysaccharide. In some embodiments, a portion of the SPF is crosslinked with the SPF. In some embodiments, a portion of the polysaccharide is crosslinked with the polysaccharide. In some embodiments, the tissue filler further comprises a crosslinked moiety, e.g., an epoxy-derived crosslinked moiety. In some embodiments, a portion of the crosslinks are self-crosslinked. In some embodiments, the portion of the crosslinked SPF is up to about 100%. In some embodiments, the cross-linked polysaccharide portion is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water.
[0041] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is crosslinked. In some embodiments, a portion of the SPF is crosslinked with a polysaccharide. In some embodiments, a portion of the SPF is crosslinked with the SPF. In some embodiments, a portion of the polysaccharide is crosslinked with the polysaccharide. In some embodiments, the tissue filler further comprises crosslinked moieties, e.g., epoxy-derived crosslinked moieties. In some embodiments, a portion of the crosslinks are self-crosslinked. In some embodiments, the portion of the crosslinked SPF is up to about 100%. In some embodiments, the portion of the crosslinked polysaccharide is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water.
[0042] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with the polysaccharide. In some embodiments, a portion of the SPF is cross-linked with the SPF. In some embodiments, a portion of the polysaccharide is cross-linked with the polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the SPF is up to about 100% cross-linked. In some embodiments, the portion of the polysaccharide is up to about 100% cross-linked. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water.
[0043] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the cross-linked SPF is up to about 100%. In some embodiments, the portion of the cross-linked polysaccharide is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water.
[0044] In some embodiments, the amount of crosslinked SPF relative to the total amount of SPF (% w / w) is up to about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%. %,approximately 22%,approximately 23%,approximately 24%,approximately 25%,approximately 26%,approximately 27%,approximately 28%,approximately 29%,approximately 30%,approximately 31%,approximately 32%,approximately 33%,approximately 34%,approximately 35%,approximately 36%,approximately 37%,approximately 38%,approximately 39%,approximately 40%,approximately 41%,approximately 42%,approximately 43%,approximately 44%,approximately 45%,approximately 46%,approximately 47%,approximately 48% 8%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%.
[0045] In some embodiments, the degree of crosslinking of the SPF is at most about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, approximately 25%, approximately 26%, approximately 27%, approximately 28%, approximately 29%, approximately 30%, approximately 31%, approximately 32%, approximately 33%, approximately 34%, approximately 35%, approximately 36%, approximately 37%, approximately 38%, approximately 39%, approximately 40%, approximately 41%, approximately 42%, approximately 43%, approximately 44%, approximately 45%, approximately 46%, approximately 47%, approximately 48%, approximately 49%, approximately 50%, approximately 51%, approximately 52%, approximately 53%, approximately 54%, approximately 55%, approximately 56%, approximately 57%, approximately 58%, approximately 59%, approximately 60%, approximately 61%, approximately 62%, approximately 63%, approximately 64%, approximately 65%, approximately 66%, approximately 67%, approximately 68%, approximately 69%, approximately 70%, approximately 71%, approximately 72%, approximately 73%, approximately 74%, approximately 75%, approximately 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%.
[0046] In some embodiments, the amount of crosslinked HA relative to the total amount of HA (% w / w) is up to about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, Approximately 22%, approximately 23%, approximately 24%, approximately 25%, approximately 26%, approximately 27%, approximately 28%, approximately 29%, approximately 30%, approximately 31%, approximately 32%, approximately 33%, approximately 34%, approximately 35%, approximately 36%, approximately 37%, approximately 38%, approximately 39%, approximately 40%, approximately 41%, approximately 42%, approximately 43%, approximately 44%, approximately 45%, approximately 46%, approximately 47%, approximately 48% ,approximately 49%,approximately 50%,approximately 51%,approximately 52%,approximately 53%,approximately 54%,approximately 55%,approximately 56%,approximately 57%,approximately 58%,approximately 59%,approximately 60%,approximately 61%,approximately 62%,approximately 63%,approximately 64%,approximately 65%,approximately 66%,approximately 67%,approximately 68%,approximately 69%,approximately 70%,approximately 71%,approximately 72%,approximately 73%,approximately 74%,approximately 75 %, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83% by weight, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%.
[0047] In some embodiments, the degree of cross-linking of the HA is up to about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, about 100%, about 4%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50% 0%, approx. 51%, approx. 52%, approx. 53%, approx. 54%, approx. 55%, approx. 56%, approx. 57%, approx. 58%, approx. 59%, approx. 60%, approx. 61%, approx. 62%, approx. 63%, approx. 64%, approx. 65%, approx. 66%, approx. 67%, approx. 68%, approx. 69%, approx. 70%, approx. 71%, approx. 72%, approx. 73%, approx. 74%, approx. 75%, approx. 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%.
[0048] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with the polysaccharide. In some embodiments, a portion of the SPF is cross-linked with the SPF. In some embodiments, a portion of the polysaccharide is cross-linked with the polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the SPF is cross-linked up to about 100%. In some embodiments, the portion of the polysaccharide is cross-linked up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the cross-linking is achieved using a cross-linking agent, a cross-linking precursor, or an activator. In some embodiments, the cross-linking agent and / or the cross-linking precursor comprises epoxy groups. In some embodiments, the SPF is substantially devoid of sericin.
[0049] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with an SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the cross-linked SPF is up to about 100%. In some embodiments, the portion of the cross-linked polysaccharide is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the cross-linking is achieved using a cross-linking agent, a cross-linking precursor, or an activator. In some embodiments, the crosslinking agent and / or crosslinking precursor comprises an epoxy group. In some embodiments, the SPF is substantially devoid of sericin.
[0050] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with the polysaccharide. In some embodiments, a portion of the SPF is cross-linked with the SPF. In some embodiments, a portion of the polysaccharide is cross-linked with the polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of cross-linked SPF is up to about 100%. In some embodiments, the portion of cross-linked polysaccharide is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, crosslinking is achieved using a crosslinking agent, crosslinking precursor, or activator selected from the group consisting of 1,4-bis(2,3-epoxypropoxy)butane, 1,4-bisglycidyloxybutane, divinyl sulfone (DVS), 1,4-butanediol diglycidyl ether (BDDE), UV light, glutaraldehyde, 1,2-bis(2,3-epoxypropoxy)ethylene (EGDGE), 1,2,7,8-diepoxyoctane (DEO), biscarbodiimide (BCDI), pentaerythritol tetraglycidyl ether (PETGE), adipic acid dihydrazide (ADH), bis(sulfosuccinimidyl)suberate (BS), hexamethylenediamine (HMDA), 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane, carbodiimide, and any combination thereof. In some embodiments, the SPF is substantially devoid of sericin.
[0051] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the SPF is up to about 100% cross-linked. In some embodiments, the portion of the cross-linked polysaccharide is up to about 100% cross-linked. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, crosslinking is achieved using a crosslinking agent, crosslinking precursor, or activator selected from the group consisting of 1,4-bis(2,3-epoxypropoxy)butane, 1,4-bisglycidyloxybutane, divinyl sulfone (DVS), 1,4-butanediol diglycidyl ether (BDDE), UV light, glutaraldehyde, 1,2-bis(2,3-epoxypropoxy)ethylene (EGDGE), 1,2,7,8-diepoxyoctane (DEO), biscarbodiimide (BCDI), pentaerythritol tetraglycidyl ether (PETGE), adipic acid dihydrazide (ADH), bis(sulfosuccinimidyl)suberate (BS), hexamethylenediamine (HMDA), 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane, carbodiimide, and any combination thereof. In some embodiments, the SPF is substantially devoid of sericin.
[0052] In one embodiment, the present invention relates to a biocompatible tissue filler gel (e.g., a dermal filler gel) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight-average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with the polysaccharide. In some embodiments, a portion of the SPF is cross-linked with the SPF. In some embodiments, a portion of the polysaccharide is cross-linked with the polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of cross-linked SPF is up to about 100%. In some embodiments, the portion of cross-linked polysaccharide is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the gel further comprises water.
[0053] In one embodiment, the present invention relates to a biocompatible tissue filler gel (e.g., a skin filler gel) comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with an SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the SPF is up to about 100% cross-linked. In some embodiments, the portion of the cross-linked polysaccharide is up to about 100% cross-linked. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the gel further comprises water.
[0054] In one embodiment, the present invention relates to a biocompatible tissue filler hydrogel (e.g., a dermal filler hydrogel) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight-average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with the polysaccharide. In some embodiments, a portion of the SPF is cross-linked with the SPF. In some embodiments, a portion of the polysaccharide is cross-linked with the polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of cross-linked SPF is up to about 100%. In some embodiments, the portion of cross-linked polysaccharide is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the hydrogel further comprises water.
[0055] In one embodiment, the present invention relates to a biocompatible tissue filler hydrogel (e.g., a dermal filler hydrogel) comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with an SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the SPF is up to about 100% cross-linked. In some embodiments, the portion of the cross-linked polysaccharide is up to about 100% cross-linked. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the hydrogel further comprises water.
[0056] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with the polysaccharide. In some embodiments, a portion of the SPF is cross-linked with the SPF. In some embodiments, a portion of the polysaccharide is cross-linked with the polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the cross-linked SPF fraction is up to about 100%. In some embodiments, the cross-linked polysaccharide fraction is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is up to about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90 %, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, or greater than 60% crystallinity.
[0057] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the SPF is up to about 100% cross-linked. In some embodiments, the portion of the cross-linked polysaccharide is up to about 100% cross-linked. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is at most about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, about 100%, about 101%, about 1 %, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, or greater than 60% crystallinity.
[0058] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with the polysaccharide. In some embodiments, a portion of the SPF is cross-linked with the SPF. In some embodiments, a portion of the polysaccharide is cross-linked with the polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the cross-linked SPF fraction is up to about 100%. In some embodiments, the cross-linked polysaccharide fraction is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the tissue filler further comprises an active agent. In some embodiments, the active agent is selected from the group consisting of an enzyme inhibitor, an anesthetic, a medicinal neurotoxin, an antioxidant, an anti-infective, an anti-inflammatory, an ultraviolet (UV) light blocking agent, a dye, a hormone, an immunosuppressant, or an anti-inflammatory agent. In one embodiment, the anesthetic is lidocaine.
[0059] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with an SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the SPF is up to about 100% cross-linked. In some embodiments, the portion of the cross-linked polysaccharide is up to about 100% cross-linked. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the tissue filler further comprises an active agent. In some embodiments, the active agent is selected from the group consisting of an enzyme inhibitor, an anesthetic, a medicinal neurotoxin, an antioxidant, an anti-infective, an anti-inflammatory, an ultraviolet (UV) light blocking agent, a dye, a hormone, an immunosuppressant, or an anti-inflammatory agent, hi one embodiment, the anesthetic is lidocaine.
[0060] In one embodiment, the present invention relates to a biocompatible injectable tissue filler (e.g., an injectable dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with the polysaccharide. In some embodiments, a portion of the SPF is cross-linked with the SPF. In some embodiments, a portion of the polysaccharide is cross-linked with the polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of cross-linked SPF is up to about 100%. In some embodiments, the portion of cross-linked polysaccharide is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA).
[0061] In one embodiment, the present invention relates to a biocompatible injectable tissue filler (e.g., an injectable dermal filler) comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with an SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the SPF is up to about 100% cross-linked. In some embodiments, the portion of the cross-linked polysaccharide is up to about 100% cross-linked. In some embodiments, the polysaccharide is hyaluronic acid (HA).
[0062] In one embodiment, the present invention relates to a biocompatible tissue filler having a storage modulus (G') of about 50 Pa to about 1500 Pa (e.g., a dermal filler having a storage modulus (G') of about 50 Pa to about 1500 Pa), comprising a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has an average weight average molecular weight of about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is crosslinked. In some embodiments, a portion of the SPF is crosslinked with the polysaccharide. In some embodiments, a portion of the SPF is crosslinked with the SPF. In some embodiments, a portion of the polysaccharide is crosslinked with the polysaccharide. In some embodiments, the crosslinking comprises chemical bond crosslinking. In some embodiments, some of the crosslinks are zero-length crosslinks. In some embodiments, some of the crosslinks are self-crosslinks. In some embodiments, the portion of crosslinked SPF is up to about 100%. In some embodiments, the portion of crosslinked polysaccharide is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, G' is measured using an oscillatory stress of about 0.1 to about 10 Hz. In some embodiments, G' is measured using an oscillatory stress of about 1 Hz.
[0063] In one embodiment, the present invention relates to a biocompatible tissue filler (e.g., a dermal filler having a storage modulus (G') of about 50 Pa to about 1500 Pa) comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with the SPF. In some embodiments, a portion of the polysaccharide is cross-linked with the polysaccharide. In some embodiments, the cross-linking comprises chemical bond cross-linking. In some embodiments, a portion of the cross-linking is zero-length cross-linking. In some embodiments, a portion of the cross-linking is self-cross-linking. In some embodiments, the portion of the cross-linked SPF is up to about 100%. In some embodiments, the cross-linked polysaccharide fraction is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, G' is measured using an oscillatory stress of about 0.1 to about 10 Hz. In some embodiments, G' is measured using an oscillatory stress of about 1 Hz.
[0064] In some embodiments, the present invention relates to a method for producing a biocompatible woven filler (e.g., a dermal filler) comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, the method comprising providing a composition comprising SPF and a polysaccharide; and adding to the composition a crosslinker, crosslink precursor, activator, or gelation accelerator, wherein the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is crosslinked. In some embodiments, a portion of the SPF is crosslinked to the polysaccharide. In some embodiments, a portion of the SPF is crosslinked to the SPF. In some embodiments, a portion of the polysaccharide is crosslinked to the polysaccharide. In some embodiments, the tissue filler further comprises cross-linking moieties, e.g., epoxy-derived cross-linking moieties. In some embodiments, a portion of the cross-links are self-cross-linking. In some embodiments, the portion of cross-linked SPF is up to about 100%. In some embodiments, the portion of cross-linked polysaccharide is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water.
[0065] In some embodiments, the present invention relates to a method for producing a biocompatible woven filler (e.g., a dermal filler) comprising silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, the method comprising providing a composition comprising SPF and a polysaccharide; and adding a crosslinker, crosslink precursor, activator, or gelation accelerator to the composition, wherein the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is crosslinked. In some embodiments, a portion of the SPF is crosslinked with a polysaccharide. In some embodiments, a portion of the SPF is crosslinked with the SPF. In some embodiments, a portion of the polysaccharide is crosslinked with the polysaccharide. In some embodiments, the tissue filler further comprises crosslinked moieties, e.g., epoxy-derived crosslinking moieties. In some embodiments, a portion of the crosslinks are self-crosslinked. In some embodiments, the portion of the SPF is up to about 100% crosslinked. In some embodiments, the portion of the polysaccharide is up to about 100% crosslinked. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water.
[0066] In some embodiments, the present invention relates to a method of treating a condition (e.g., a skin condition) in a subject in need thereof, comprising administering to the subject a therapeutically effective amount of a biocompatible tissue filler (e.g., a dermal filler), wherein the biocompatible tissue filler comprises a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, and the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is crosslinked. In some embodiments, a portion of the SPF is crosslinked to the polysaccharide. In some embodiments, a portion of the SPF is crosslinked to the SPF. In some embodiments, a portion of the polysaccharide is crosslinked to the polysaccharide. In some embodiments, the tissue filler further comprises cross-linking moieties, e.g., epoxy-derived cross-linking moieties. In some embodiments, a portion of the cross-links are self-cross-linking. In some embodiments, the cross-linked SPF portion is up to about 100%. In some embodiments, the cross-linked polysaccharide portion is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water. In some embodiments, the skin condition is selected from the group consisting of skin dehydration, lack of skin elasticity, rough skin, lack of skin firmness, skin stretch lines, skin stretch marks, skin paleness, skin divots, sunken cheeks, thin lips, retro-orbital defects, facial creases, and wrinkles. In some embodiments, the tissue filler is administered to the dermal region of the subject. In some embodiments, the method is augmentation, reconstruction, treatment of disease, treatment of a disorder, or treatment of a defect or imperfection in a body part, region, or area. In some embodiments, the method is facial augmentation, facial reconstruction, treatment of a facial disease, treatment of a facial disorder, treatment of a facial defect, or treatment of a facial imperfection.In some embodiments, the tissue filler resists biodegradation, bioerosion, bioabsorption, and / or bioresorption for at least about 3 days, about 7 days, about 14 days, about 21 days, about 28 days, about 1 month, about 2 months, about 3 months, about 4 months, about 5 months, or about 6 months.
[0067] In some embodiments, the present invention relates to a method of treating a condition (e.g., a skin condition) in a subject in need thereof, comprising administering to the subject a therapeutically effective amount of a biocompatible tissue filler (e.g., a dermal filler), wherein the biocompatible tissue filler comprises silk protein fragments (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, and the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with an SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the tissue filler further comprises cross-linked moieties, e.g., epoxy-derived cross-linking moieties. In some embodiments, a portion of the cross-links is self-cross-linked. In some embodiments, the portion of the SPF is up to about 100% cross-linked. In some embodiments, the portion of the polysaccharide is up to about 100% cross-linked. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water. In some embodiments, the skin condition is selected from the group consisting of skin dehydration, lack of skin elasticity, rough skin, lack of skin firmness, skin stretch lines, skin stretch marks, skin paleness, dermal divots, sunken cheeks, thin lips, retro-orbital defects, facial creases, and wrinkles. In some embodiments, the tissue filler is administered to the dermal region of the subject. In some embodiments, the method is augmentation, reconstruction, treatment of disease, treatment of a disorder, treatment of a defect or imperfection in a body part, portion, or region. In some embodiments, the method is facial augmentation, facial reconstruction, treatment of a facial disease, treatment of a facial disorder, treatment of a facial defect, or treatment of a facial imperfection.In some embodiments, the tissue filler resists biodegradation, bioerosion, bioabsorption, and / or bioresorption for at least about 3 days, about 7 days, about 14 days, about 21 days, about 28 days, about 1 month, about 2 months, about 3 months, about 4 months, about 5 months, or about 6 months.
[0068] In some embodiments, the present invention relates to a method of cosmetic treatment in a subject in need thereof, comprising administering to the subject an effective amount of a biocompatible tissue filler (e.g., a dermal filler), wherein the biocompatible tissue filler comprises a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, and the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa, about 5 kDa to about 150 kDa, about 6 kDa to about 17 kDa, about 17 kDa to about 39 kDa, or about 39 kDa to about 80 kDa. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is crosslinked. In some embodiments, a portion of the SPF is crosslinked to the polysaccharide. In some embodiments, a portion of the SPF is crosslinked to the SPF. In some embodiments, a portion of the polysaccharide is crosslinked to the polysaccharide. In some embodiments, the tissue filler further comprises cross-linking moieties, e.g., epoxy-derived cross-linking moieties. In some embodiments, a portion of the cross-links are self-cross-linking. In some embodiments, the cross-linked SPF portion is up to about 100%. In some embodiments, the cross-linked polysaccharide portion is up to about 100%. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water. In some embodiments, the tissue filler is administered to a dermal region of a subject. In some embodiments, the method is augmentation, reconstruction, treatment of a disease, treatment of a disorder, treatment of a defect or imperfection in a body part, portion, or region. In some embodiments, the method is facial augmentation, facial reconstruction, treatment of a facial disease, treatment of a facial disorder, treatment of a facial defect, or treatment of a facial imperfection. In some embodiments, the tissue filler resists biodegradation, bioerosion, bioabsorption, and / or bioresorption for at least about 3 days, about 7 days, about 14 days, about 21 days, about 28 days, about 1 month, about 2 months, about 3 months, about 4 months, about 5 months, or about 6 months.
[0069] In some embodiments, the present invention relates to a method of cosmetic treatment in a subject in need thereof, comprising administering to the subject an effective amount of a biocompatible tissue filler (e.g., a dermal filler), wherein the biocompatible tissue filler comprises a silk protein fragment (SPF) having a polydispersity of about 1.5 to about 3.0 and a polysaccharide, and the SPF has a low, medium, and / or high molecular weight. In some embodiments, the tissue filler is biodegradable. In some embodiments, a portion of the SPF is cross-linked. In some embodiments, a portion of the SPF is cross-linked with a polysaccharide. In some embodiments, a portion of the SPF is cross-linked with an SPF. In some embodiments, a portion of the polysaccharide is cross-linked with a polysaccharide. In some embodiments, the tissue filler further comprises cross-linked moieties, e.g., epoxy-derived cross-linking moieties. In some embodiments, a portion of the cross-links is self-cross-linked. In some embodiments, the portion of the SPF is up to about 100% cross-linked. In some embodiments, the portion of the polysaccharide is up to about 100% cross-linked. In some embodiments, the polysaccharide is hyaluronic acid (HA). In some embodiments, the SPF is substantially devoid of sericin. In some embodiments, the tissue filler further comprises water. In some embodiments, the tissue filler is administered to a dermal region of a subject. In some embodiments, the method is augmentation, reconstruction, treatment of a disease, treatment of a disorder, treatment of a defect or imperfection in a body part, portion, or region. In some embodiments, the method is facial augmentation, facial reconstruction, treatment of a facial disease, treatment of a facial disorder, treatment of a facial defect, or treatment of a facial imperfection. In some embodiments, the tissue filler is resistant to biodegradation, bioerosion, bioabsorption, and / or bioresorption for at least about 3 days, about 7 days, about 14 days, about 21 days, about 28 days, about 1 month, about 2 months, about 3 months, about 4 months, about 5 months, or about 6 months.
[0070] In some embodiments, the present invention relates to a biocompatible tissue filler comprising hyaluronic acid (HA) and an anesthetic, wherein a portion of the HA is modified with one or more linker moieties comprising one or more of an alkane or alkyl chain, an ether group, and a secondary alcohol, the linker moiety being attached to the HA at one end of the linker. In some embodiments, the modification is achieved using a crosslinker, crosslink precursor, or activator. In some embodiments, the HA in the tissue filler is about 10.0%, about 10.1%, about 10.2%, about 10.3%, about 10.4%, about 10.5%, about 10.6%, about 10.7%, about 10.8%, about 10.9%, about 11.0%, about 11.1%, about 11.2%, about 11.3%, about 11.4%, about 11.5%, about 11.6%, about 11.7%, about 11.8%, about 11.9%, about 12.0%, about 12.1%, about 12.2%, about 12.3%, about 12.4%, about 12.5%, about 12.6%, about 12.7%, about 12.8%, about 12.9%, about 13.0%, about 13.1%, about 13.10%, about 13.11%, about 13.12%, about 13.13%, about 13.14%, about 13.15%, about 13.16%, about 13.17%, about 13.18%, about 13.19%, about 14.20%, about 14.21%, about 14.22%, about 14.23%, about 14.24%, about 14.25%, about 14.26%, about 14.27%, about 14.28%, about 14.29%, about 14.30%, about 14.31%, about 14.32%, about 14.33%, about 14.34%, about 14.35%, about 14.36%, about 14.37%, about 14.38%, about 14.39%, about 14.40%, about 14.41%, about 14.42%, about 14.43%, about 2.3%, approx. 12.4%, approx. 12.5%, approx. 12.6%, approx. 12.7%, approx. 12.8%, approx. 12.9%, approx. 13.0%, approx. 13.1%, approx. 13.2%, approx. 13.3%, approx. 13.4%, approx. 13.5%, approx. 13.6%, approx. 13.7%, approx. 13.8%, approx. 13.9%, approx. 14.0%, approx. 14.1%, approx. 14.2%, approx. 14.3%, approx. 14.4%, approx. 14.5%, approx. 14.6%, approx. 14.7%, approx. 14.8%, approx. 14.9% ,approx. 15.0%,approx. 15.1%,approx. 15.2%,approx. 15.3%,approx. 15.4%,approx. 15.5%,approx. 15.6%,approx. 15.7%,approx. 15.8%,approx. 15.9%,approx. 16.0%,approx. 16.1%,approx. 16.2%,approx. 16.3%,approx. 16.4%,approx. 16.5%,approx. 16.6%,approx. 16.7%,approx. 16.8%,approx. 16.9%,approx. 17.0%,approx. 17.1%,approx. 17.2%,approx. 17.3%,approx. 17.4%,approx. 17.5%,approx. 17.6%,approx. 0.6%, about 17.7%, about 17.8%, about 17.9%, about 18.0%, about 18.1%, about 18.2%, about 18.3%, about 18.4%, about 18.5%, about 18.6%, about 18.7%, about 18.8%, about 18.9%, about 19.0%, about 19.1%, about 19.2%, about 19.3%, about 19.4%, about 19.5%, about 19.6%, about 19.7%, about 19.8%, about 19.9%, or about 20.0% Modification of Degree of Denaturation (MoD).In some embodiments, the amount of denatured HA relative to the total amount of HA in the tissue filler (% w / w) is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about %, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47% ,approximately 48%,approximately 49%,approximately 50%,approximately 51%,approximately 52%,approximately 53%,approximately 54%,approximately 55%,approximately 56%,approximately 57%,approximately 58%,approximately 59%,approximately 60%,approximately 61%,approximately 62%,approximately 63%,approximately 64%,approximately 65%,approximately 66%,approximately 67%,approximately 68%,approximately 69%,approximately 70%,approximately 71%,approximately 72%,approximately 73%,approximately 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%.
[0071] In some embodiments, the modified HA comprises cross-linked HA, and the degree of cross-linking of the cross-linked HA is about 1% to about 100%. In some embodiments, the degree of cross-linking of the cross-linked HA is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, 4%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50% 0%, approx. 51%, approx. 52%, approx. 53%, approx. 54%, approx. 55%, approx. 56%, approx. 57%, approx. 58%, approx. 59%, approx. 60%, approx. 61%, approx. 62%, approx. 63%, approx. 64%, approx. 65%, approx. 66%, approx. 67%, approx. 68%, approx. 69%, approx. 70%, approx. 71%, approx. 72%, approx. 73%, approx. 74%, approx. 75%, approx. In some embodiments, the degree of crosslinking of the crosslinked HA is about 1% to about 15%.
[0072] In some embodiments, the modified or crosslinked HA comprises a linker or crosslinking moiety comprising a polyethylene glycol (PEG) chain. In some embodiments, the crosslinker and / or crosslinking precursor comprises an epoxy group. In some embodiments, the modification or crosslinking is achieved by a polyepoxy linker, diepoxy linker, polyepoxy-PEG, diepoxy-PEG, polyglycidyl-PEG, diglycidyl-PEG, polyacrylate PEG, diacrylate PEG, 1,4-bis(2,3-epoxypropoxy)butane, 1,4-bisglycidyloxybutane, divinyl sulfone (DVS), 1,4-butanediol diglycidyl ether (BDDE), UV light, glutaraldehyde, 1,2-bis(2,3-epoxypropoxy)ethoxy. The crosslinking agent, crosslinking precursor, or activator may be selected from the group consisting of ethylenediamine (EGDGE), 1,2,7,8-diepoxyoctane (DEO), biscarbodiimide (BCDI), pentaerythritol tetraglycidyl ether (PETGE), adipic acid dihydrazide (ADH), bis(sulfosuccinimidyl) suberate (BS), hexamethylenediamine (HMDA), 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane, carbodiimide, and any combination thereof. In some embodiments, the modification or crosslinking is achieved using a multifunctional epoxy compound selected from the group consisting of 1,4-butanediol diglycidyl ether (BDDE), ethylene glycol diglycidyl ether (EGDGE), 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, polyglycerol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, pentaerythritol polyglycidyl ether, and sorbitol polyglycidyl ether.In some embodiments, the modification or crosslinking is achieved using a crosslinker and / or crosslinking precursor selected from the group consisting of polyethylene glycol diglycidyl ether, diepoxy PEG, PEG diglycidyl ether, polyoxyethylene bis-glycidyl ether, PEGDE, and PEGDGE. In some embodiments, the modification or crosslinking has an average M of about 500, about 1000, about 2000, or about 6000. n In some embodiments, the modification or crosslinking is achieved using a polyethylene glycol diglycidyl ether having from about 2 to about 25 ethylene glycol groups. In some embodiments, the modification or crosslinking is achieved using a crosslinker and / or crosslinking precursor selected from the group consisting of a polyepoxy silk fibroin linker, a diepoxy silk fibroin linker, a polyepoxy silk fibroin fragment linker, a diepoxy silk fibroin fragment linker, a polyglycidyl silk fibroin linker, a diglycidyl silk fibroin linker, a polyglycidyl silk fibroin fragment linker, and a diglycidyl silk fibroin fragment linker.
[0073] In some embodiments, the tissue filler further comprises an organic compound and / or an inorganic compound. In some embodiments, the inorganic compound comprises calcium hydroxyapatite. In some embodiments, the calcium hydroxyapatite is formulated as particles having a diameter of about 1 μm to about 100 μm, about 1 μm to about 10 μm, about 2 μm to about 12 μm, about 3 μm to about 10 μm, about 4 μm to about 15 μm, about 8 μm to about 12 μm, about 5 μm to about 10 μm, about 6 μm to about 12 μm, about 7 μm to about 20 μm, about 9 μm to about 18 μm, or about 10 μm to about 25 μm. In some embodiments, the concentration of calcium hydroxyapatite is about 0.001% to about 5%. In some embodiments, the concentration of calcium hydroxyapatite is about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.011%, about 0.012%, about 0.013%, about 0.014%, about 0.015%, about 0.016%, about 0.017%, about 0.018%, about 0.019%, or about 0.02%. In some embodiments, the concentration of calcium hydroxyapatite is about 0.05%, about 0.1%, about 0.15%, about 0.2%, about 0.25%, about 0.3%, about 0.35%, about 0.4%, about 0.45%, about 0.5%, about 0.55%, about 0.6%, about 0.65%, about 0.7%, about 0.75%, about 0.8%, about 0.85%, about 0.9 %, about 0.95%, about 1%, about 1.05%, about 1.1%, about 1.15%, about 1.2%, about 1.25%, about 1.3%, about 1.35%, about 1.4%, about 1.45%, about 1.5%, about 1.55%, about 1.6%, about 1.65%, about 1.7%, about 1.75%, about 1.8%, about 1.85%, about 1.9%, about 1.95%, or about 2%. In some embodiments, the organic compound comprises an amino acid selected from the group consisting of glycine, L-proline, alanine, arginine, asparagine, aspartic acid, cysteine, glutamic acid, glutamine, histidine, isoleucine, leucine, lysine, methionine, phenylalanine, proline, serine, threonine, tryptophan, tyrosine, and valine.
[0074] In some embodiments, the HA is obtained from Streptococcus or Bacillus subtilis. In some embodiments, the active agent is lidocaine. In some embodiments, the concentration of the active agent in the tissue filler is about 0.001% to about 5%. In some embodiments, the concentration of lidocaine in the tissue filler is about 0.3%.
[0075] In some embodiments, the tissue fillers disclosed herein are gels. In some embodiments, the tissue fillers are hydrogels. In some embodiments, the tissue fillers further comprise water. In some embodiments, the total concentration of HA in the tissue filler is about 10 mg / mL to about 50 mg / mL. In some embodiments, the total concentration of HA in the tissue filler is about 15 mg / mL, about 16 mg / mL, 17 mg / mL, about 18 mg / mL, about 19 mg / mL, about 20 mg / mL, about 21 mg / mL, about 22 mg / mL, about 23 mg / mL, about 24 mg / mL, about 25 mg / mL, about 26 mg / mL, about 27 mg / mL, about 28 mg / mL, about 29 mg / mL, or about 30 mg / mL. In some embodiments, the concentration of modified or crosslinked HA in the tissue filler is about 10 mg / mL to about 50 mg / mL. In some embodiments, the concentration of the modified or crosslinked HA in the tissue filler is about 15 mg / mL, about 16 mg / mL, about 17 mg / mL, about 18 mg / mL, about 19 mg / mL, about 20 mg / mL, about 21 mg / mL, about 22 mg / mL, about 23 mg / mL, about 24 mg / mL, about 25 mg / mL, about 26 mg / mL, about 27 mg / mL, about 28 mg / mL, about 29 mg / mL, or about 30 mg / mL.
[0076] In some embodiments, the disclosed tissue fillers further comprise silk protein or silk protein fragments (SPF). In some embodiments, the silk protein is silk fibroin. In some embodiments, the silk protein is silk fibroin that is substantially free of sericin. In some embodiments, the SPF has an average weight average molecular weight of about 1 kDa to about 250 kDa. In some embodiments, the SPF has an average weight average molecular weight of about 5 kDa to about 150 kDa. In some embodiments, the SPF has an average weight average molecular weight of about 6 kDa to about 17 kDa. In some embodiments, the SPF has an average weight average molecular weight of about 17 kDa to about 39 kDa. In some embodiments, the SPF has an average weight average molecular weight of about 39 kDa to about 80 kDa. In some embodiments, the SPF has a low molecular weight. In some embodiments, the SPF has a medium molecular weight. In some embodiments, the SPF has a high molecular weight. In some embodiments, the silk protein fragments (SPF) have a polydispersity of about 1.5 to about 3.0, hi some embodiments, the SPF have a crystallinity of up to 60%.
[0077] In some embodiments, the present invention relates to a tissue filler comprising HA and SPF, wherein a portion of the SPF is modified or crosslinked. In some embodiments, the amount of modified or crosslinked SPF relative to the total amount of SPF (% w / w) is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, approximately 49%, approximately 50%, approximately 51%, approximately 52%, approximately 53%, approximately 54%, approximately 55%, approximately 56%, approximately 57%, approximately 58%, approximately 59%, approximately 60%, approximately 61%, approximately 62%, approximately 63%, approximately 64%, approximately 65%, approximately 66%, approximately 67%, approximately 68%, approximately 69%, approximately 70%, approximately 71%, approximately 72%, approximately 73%, approximately 74%, approximately 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%. In some embodiments, the degree of modification or crosslinking of the modified or crosslinked SPF is about 1% to about 100%.In some embodiments, the degree of modification or crosslinking of the modified or crosslinked SPF is about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, about 1 Approximately 23%, approximately 24%, approximately 25%, approximately 26%, approximately 27%, approximately 28%, approximately 29%, approximately 30%, approximately 31%, approximately 32%, approximately 33%, approximately 34%, approximately 35%, approximately 36%, approximately 37%, approximately 38%, approximately 39%, approximately 40%, approximately 41%, approximately 42%, approximately 43%, approximately 44%, approximately 45%, approximately 46%, approximately 47%, approximately 48%, approximately 49% 9%, approximately 50%, approximately 51%, approximately 52%, approximately 53%, approximately 54%, approximately 55%, approximately 56%, approximately 57%, approximately 58%, approximately 59%, approximately 60%, approximately 61%, approximately 62%, approximately 63%, approximately 64%, approximately 65%, approximately 66%, approximately 67%, approximately 68%, approximately 69%, approximately 70%, approximately 71%, approximately 72%, approximately 73%, approximately 74%, approximately 75% , about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, or about 100%. In some embodiments, the degree of modification or crosslinking of the modified or crosslinked SPF is about 1% to about 15%. In some embodiments, the degree of modification or crosslinking of the modified or crosslinked SPF is one or more of about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, and about 15%.
[0078] In some embodiments, the modified or crosslinked SPF comprises a linker or crosslinking moiety comprising an alkane or alkyl chain and / or an ether group, with the linker or crosslinking moiety attached to the SPF at one end of the linker or crosslinking moiety. In some embodiments, the modified or crosslinked SPF comprises a linker or crosslinking moiety comprising a polyethylene glycol (PEG) chain. In some embodiments, the modified or crosslinked SPF comprises a linker or crosslinking moiety comprising a secondary alcohol. In some embodiments, the modification or crosslinking is achieved using a modifying or crosslinking agent, a modified or crosslinking precursor, or an activator. In some embodiments, the modified or crosslinking agent and / or the modified or crosslinking precursor comprises an epoxy group. In some embodiments, the modification or crosslinking is performed using a polyepoxy linker, a diepoxy linker, a polyepoxy-PEG, a diepoxy-PEG, a polyglycidyl-PEG, a diglycidyl-PEG, a polyacrylate PEG, a diacrylate PEG, 1,4-bis(2,3-epoxypropoxy)butane, 1,4-bisglycidyloxybutane, divinyl sulfone (DVS), 1,4-butanediol diglycidyl ether (BDDE), UV light, glutaraldehyde, 1,2-bis(2,3-epoxypropoxy)ethylene (E The modified or crosslinked polymer may be obtained using a modifying or crosslinking agent, a modified or crosslinked precursor, or an activating agent selected from the group consisting of bis(sulfosuccinimidyl)suberate (BS), hexamethylenediamine (HMDA), 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane, carbodiimide, and any combination thereof.In some embodiments, the modification or crosslinking is achieved using a multifunctional epoxy compound selected from the group consisting of 1,4-butanediol diglycidyl ether (BDDE), ethylene glycol diglycidyl ether (EGDGE), 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, polyglycerol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, pentaerythritol polyglycidyl ether, and sorbitol polyglycidyl ether.
[0079] In some embodiments, the modification or crosslinking is achieved using a crosslinking agent and / or crosslinking precursor selected from the group consisting of polyethylene glycol diglycidyl ether, diepoxy PEG, PEG diglycidyl ether, polyoxyethylene bis-glycidyl ether, PEGDE, and PEGDGE. ... n In some embodiments, the modification or crosslinking is achieved using a polyethylene glycol diglycidyl ether having from about 2 to about 25 ethylene glycol groups. In some embodiments, the modification or crosslinking is achieved using a modifying or crosslinking agent and / or a modified or crosslinking precursor selected from the group consisting of a polyepoxy silk fibroin linker, a diepoxy silk fibroin linker, a polyepoxy silk fibroin fragment linker, a diepoxy silk fibroin fragment linker, a polyglycidyl silk fibroin linker, a diglycidyl silk fibroin linker, a polyglycidyl silk fibroin fragment linker, and a diglycidyl silk fibroin fragment linker.
[0080] In some embodiments, the present invention relates to a tissue filler comprising HA and SPF, wherein a portion of the SPF is crosslinked to the HA. In some embodiments, the present invention relates to a tissue filler comprising HA and SPF, wherein a portion of the SPF is crosslinked to the SPF. In some embodiments, the tissue filler is a gel. In some embodiments, the tissue filler is a hydrogel. In some embodiments, the tissue filler further comprises water. In some embodiments, the total concentration of SPF in the tissue filler is from about 0.1 mg / mL to about 15 mg / mL. In some embodiments, the total concentration of SPF in the tissue filler is about 0.1 mg / mL, about 0.5 mg / mL, about 1 mg / mL, about 1.5 mg / mL, about 2 mg / mL, about 2.5 mg / mL, about 3 mg / mL, about 3.5 mg / mL, about 4 mg / mL, about 4.5 mg / mL, about 5 mg / mL, about 5.5 mg / mL, about 6 mg / mL, about 6.5 mg / mL, about 7 mg / mL, about 7.5 mg / mL, about 8 mg / mL, about 8.5 mg / mL, about 9 mg / mL, about 9.5 mg / mL, about 10 mg / mL, about 10.5 mg / mL, about 11 mg / mL, about 11.5 mg / mL, about 12 mg / mL, about 12.5 mg / mL, about 13 mg / mL, about 13.5 mg / mL, about 14 mg / mL, about 14.5 mg / mL, or about 15 mg / mL. In some embodiments, the concentration of the modified or crosslinked SPF in the tissue filler is from about 0.1 mg / mL to about 15 mg / mL. In some embodiments, the concentration of the modified or crosslinked SPF in the tissue filler is about 0.1 mg / mL, about 0.5 mg / mL, about 1 mg / mL, about 1.5 mg / mL, about 2 mg / mL, about 2.5 mg, about 3 mg / mL, about 3.5 mg / mL, about 4 mg / mL, about 4.5 mg / mL, about 5 mg / mL, about 5.5 mg / mL, about 6 mg / mL, about 6.5 mg / mL, about 7 mg / mL, about 7.5 mg / mL, about 8 mg / mL, about 8.5 mg / mL, about 9 mg / mL, about 9.5 mg / mL, about 10 mg / mL, about 10.5 mg / mL, about 11 mg / mL, about 11.5 mg / mL, about 12 mg / mL, about 12.5 mg / mL, about 13 mg / mL, about 13.5 mg / mL, about 14 mg / mL, about 14.5 mg / mL, or about 15 mg / mL.
[0081] In some embodiments, the present invention relates to a tissue filler that is a dermal filler, comprising modified or crosslinked HA and / or modified or crosslinked SPF. In some embodiments, the tissue filler is biodegradable. In some embodiments, the tissue filler is injectable. In some embodiments, the tissue filler has a storage modulus (G') of about 25 Pa to about 1500 Pa. In some embodiments, the tissue filler has a storage modulus (G') of about 25 Pa, about 26 Pa, about 27 Pa, about 28 Pa, about 29 Pa, about 30 Pa, about 31 Pa, about 32 Pa, about 33 Pa, about 34 Pa, about 35 Pa, about 36 Pa, about 37 Pa, about 38 Pa, about 39 Pa, about 40 Pa, about 41 Pa, about 42 Pa, about 43 Pa, about 44 Pa, about 45 Pa, about 46 Pa, about 47 Pa, about 48 Pa, about 49 Pa, about 50 Pa, about 51 Pa, about 52 Pa, about 53 Pa, about 54 Pa, about 55 Pa, about 56 Pa, about 57 Pa, about 58 Pa, about 59 Pa, about 60 Pa, about 61 Pa, about 62 Pa, about 63 Pa, about 64 Pa, about 65 Pa, about 66 Pa, about 67 Pa, about 68 Pa, about 69 Pa, about 70 Pa, about 71 Pa, about 72 Pa, about 73 Pa, about 74 Pa, about 75 Pa, about 76 Pa, about 77 Pa, about 78 Pa, about 79 Pa, about 80 Pa, about 81 Pa, about 82 Pa, about 83 Pa, about 84 Pa, about 85 Pa, about 86 Pa, about 87 Pa, about 88 Pa, about 89 Pa, about Pa, approximately 50Pa, approximately 51Pa, approximately 52Pa, approximately 53Pa, approximately 54Pa, approximately 55Pa, approximately 56Pa, approximately 57Pa, approximately 58Pa, approximately 59Pa, approximately 60Pa, approximately 61Pa, approximately 62Pa, approximately 6 3Pa, about 64Pa, about 65Pa, about 66Pa, about 67Pa, about 68Pa, about 69Pa, about 70Pa, about 71Pa, about 72Pa, about 73Pa, about 74Pa, about 75Pa, about 76Pa, about 7 7 Pa, approximately 78 Pa, approximately 79 Pa, approximately 80 Pa, approximately 81 Pa, approximately 82 Pa, approximately 83 Pa, approximately 84 Pa, approximately 85 Pa, approximately 86 Pa, approximately 87 Pa, approximately 88 Pa, approximately 89 Pa, approximately 90 Pa, approximately 91 Pa, approximately 92 Pa, approximately 93 Pa, approximately 94 Pa, approximately 95 Pa, approximately 96 Pa, approximately 97 Pa, approximately 98 Pa, approximately 99 Pa, approximately 100 Pa, approximately 101 Pa, approximately 102 Pa, approximately 103 Pa, approximately 10 The composition has a storage modulus (G') of about 4 Pa, about 10 Pa, about 10 Pa, about 10 Pa, about 10 Pa, about 10 Pa, about 10 Pa, about 10 Pa, about 110 Pa, about 111 Pa, about 112 Pa, about 113 Pa, about 114 Pa, about 115 Pa, about 116 Pa, about 117 Pa, about 118 Pa, about 119 Pa, about 120 Pa, about 121 Pa, about 122 Pa, about 123 Pa, about 124 Pa, or about 125 Pa. In some embodiments, G' is measured using an oscillatory stress of about 0.1 to about 10 Hz. In some embodiments, G' is measured using an oscillatory stress of about 1 Hz. In some embodiments, G' is measured using an oscillatory stress of about 5 Hz. In some embodiments, G' is measured using an oscillatory stress of about 10 Hz.In some embodiments, the tissue filler has a complex viscosity of about 1 Pa·s to about 10 Pa·s. In some embodiments, the tissue filler has a complex viscosity of about 1 Pa·s, about 1.5 Pa·s, about 2 Pa·s, about 2.5 Pa·s, about 3 Pa·s, about 3.5 Pa·s, about 4 Pa·s, about 4.5 Pa·s, about 5 Pa·s, about 5.5 Pa·s, about 6 Pa·s, about 6.5 Pa·s, about 7 Pa·s, about 7.5 Pa·s, about 8 Pa·s, about 8.5 Pa·s, about 9 Pa·s, about 9.5 Pa·s, or about 10 Pa·s. In some embodiments, the complex viscosity is measured using an oscillatory stress of about 0.1 to about 10 Hz. In some embodiments, the complex viscosity is measured using an oscillatory stress of about 1 Hz. In some embodiments, the complex viscosity is measured using an oscillatory stress of about 5 Hz.
[0082] In some embodiments, the present invention relates to a method of treating a condition in a subject in need thereof, comprising administering to the subject a therapeutically effective amount of a tissue filler comprising modified or crosslinked HA and / or modified or crosslinked SPF. In some embodiments, the condition is a skin condition. In some embodiments, the skin condition is selected from the group consisting of skin dehydration, lack of skin elasticity, rough skin, lack of skin firmness, skin stretch lines, skin stretch marks, skin pallor, skin divots, sunken cheeks, thin lips, retro-orbital defects, facial creases, and wrinkles.
[0083] In some embodiments, the present invention relates to a method of cosmetic treatment in a subject in need thereof, comprising administering to the subject an effective amount of a tissue filler comprising denatured or crosslinked HA and / or denatured or crosslinked SPF. In some embodiments, the tissue filler is administered to the dermal region of the subject. In some embodiments, the method is augmentation, reconstruction, treatment of a disease, treatment of a disorder, treatment of a defect or imperfection in a body part, portion, or region. In some embodiments, the method is facial augmentation, facial reconstruction, treatment of a facial disease, treatment of a facial disorder, treatment of a facial defect, or treatment of a facial imperfection.
[0084] In some embodiments of the methods disclosed herein, the tissue filler resists biodegradation, bioerosion, bioabsorption, and / or bioresorption for at least about 3 days, about 7 days, about 14 days, about 21 days, about 28 days, about 1 month, about 2 months, about 3 months, about 4 months, about 5 months, or about 6 months. In some embodiments of the methods disclosed herein, administration of the tissue filler to a subject reduces an inflammatory response compared to the inflammatory response induced by a control tissue filler comprising a polysaccharide and lidocaine but no silk protein fragments (SPF).
[0085] In some embodiments of the methods disclosed herein, administration of the tissue filler to a subject increases collagen production compared to collagen production induced by a control tissue filler comprising polysaccharides and lidocaine but not silk protein fragments (SPF).
[0086] The presently disclosed embodiments will be further described with reference to the accompanying drawings, in which the drawings are not necessarily to scale, emphasis instead generally being placed upon illustrating the principles of the presently disclosed embodiments. [Brief explanation of the drawings]
[0087] [Figure 1] FIG. 1 is a flow chart illustrating various embodiments for producing pure silk fibroin-based protein fragments (SPF) of the present disclosure. [Figure 2] FIG. 2 is a flow chart illustrating various parameters that can be varied during the extraction and dissolution steps during the process of making the SPF of the present disclosure. [Figure 3] FIG. 3 is a table summarizing the concentrations of LiBr and sodium carbonate (Na2CO3) in silk protein solutions of the present disclosure. [Figure 4] FIG. 4 is a table summarizing the concentrations of LiBr and Na2CO3 in silk protein solutions of the present disclosure. [Figure 5]FIG. 5 is a table summarizing the molecular weights of silk protein solutions of the present disclosure. [Figure 6] FIG. 6 is a graph depicting the effect of extraction volume on % mass loss. [Figure 7] FIG. 7 is a graph depicting the effect of extraction volume on % mass loss. [Figure 8] FIG. 8 is a table summarizing the molecular weight of silk dissolved from various concentrations of LiBr and various extraction and dissolution sizes. [Figure 9] Figure 9 is a graph summarizing the effect of extraction time on the molecular weight of silk treated with 100°C extraction temperature, 100°C LiBr, and 100°C oven dissolution conditions (varying oven / dissolution times). [Figure 10] FIG. 10 is a graph summarizing the effect of extraction time on the molecular weight of silk treated with an extraction temperature of 100° C., boiling LiBr, and oven dissolution at 60° C. (varying oven / dissolution times). [Figure 11] FIG. 11 is a graph summarizing the effect of extraction time on the molecular weight of silk treated with 100° C. extraction temperature, 60° C. LiBr, and 60° C. oven dissolution conditions (varying oven / dissolution times). [Figure 12] FIG. 12 is a graph summarizing the effect of extraction time on the molecular weight of silk treated with 100° C. extraction temperature, 80° C. LiBr, and 80° C. oven dissolution conditions (varying oven / dissolution times). [Figure 13] FIG. 13 is a graph summarizing the effect of extraction time on the molecular weight of silk treated with an extraction temperature of 100° C., LiBr at 80° C., and oven dissolution at 60° C. (varying oven / dissolution times). [Figure 14] FIG. 14 is a graph summarizing the effect of extraction time on the molecular weight of silk treated with 100° C. extraction temperature, 100° C. LiBr, and 60° C. oven dissolution conditions (varying oven / dissolution times). [Figure 15]FIG. 15 is a graph summarizing the effect of extraction time on the molecular weight of silk treated with 100° C. extraction temperature, 140° C. LiBr, and 140° C. oven dissolution conditions (varying oven / dissolution times). [Figure 16] FIG. 16 is a graph summarizing the effect of extraction temperature on the molecular weight of silk treated with 60 minute extraction time, 100° C. LiBr, and 100° C. oven dissolution (varying oven / dissolution times). [Figure 17] FIG. 17 is a graph summarizing the effect of LiBr temperature on the molecular weight of silk processed under conditions of 60 min extraction time, 100° C. extraction temperature, and 60° C. oven dissolution (varying oven / dissolution times). [Figure 18] FIG. 18 is a graph summarizing the effect of LiBr temperature on the molecular weight of silk processed under conditions of 30 min extraction time, 100° C. extraction temperature, and 60° C. oven dissolution (varying oven / dissolution times). [Figure 19] Figure 19 is a graph summarizing the effect of oven / dissolution temperature on the molecular weight of silk treated with an extraction temperature of 100°C, an extraction time of 30 minutes, and lithium bromide at 100°C (varying oven / dissolution times). [Figure 20] Figure 20 is a graph summarizing the effect of oven / dissolution temperature on the molecular weight of silk treated with an extraction temperature of 100°C, an extraction time of 60 minutes, and lithium bromide at 100°C (varying oven / dissolution times). [Figure 21] Figure 21 is a graph summarizing the effect of oven / dissolution temperature on the molecular weight of silk treated with an extraction temperature of 100°C, an extraction time of 60 minutes, and lithium bromide at 140°C (varying oven / dissolution times). [Figure 22] Figure 22 is a graph summarizing the effect of oven / dissolution temperature on the molecular weight of silk treated with an extraction temperature of 100°C, an extraction time of 30 minutes, and lithium bromide at 140°C (varying oven / dissolution times). [Figure 23]Figure 23 is a graph summarizing the effect of oven / dissolution temperature on the molecular weight of silk treated with an extraction temperature of 100°C, an extraction time of 60 minutes, and lithium bromide at 80°C (varying oven / dissolution times). [Figure 24] FIG. 24 is a graph summarizing the molecular weight of silk treated under various conditions including extraction time, extraction temperature, lithium bromide (LiBr) temperature, oven temperature for dissolution, and oven time for dissolution. [Figure 25] FIG. 25 is a graph summarizing the molecular weight of silk treated at oven / melt temperatures equal to that of LiBr. [Figure 26] Figure 26 shows photographs of aqueous silk / HA formulations at various concentrations in water or phosphate buffered saline (PBS), showing that the silk / HA formulations are homogeneous, opaque solutions. The first unmarked vial is the control vial (22 mg / mL HA in water). [Figure 27] Figure 27 is a photograph of the aqueous silk / HA formulation loaded into a syringe, showing that the silk / HA formulation is a homogeneous, opaque solution. The control is a solution of 22 mg / mL HA in water. [Figure 28] Figure 28 is a chart showing the degradation profiles of silk-HA and HA hydrogels. [Figure 29] Figure 29 shows photographs of intradermal areas in guinea pigs injected with a control dermal filler (a commercially available HA filler containing lidocaine). The increased level of inflammation is reflected by the extent of the granulomatous area. The commercially available filler is observed as a blue / gray substance. Granulomatous inflammation associated with this substance can be observed for 7 days. [Figure 30] Figure 30 shows a photograph of an intradermal area in a guinea pig injected with a control dermal filler (a commercially available HA filler containing lidocaine). The commercial product appears as a blue / gray substance. At 30 days, inflammation accompanied by fibrosis can be observed. [Figure 31]Figure 31 is a photograph of an intradermal area in a guinea pig injected with a silk-HA dermal filler of the present invention (24 mg / mL HA, 9.6 mg / mL silk, BDDE crosslinked). The reduced granulomatous area compared to the control injection indicates a negligible acute inflammatory response and good biodegradability of the silk-HA filler compared to the control. There is little inflammation at 7 days. Inflammation is localized and can be difficult to detect. No implant material is observed. [Figure 32] Figure 32 is a photograph of an intradermal area in a guinea pig injected with a silk-HA dermal filler of the present invention (24 mg / mL HA, 9.6 mg / mL silk, BDDE crosslinked). At 30 days, inflammation is very minimal and hardly noticeable. No implant material is observed. [Figure 33] Figure 33 is a photograph of an intradermal area in a guinea pig injected with a silk-HA dermal filler of the present invention (24 mg / mL HA, 0.48 mg / mL silk, BDDE crosslinked). At 7 days, the filler produces localized, mild inflammation. The inflammation is chronic. This inflammation was localized and minimal, requiring close evaluation to identify. No implant material is observed. [Figure 34] Figure 34 is a photograph of an intradermal area in a guinea pig injected with a silk-HA dermal filler of the present invention (24 mg / mL HA, 0.48 mg / mL silk, BDDE crosslinked). The 30-day image shows a lower degree of inflammation, which was more difficult to identify compared to the 7-day implant. No implant material is observed. [Figure 35] Figure 35 is a chart showing turbidity measurements of silk-HA hydrogels. Black curve (a): standard transmittance; red curve (b): transmittance plus forward scattering. [Figure 36] Figure 36 is a chart showing turbidity measurements of silk-free HA hydrogels. Black curve (a): standard transmittance; red curve (b): transmittance plus forward scattering. [Figure 37] FIG. 37 is a representative histological photograph of an intradermal area in a guinea pig injected with a control dermal filler. [Figure 38]Figure 38 is a representative histological photograph of an intradermal area in a guinea pig injected with a HA dermal filler of the present invention (24 mg / mL HA, PEGDE crosslinked, Sample C4 - Table 25). [Figure 39] Figure 39 is a representative histological photograph of an intradermal area in a guinea pig injected with a silk-HA dermal filler of the present invention (22.8 mg / mL HA, 1.2 mg / mL silk, PEGDE crosslinked, Sample L - Table 25). [Figure 40] Figure 40 is a representative histological photograph of an intradermal area in a guinea pig injected with a silk-HA dermal filler of the present invention (23.76 mg / mL HA, 0.24 mg / mL silk, PEGDE crosslinked, Sample M - Table 25). [Figure 41] Figure 41 is a representative histological photograph of an intradermal area in a guinea pig injected with a silk-HA dermal filler of the present invention (22.8 mg / mL HA, 1.2 mg / mL silk, PEGDE crosslinked, Sample N - Table 25). [Figure 42] Figure 42 is a representative histological photograph of an intradermal area in a guinea pig injected with a silk-HA dermal filler of the present invention (22.8 mg / mL HA, 1.2 mg / mL silk, PEGDE crosslinked, Sample O - Table 25). [Figure 43] Figure 43 is a graph showing histological results for gel degradation 7 days after implantation (formulations in Table 25 - BDDE crosslinked formulations are mostly degraded; scores: 0 - normal; 1 - minimal; 2 - mild; 3 - moderate; 4 - severe). [Figure 44] FIG. 44 is a graph showing the histological results for gel migration 7 days after implantation (formulations in Table 25 - score: 0 - normal; 1 - minimal; 2 - mild; 3 - moderate; 4 - severe). [Figure 45] Figure 45 is a graph showing histology results for inflammation 7 days after implantation (formulations in Table 25 - no tissue necrosis observed, no blood clotting observed, minimal collagen deposition observed in control and some of the test formulations; score: 0 - normal; 1 - minimal; 2 - mild; 3 - moderate; 4 - severe). [Figure 46]Figure 46 is a graph showing histology results for macrophages 7 days after implantation (Table 25 formulations - score: 0 - normal; 1 - minimal; 2 - mild; 3 - moderate; 4 - severe). [Figure 47A] FIG. 47A shows the G' of hydrogels with various silk concentrations before and after crosslinking dialysis at 100 gm / ml of mixed crosslinked HA. [Figure 47B] FIG. 47B shows the G' of hydrogels with various silk concentrations before and after crosslinking dialysis at single MW crosslinked HA 25 mg / ml. [Figure 48A] FIG. 48A shows the swelling ratio of hydrogels with various silk concentrations during dialysis with mixed cross-linked HA at 100 gm / ml. [Figure 48B] FIG. 48B shows the swelling ratio of hydrogels with different silk concentrations during dialysis with single MW cross-linked HA at 25 mg / ml. [Figure 49A] Figure 49A shows the calibration curves of medium and low molecular weight silk solutions. [Figure 49B] Figure 49B shows the calibration curves of medium and low molecular weight silk solutions. [Figure 50A] FIG. 50A shows the absorption spectrum of diluted silk-HA gels with unknown silk concentrations, and the theoretical silk concentration (mg / ml) is shown for each silk-HA gel sample in Table 26. [Figure 50B] FIG. 50B shows the absorption spectrum of diluted silk-HA gels with unknown silk concentrations, and the theoretical silk concentration (mg / ml) is shown for each silk-HA gel sample in Table 26. [Figure 51] Figure 51 shows turbidity measurements of silk-free HA hydrogels (red; higher transmittance across the entire wavelength interval) and HA hydrogels with 3 mg / mL silk (blue; lower transmittance across the entire wavelength interval), with higher % transmittance indicating a less turbid, less optically opaque sample.
[0088] While the above-identified drawings illustrate embodiments of the presently disclosed invention, other embodiments are contemplated, as noted in the discussion. The present disclosure presents exemplary embodiments that are representative and not limiting. Numerous other modifications and embodiments can be devised by those skilled in the art that fall within the scope and spirit of the principles of the presently disclosed embodiments. DETAILED DESCRIPTION OF THE INVENTION
[0089] Disclosed herein is a tissue filler comprising silk protein fragments (SPF). In some embodiments, the tissue filler is prepared from a composition described herein that can include SPF and hyaluronic acid (HA). In some embodiments, the tissue filler described herein can be a dermal filler.
[0090] In some embodiments, dermal fillers are produced by the processes described herein using HA having a MW of about 5 kDa to about 5 MDa, about 100 kDa to about 4 MDa, or about 500 kDa to about 3 MDa. In some embodiments, the dermal filler is produced by the processes described herein using HA having a MW of about 50 kDa, about 100 kDa, about 150 kDa, about 200 kDa, about 250 kDa, about 300 kDa, about 350 kDa, about 400 kDa, about 450 kDa, about 500 kDa, about 550 kDa, about 600 kDa, about 650 kDa, about 700 kDa, about 750 kDa, about 800 kDa, about 850 kDa, about 900 kDa, about 950 kDa, about 1000 kDa, about 105 ... 100kDa, about 1150kDa, about 1200kDa, about 1250kDa, about 1300kDa, about 1350kDa, about 1400kDa, about 1450kDa, about 1500kDa, about 1550kDa, about 1600kD a, about 1650kDa, about 1700kDa, about 1750kDa, about 1800kDa, about 1850kDa, about 1900kDa, about 1950kDa, about 2000kDa, about 2050kDa, about 2100kDa, about 215 0kDa, about 2200kDa, about 2250kDa, about 2300kDa, about 2350kDa, about 2400kDa, about 2450kDa, about 2500kDa, about 2550kDa, about 2600kDa, about 2650kDa, About 2700kDa, about 2750kDa, about 2800kDa, about 2850kDa, about 2900kDa, about 2950kDa, about 3000kDa, about 3050kDa, about 3100kDa, about 3150kDa, about 3200 The process described herein may be carried out using HA having a MW of about 3250 kDa, about 3300 kDa, about 3350 kDa, about 3400 kDa, about 3450 kDa, about 3500 kDa, about 3550 kDa, about 3600 kDa, about 3650 kDa, about 3700 kDa, about 3750 kDa, about 3800 kDa, about 3850 kDa, about 3900 kDa, about 3950 kDa, or about 4000 kDa. Any of the above MWs of HA can be mixed with any other of the above MWs of HA in any possible proportion.In some embodiments, the dermal filler is made by blending high MW HA with low MW HA, wherein the percentage of high MW HA is about 0.01%, or about 0.1%, or about 0.2%, or about 0.3%, or about 0.4%, or about 0.5%, or about 0.6%, or about 0.7%, or about 0.8%, or about 0.9%, or about 1%, or about 2%, or about 3%, or about 4%, or about 5%, or about 6%, or about 7%, or about 8%, or about 9%, or about 10%, or about 11%, or about 12%, or about 13%, or about 14%, or about 15%, or about 16%, or about 17%, or about 18%, or about 19%, or about 20%, or about 21%, or about 22%, or about 23%, or about 24%, or about 25%, or about 26%, or about 27%, or about 28%, or about 29%, or about 30%, or about 31%, or about 32%, or about 33%, or about 34%, or about 35%, or about 36%, or about 37%, or about 38%, or about 39%, or about 40%, or about 41%, or about 42%, or about 43%, or about 44%, or about 45%, or about 46%, or about 47%, or about 48%, or about 49%, or about 50%, or about 51%, or about 52%, or about 53%, or about 54%, or about 55%, or about 56%, or about 57%, or about 58%, or about 59%, or about 60%, or about 61%, or about 62%, or about 63%, or about 64%, or about 65%, or about 66%, or about 67%, or about 68%, or about 69%, or about 70%, or about 71%, or about 72%, or about 73%, or about 74%, or about 75%, or about 76%, or about 77%, or about 78%, or about 79%, or about 80%, or about 81%, or about 82%, or about 83%, or about 84%, or about 85%, or about 86%, or about 87%, or about 88%, or about 89%, or about 90%, or about 91%, or about 92%, or about 93%, or about 94%, or about 95%, or about 96%, or about 97%, or about 98%, or about 99%, or about 99.5%, or about 99.9%.
[0091] In some embodiments, the dermal filler is produced by the processes described herein by using a silk SPF having a molecular weight of about 5 kDa to about 35 kDa. In some embodiments, the dermal filler is produced by the process described herein by using a silk SPF having a MW of about 5 kDa, or about 6 kDa, or about 7 kDa, or about 8 kDa, or about 9 kDa, or about 10 kDa, or about 11 kDa, or about 12 kDa, or about 13 kDa, or about 14 kDa, or about 15 kDa, or about 16 kDa, or about 17 kDa, or about 19 kDa, or about 19 kDa, or about 20 kDa, or about 21 kDa, or about 22 kDa, or about 23 kDa, or about 24 kDa, or about 25 kDa, or about 26 kDa, or about 27 kDa, or about 28 kDa, or about 29 kDa, or about 30 kDa.
[0092] In some embodiments, the dermal filler has a viscosity of about 80 mg / ml, or about 81 mg / ml, or about 82 mg / ml, or about 83 mg / ml, or about 84 mg / ml, or about 85 mg / ml, or about 86 mg / ml, or about 87 mg / ml, or about 88 mg / ml, or about 89 mg / ml, or about 90 mg / ml, or about 91 mg / ml, or about 92 mg / ml, or about 93 mg / ml, or about 94 mg / ml, or about 95 mg / ml, or about 96 mg / ml, or about 97 mg / ml, or about 98 mg / ml, or about 99 mg / ml, or about 100 mg / ml, or about 101 mg / ml, or about 102 mg / ml. The present invention is produced by the processes described herein by using an initial concentration of HA of about 103 mg / ml, or about 104 mg / ml, or about 105 mg / ml, or about 106 mg / ml, or about 107 mg / ml, or about 108 mg / ml, or about 109 mg / ml, or about 110 mg / ml, or about 111 mg / ml, or about 112 mg / ml, or about 113 mg / ml, or about 114 mg / ml, or about 115 mg / ml, or about 116 mg / ml, or about 117 mg / ml, or about 118 mg / ml, or about 119 mg / ml, or about 120 mg / ml, or higher.
[0093] In some embodiments, the dermal fillers described herein represent about 0.1%, or about 0.2%, or about 0.3%, or about 0.4%, or about 0.5%, or about 0.6%, or about 0.7%, or about 0.8%, or about 0.9%, or about 1%, or about 1.1%, or about 1.2%, or about 1.3%, or about 1.4%, or about 1.5%, or about 1.6%, or about 1.7%, or about 1.8%, or about 1.9%, or about 2%, or about 2.1%, or about 2.2%, or about 2.3%, or has a silk SPF concentration of about 2.4%, or about 2.5%, or about 2.6%, or about 2.7%, or about 2.8%, or about 2.9%, or about 3%, or about 3.1%, or about 3.2%, or about 3.3%, or about 3.4%, or about 3.5%, or about 3.6%, or about 3.7%, or about 3.8%, or about 3.9%, or about 4%, or about 4.1%, or about 4.2%, or about 4.3%, or about 4.4%, or about 4.5%, or about 4.6%, or about 4.7%, or about 4.8%, or about 4.9%, or about 5%.
[0094] In some embodiments, the dermal filler is produced by the processes described herein by using a PEGDE crosslinker having an Mn of about 100, about 200, about 300, about 400, about 500, about 600, about 700, about 800, about 900, about 1000, about 1100, or about 1200.
[0095] In some embodiments, the dermal filler is produced by the processes described herein by using reaction conditions that include a crosslinking step at about 35°C, about 36°C, about 37°C, about 38°C, about 39°C, about 40°C, about 41°C, about 42°C, about 43°C, about 44°C, about 45°C, about 46°C, about 47°C, about 48°C, about 49°C, about 50°C, about 51°C, about 52°C, about 53°C, about 54°C, or about 55°C. In some embodiments, the dermal filler may be applied for about 15 minutes, about 16 minutes, about 17 minutes, about 18 minutes, about 19 minutes, about 20 minutes, about 21 minutes, about 22 minutes, about 23 minutes, about 24 minutes, about 25 minutes, about 26 minutes, about 27 minutes, about 28 minutes, about 29 minutes, about 30 minutes, about 31 minutes, about 32 minutes, about 33 minutes, about 34 minutes, about 35 minutes, about 36 minutes, about 37 minutes, about 38 minutes, about 39 minutes, about 40 minutes, about 41 minutes, about 42 minutes The crosslinking step can be produced by the process described herein using reaction conditions including a crosslinking step of about 43 minutes, about 44 minutes, about 45 minutes, about 46 minutes, about 47 minutes, about 48 minutes, about 49 minutes, about 50 minutes, about 51 minutes, about 52 minutes, about 53 minutes, about 54 minutes, about 55 minutes, about 56 minutes, about 57 minutes, about 58 minutes, about 59 minutes, about 60 minutes, about 61 minutes, about 62 minutes, about 63 minutes, about 64 minutes, or about 65 minutes.
[0096] In some embodiments, the dermal filler comprises free HA, e.g., non-crosslinked HA. In some embodiments, the dermal filler comprises about 0.1%, or about 0.2%, or about 0.3%, or about 0.4%, or about 0.5%, or about 0.6%, or about 0.7%, or about 0.8%, or about 0.9%, or about 1%, or about 1.1%, or about 1.2%, or about 1.3%, or about 1.4%, or about 1.5%, or about 1.6%, or about 1.7%, or about 1.8%, or about 1.9%, or about 2%, or about 2.1%, or about 2.2%, or is about 2.3%, or about 2.4%, or about 2.5%, or about 2.6%, or about 2.7%, or about 2.8%, or about 2.9%, or about 3%, or about 3.1%, or about 3.2%, or about 3.3%, or about 3.4%, or about 3.5%, or about 3.6%, or about 3.7%, or about 3.8%, or about 3.9%, or about 4%, or about 4.1%, or about 4.2%, or about 4.3%, or about 4.4%, or about 4.5%, or about 4.6%, or about 4.7%, or about 4.8%, or is about 4.9%, or about 5%, or about 5.1%, or about 5.2%, or about 5.3%, or about 5.4%, or about 5.5%, or about 5.6%, or about 5.7%, or about 5.8%, or about 5.9%, or %, or about 6%, or about 6.1%, or about 6.2%, or about 6.3%, or about 6.4%, or about 6.5%, or about 6.6%, or about 6.7%, or about 6.8%, or about 6.9%, or about 7%, or about 7.1%, or about 7.2%, or about 7.3%, or about 7.4%, or In some embodiments, the dermal filler contains about 7.5%, or about 7.6%, or about 7.7%, or about 7.8%, or about 7.9%, or about 8%, or about 8.1%, or about 8.2%, or about 8.3%, or about 8.4%, or about 8.5%, or about 8.6%, or about 8.7%, or about 8.8%, or about 8.9%, or about 9%, or about 9.1%, or about 9.2%, or about 9.3%, or about 9.4%, or about 9.5%, or about 9.6%, or about 9.7%, or about 9.8%, or about 9.9%, or about 10%. In some embodiments, the dermal filler does not contain free HA.
[0097] In some embodiments, the dermal filler comprises HA at about 10 mg / ml, about 11 mg / ml, about 12 mg / ml, about 13 mg / ml, about 14 mg / ml, about 15 mg / ml, about 16 mg / ml, about 17 mg / ml, about 18 mg / ml, about 19 mg / ml, about 20 mg / ml, about 21 mg / ml, about 22 mg / ml, about 23 mg / ml, about 24 mg / ml, about 25 mg / ml, about 26 mg / ml, about 27 mg / ml, about 28 mg / ml, about 29 mg / ml, or about 30 mg / ml.
[0098] In some embodiments, the dermal filler is about 10.0%, about 10.1%, about 10.2%, about 10.3%, about 10.4%, about 10.5%, about 10.6%, about 10.7%, about 10.8%, about 10.9%, about 11.0%, about 11.1%, about 11.2%, about 11.3%, about 11.4%, about 11.5%, about 11.6%, about 11.7%, about 11.8%, about 11.9%, about 12.0%, about 12.1%, about 12.2%, about 12.3%, about 12.4%, about 12.5%, about 12.6%, about 12.7%, about 12.8%, about 12.9%, about 13.0%, about 13.1%, about 13.1%. 3%, approx. 12.4%, approx. 12.5%, approx. 12.6%, approx. 12.7%, approx. 12.8%, approx. 12.9%, approx. 13.0%, approx. 13.1%, approx. 13.2%, approx. 13.3%, approx. 13.4%, approx. 13.5%, approx. 13.6%, approx. 13.7%, approx. 13.8%, approx. 13.9%, approx. 14.0%, approx. 14.1%, approx. 14.2%, approx. 14.3%, approx. 14.4%, approx. 14.5%, approx. 14.6%, approx. 14.7%, approx. 14.8%, approx. 14.9% ,approx. 15.0%,approx. 15.1%,approx. 15.2%,approx. 15.3%,approx. 15.4%,approx. 15.5%,approx. 15.6%,approx. 15.7%,approx. 15.8%,approx. 15.9%,approx. 16.0%,approx. 16.1%,approx. 16.2%,approx. 16.3%,approx. 16.4%,approx. 16.5%,approx. 16.6%,approx. 16.7%,approx. 16.8%,approx. 16.9%,approx. 17.0%,approx. 17.1%,approx. 17.2%,approx. 17.3%,approx. 17.4%,approx. 17.5%,approx. has an MoD of 17.6%, about 17.7%, about 17.8%, about 17.9%, about 18.0%, about 18.1%, about 18.2%, about 18.3%, about 18.4%, about 18.5%, about 18.6%, about 18.7%, about 18.8%, about 18.9%, about 19.0%, about 19.1%, about 19.2%, about 19.3%, about 19.4%, about 19.5%, about 19.6%, about 19.7%, about 19.8%, about 19.9%, or about 20.0%.
[0099] In some embodiments, the dermal filler has an ejection force of about 5 N, about 6 N, about 7 N, about 8 N, about 9 N, about 10 N, about 11 N, about 12 N, about 13 N, about 14 N, about 15 N, about 16 N, about 17 N, about 18 N, about 19 N, about 20 N, about 21 N, about 22 N, about 23 N, about 24 N, or about 25 N. In some embodiments, the ejection force is for injection through a 30 G needle.
[0100] The tissue fillers provided herein include compositions further comprising one or more components such as SPF, e.g., cross-linked SPF and / or non-cross-linked SPF, and hyaluronic acid, e.g., cross-linked HA and / or non-cross-linked HA. As used herein, cross-linked SPF refers to SPF cross-linked with identical or non-identical SPF. Cross-linked SPF can also be referred to as homo-cross-linked SPF. As used herein, cross-linked HA refers to HA cross-linked with identical or non-identical HA. Cross-linked HA can also be referred to as homo-cross-linked HA. The tissue fillers provided herein can also include SPF cross-linked to HA and / or HA cross-linked to SPF. SPF cross-linked to HA and / or HA cross-linked to SPF can also be referred to as cross-linked SPF-HA or hetero-cross-linked SPF-HA.
[0101] In some embodiments, the compositions of the present invention are single-phase. In some embodiments, the compositions of the present invention are two-phase or multi-phase. In some embodiments, the compositions of the present invention include a non-crosslinked polymer phase, such as non-crosslinked SPF and / or non-crosslinked HA. In some embodiments, the compositions of the present invention include a crosslinked phase, such as crosslinked SPF and / or crosslinked HA. In some embodiments, the compositions of the present invention include a liquid phase, such as water and / or an aqueous solution. In some embodiments, the aqueous solution can include SPF. In some embodiments, the aqueous phase can include HA. In some embodiments, the liquid phase can include a non-crosslinked polymer, such as non-crosslinked HA and / or non-crosslinked SPF.
[0102] In some embodiments, the compositions of the present invention include a carrier phase. Thus, the disclosed compositions can be single-phase or multi-phase compositions. As used herein, the term "carrier phase" is synonymous with "carrier" and refers to a material used to increase the fluidity of the hydrogel. The carrier is advantageously a physiologically acceptable carrier and can include one or more conventional excipients useful in pharmaceutical compositions. As used herein, the term "physiologically acceptable carrier" refers to a carrier that is compatible with or characterized by the normal function of an organism. Thus, when administered to a mammal, administration of a composition comprising a hydrogel and a carrier does not substantially cause long-term or permanent adverse effects. The present tissue fillers include carriers whose majority of their volume is water or saline. However, other useful carriers include any physiologically acceptable material that improves the extrudability or penetration (through a needle) of the hydrogel into the intended host environment. Potential carriers include, but are not limited to, physiological buffer solutions, serum, other protein solutions, and gels composed of polymers containing proteins, glycoproteins, proteoglycans, or polysaccharides. Any of the potential carriers may be naturally derived, wholly synthetic, or a combination thereof.
[0103] In one embodiment, the compositions provided herein comprise one or more of denatured SPF, cross-linked SPF, non-cross-linked SPF, denatured HA, cross-linked HA, non-cross-linked HA, homo-cross-linked SPF, homo-cross-linked HA, and hetero-cross-linked SPF-HA.
[0104] In some embodiments, the compositions provided herein comprise cross-linked SPF and uncross-linked SPF. In some embodiments, the compositions provided herein comprise cross-linked SPF and uncross-linked HA. In some embodiments, the compositions provided herein comprise cross-linked SPF and cross-linked HA. In some embodiments, the compositions provided herein comprise cross-linked SPF and cross-linked SPF-HA.
[0105] In some embodiments, the compositions provided herein comprise uncrosslinked SPF and uncrosslinked HA. In some embodiments, the compositions provided herein comprise uncrosslinked SPF and crosslinked HA. In some embodiments, the compositions provided herein comprise uncrosslinked SPF and crosslinked SPF-HA.
[0106] In some embodiments, the compositions provided herein comprise cross-linked SPF, uncross-linked SPF, and uncross-linked HA. In some embodiments, the compositions provided herein comprise cross-linked SPF, uncross-linked SPF, and cross-linked HA. In some embodiments, the compositions provided herein comprise cross-linked SPF, uncross-linked SPF, and cross-linked SPF-HA.
[0107] In some embodiments, the compositions provided herein comprise cross-linked SPF, cross-linked HA, and non-cross-linked HA. In some embodiments, the compositions provided herein comprise cross-linked SPF, cross-linked HA, and cross-linked SPF-HA. In some embodiments, the compositions provided herein comprise cross-linked SPF, non-cross-linked HA, and cross-linked SPF-HA.
[0108] In some embodiments, the compositions provided herein comprise uncrosslinked SPF, crosslinked HA, and uncrosslinked HA. In some embodiments, the compositions provided herein comprise uncrosslinked SPF, crosslinked HA, and crosslinked SPF-HA. In some embodiments, the compositions provided herein comprise uncrosslinked SPF, uncrosslinked HA, and crosslinked SPF-HA.
[0109] In some embodiments, the compositions provided herein comprise cross-linked SPF, uncross-linked SPF, cross-linked HA, and uncross-linked HA. In some embodiments, the compositions provided herein comprise cross-linked SPF, uncross-linked SPF, cross-linked HA, and cross-linked SPF-HA. In some embodiments, the compositions provided herein comprise cross-linked SPF, uncross-linked SPF, uncross-linked HA, and cross-linked SPF-HA.
[0110] In some embodiments, the compositions provided herein comprise cross-linked SPF, cross-linked HA, non-cross-linked HA, and cross-linked SPF-HA. In some embodiments, the compositions provided herein comprise non-cross-linked SPF, cross-linked HA, non-cross-linked HA, and cross-linked SPF-HA.
[0111] In some embodiments, the compositions provided herein comprise cross-linked SPF, uncross-linked SPF, cross-linked HA, uncross-linked HA, and cross-linked SPF-HA.
[0112] In some embodiments, the compositions provided herein comprise cross-linked SPF. In some embodiments, the compositions provided herein comprise SPF and hyaluronic acid (HA). In one aspect, the SPF / HA-based compositions described herein comprise an HA cross-linking moiety. In some embodiments, the composition comprises an SPF-HA cross-linking moiety. In some embodiments, the composition comprises non-cross-linked HA. In some embodiments, the composition can comprise non-cross-linked SPF. In some embodiments, the composition can comprise at least one additional agent. In some embodiments, the composition comprises cross-linked SPF-SPF, SPF-HA, and / or HA-HA, resulting in compositions with varying degrees of bioabsorbability and / or bioresorbability.
[0113] In some embodiments, the HA is cross-linked into a matrix. In some embodiments, the HA matrix encapsulates or semi-encapsulates one or more SPFs. In some embodiments, the HA is cross-linked to one or more SPFs.
[0114] In some embodiments, the tissue filler, or portions thereof, are biocompatible, biodegradable, bioabsorbable, bioresorbable, or a combination thereof. In some embodiments, the tissue fillers provided herein include a fluid component, e.g., a single fluid or solution substantially comprising one or more fluids. In some embodiments, the tissue filler comprises water or an aqueous solution. In some embodiments, the tissue filler is subcutaneously injectable, implantable, or deliverable by any means known in the art, such as after surgical removal of tissue. In some embodiments, the composition is a dermal filler. In some embodiments, the composition is sterile.
[0115] In some embodiments, the tissue fillers described herein can include about 1% (w / w) SPF and about 0.3% (w / w) lidocaine.
[0116] Provided herein are methods of making compositions comprising silk protein fragments (SPF) and hyaluronic acid (HA), methods of delivering compositions comprising SPF and HA, and methods of treatment using compositions comprising SPF and HA.
[0117] definition As used herein, the term "fibroin" includes silkworm fibroin, insect or spider silk protein, or recombinant silk fibroin. In embodiments, fibroin is derived from Bombyx mori ( Bombyx mori ) is obtained from
[0118] As used herein, the terms "substantially free of sericin" or "substantially devoid of sericin" refer to silk fibers from which most of the sericin protein has been removed and / or SPF made from silk fibers from which most of the sericin protein has been removed. In embodiments, silk fibroin and SPF substantially devoid of sericin refer to silk fibroin and SPF having about 0.01% (w / w) to about 10.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refer to silk fibroin and SPF having about 0.01% (w / w) to about 9.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refer to silk fibroin and SPF having about 0.01% (w / w) to about 8.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 0.01% (w / w) to about 7.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 0.01% (w / w) to about 6.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 0.01% (w / w) to about 5.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 0% (w / w) to about 4.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 0.05% (w / w) to about 4.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 0.1% (w / w) to about 4.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 0.5% (w / w) to about 4.0% (w / w) sericin.In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 1.0% (w / w) to about 4.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 1.5% (w / w) to about 4.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 2.0% (w / w) to about 4.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refers to silk fibroin and SPF having about 2.5% (w / w) to about 4.0% (w / w) sericin. In embodiments, silk fibroin and SPF substantially devoid of sericin refer to silk fibroin and SPF having a sericin content of about 0.01% (w / w) to about 0.1% (w / w). In embodiments, silk fibroin and SPF substantially devoid of sericin refer to silk fibroin and SPF having a sericin content of less than about 0.1% (w / w). In embodiments, silk fibroin and SPF substantially devoid of sericin refer to silk fibroin and SPF having a sericin content of less than about 0.05% (w / w). In embodiments, when a silk source is added to a boiling (100°C) aqueous sodium carbonate solution for a treatment time of about 30 minutes to about 60 minutes, a degumming loss of about 26% to about 31% by weight is obtained.
[0119] As used herein, the term "substantially homogeneous" can refer to pure silk fibroin-based protein fragments that are normally distributed around an identified molecular weight. As used herein, the term "substantially homogeneous" can refer to the uniform distribution of an additive, such as lidocaine, throughout the composition of the present disclosure.
[0120] As used herein, the term "substantially free of inorganic residue" means that the composition exhibits 0.1% (w / w) or less residue. In embodiments, substantially free of inorganic residue means that the composition exhibits 0.05% (w / w) or less residue. In embodiments, substantially free of inorganic residue means that the composition exhibits 0.01% (w / w) or less residue. In embodiments, the amount of inorganic residue is 0 ppm ("not detectable" or "ND") to 1000 ppm. In embodiments, the amount of inorganic residue is ND to about 500 ppm. In embodiments, the amount of inorganic residue is ND to about 400 ppm. In embodiments, the amount of inorganic residue is ND to about 300 ppm. In embodiments, the amount of inorganic residue is ND to about 200 ppm. In embodiments, the amount of inorganic residue is ND to about 100 ppm. In embodiments, the amount of inorganic residue is 10 ppm to 1000 ppm.
[0121] As used herein, the term "substantially free of organic residue" means that the composition exhibits 0.1% (w / w) or less of a residue. In embodiments, substantially free of organic residue means that the composition exhibits 0.05% (w / w) or less of a residue. In embodiments, substantially free of organic residue means that the composition exhibits 0.01% (w / w) or less of a residue. In embodiments, the amount of organic residue is 0 ppm ("not detectable" or "ND") to 1000 ppm. In embodiments, the amount of organic residue is ND to about 500 ppm. In embodiments, the amount of organic residue is ND to about 400 ppm. In embodiments, the amount of organic residue is ND to about 300 ppm. In embodiments, the amount of organic residue is ND to about 200 ppm. In embodiments, the amount of organic residue is ND to about 100 ppm. In embodiments, the amount of organic residue is 10 ppm to 1000 ppm.
[0122] As used herein, the term "non-crosslinked" refers to the lack of intermolecular bonds connecting individual matrix polymer molecules, macromolecules, and / or monomer chains. Thus, a non-crosslinked matrix polymer is not attached to other matrix polymers by intermolecular bonds.
[0123] The tissue fillers, compositions, or portions thereof of the present disclosure exhibit or are "biocompatible," meaning that the compositions are compatible with living tissues or living systems by being substantially non-toxic, non-toxic, free of physiological responses, and free of immune rejection. The term "biocompatible" encompasses the terms "bioabsorbable," "bioresorbable," and "biodegradable," as defined herein.
[0124] The tissue fillers, compositions, or portions thereof of the present disclosure can be "bioabsorbable," "bioresorbable," and / or "biodegradable." As used herein, the term "bioresorbable" refers to a material or substance that is eliminated upon implantation, regardless of the mechanism by which elimination may occur (such as dissolution, degradation, absorption, and excretion). As used herein, the term "bioresorbable" means capable of being absorbed by the body. As used herein, the term "biodegradable" refers to a material that can be broken down into by-products under physiological conditions. Such physiological conditions include, for example, hydrolysis (breakdown via hydrolysis), enzyme catalysis (enzymatic degradation), mechanical interaction, and the like. As used herein, the term "biodegradable" also encompasses the term "bioresorbable," which describes a material or substance that breaks down under physiological conditions and decomposes into products that are bioresorbed by the host organism, i.e., metabolic products of the host organism's biochemical systems. As used herein, the terms "bioresorbable" and "bioresorbable" are understood by those skilled in the art to encompass processes such as cell-mediated degradation, enzymatic degradation, and / or hydrolysis of the bioabsorbable polymer, and / or removal of the bioresorbable polymer from living tissue. In some embodiments, the SPF-HA compositions and materials described herein can be biocompatible, bioresorbable, bioabsorbable, and / or biodegradable.
[0125] When the tissue fillers described herein are biodegradable or bioresorbable, they may have a shelf life of at least about 1 day, or at least about 2 days, or at least about 3 days, or at least about 4 days, or at least about 5 days, or at least about 10 days, or at least about 15 days, or at least about 20 days, or at least about 25 days, or at least about 30 days, or at least about 35 days, or at least about 40 days, or at least about 45 days, or at least about 50 days, or at least about 60 days, or at least about 70 days, or at least about 80 days, or at least about 90 days, or at least about 100 days, or at least 110 days, or at least about 120 days, or at least about 130 days, or at least about 140 days, or at least about 150 days, or at least about 160 days, or at least about 170 days, or at least about 180 days, or at least about 190 days, or at least They may be resistant to biodegradation or bioresorption for about 200 days, or at least about 250 days, or at least about 300 days, or at least about 1 year, or at least about 2 years, or they may be resistant to biodegradation or bioresorption for less than about 5 days, or up to about 10 days, or up to about 15 days, or up to about 20 days, or up to about 25 days, or up to about 30 days, or up to about 35 days, or up to about 40 days, or up to about 45 days, or up to about 50 days, or up to about 60 days, or up to about 70 days. or up to about 80 days, or up to about 90 days, or up to about 100 days, or up to about 110 days, or up to about 120 days, or up to about 130 days, or up to about 140 days, or up to about 150 days, or up to about 160 days, or up to about 170 days, or up to about 180 days, or up to about 190 days, or up to about 200 days, or up to about 250 days, or up to about 300 days, or up to about 1 year, or up to about 2 years.
[0126] When the tissue fillers described herein are bioabsorbable, they may have a resorbable life of at least about 1 day, or at least about 2 days, or at least about 3 days, or at least about 4 days, or at least about 5 days, or at least about 10 days, or at least about 15 days, or at least about 20 days, or at least about 25 days, or at least about 30 days, or at least about 35 days, or at least about 40 days, or at least about 45 days, or at least about 50 days, or at least about 60 days, or at least about 70 days, or at least about 80 days, or at least about 90 days, or at least about 100 days, or at least 110 days, or at least about 120 days, or at least about 130 days, or at least about 140 days, or at least about 140 days, or at least about 150 days, or at least about 160 days, or at least about 170 days, or at least about 180 days, or at least about 190 days, or at least about They may be resistant to bioabsorption for 200 days, or at least about 250 days, or at least about 300 days, or at least about 1 year, or at least about 2 years, or they may be resistant to bioabsorption for less than about 5 days, or up to about 10 days, or up to about 15 days, or up to about 20 days, or up to about 25 days, or up to about 30 days, or up to about 35 days, or up to about 40 days, or up to about 45 days, or up to about 50 days, or up to about 60 days, or up to about 70 days, or up to about 80 days. It may be resistant to bioabsorption for at most about 80 days, or up to about 90 days, or up to about 100 days, or up to about 110 days, or up to about 120 days, or up to about 130 days, or up to about 140 days, or up to about 150 days, or up to about 160 days, or up to about 170 days, or up to about 180 days, or up to about 190 days, or up to about 200 days, or up to about 250 days, or up to about 300 days, or up to about 1 year, or up to about 2 years.
[0127] As described herein, the degree of biodegradation, bioabsorption, and bioresorbability can be modified and / or controlled, for example, by adding one or more agents to the compositions described herein that retard biodegradation, bioabsorption, and / or bioresorption. The degree of biodegradation, bioabsorption, and bioresorbability can also be modified and / or controlled by increasing or decreasing the degree of polymeric crosslinking present in the polymeric materials described herein. For example, the rate of biodegradation, bioabsorption, and / or bioresorption of the compositions described herein can be increased by decreasing the amount of crosslinking in the polymeric materials described herein. Alternatively, the rate of biodegradation, bioabsorption, and / or bioresorption of the tissue fillers and compositions described herein can be decreased by increasing the amount of crosslinking in the polymeric materials described herein.
[0128] The tissue fillers and compositions of the present disclosure are "hypoallergenic," meaning that they are relatively unlikely to cause an allergic reaction. Such hypoallergenicity can be demonstrated by having a participant topically apply the compositions of the present disclosure to their skin for an extended period of time. In embodiments, the extended period is about 3 days. In embodiments, the extended period is about 7 days. In embodiments, the extended period is about 14 days. In embodiments, the extended period is about 21 days. In embodiments, the extended period is about 30 days. In embodiments, the extended period is selected from the group consisting of about 1 month, about 2 months, about 3 months, about 4 months, about 5 months, about 6 months, about 7 months, about 8 months, about 9 months, about 10 months, about 11 months, about 12 months, and indefinitely.
[0129] As used herein, "low molecular weight" silk refers to silk protein fragments having a molecular weight of about 5 kDa to about 20 kDa. In some embodiments, the target low molecular weight for a particular silk protein fragment can be about 11 kDa.
[0130] As used herein, "medium molecular weight" silk refers to silk protein fragments having a molecular weight of about 20 kDa to about 55 kDa. In some embodiments, the target low molecular weight for a particular silk protein fragment can be about 40 kDa.
[0131] As used herein, "high molecular weight" silk refers to silk protein fragments having a molecular weight of about 55 kDa to about 150 kDa. In some embodiments, the target low molecular weight for a particular silk protein fragment can be about 100 kDa to about 145 kDa.
[0132] In some embodiments, the molecular weights described herein, e.g., low molecular weight SPFs, medium molecular weight SPFs, and high molecular weight SPFs, can each be converted to the approximate number of amino acids contained in a natural or recombinant protein (e.g., a natural or recombinant silk protein), as understood by those skilled in the art. For example, the average weight of an amino acid may be approximately 110 daltons, i.e., 110 g / mol. Thus, in some embodiments, dividing the molecular weight of a linear protein by 110 daltons can be used to approximate the number of amino acid residues contained therein.
[0133] As used herein, the term "polydispersity" refers to a measure of molecular weight distribution in a given polymer sample. Polydispersity can be calculated by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn). As used herein, the term "weight average molecular weight" (Mw) generally refers to a molecular weight measurement that depends on the contributions of polymer molecules according to their size. Weight average molecular weight can be defined by the following formula:
number
number
[0134] As used herein, the term "tissue filler" broadly refers to materials that can be placed in or around soft tissue to add volume, support, or otherwise treat soft tissue defects. The term "tissue filler" also encompasses dermal fillers. However, the term "dermal filler" should not be construed as imposing any limitations on the location and type of filler delivery. Nevertheless, the dermal fillers described herein can generally encompass the use and delivery of dermal fillers at multiple levels below the dermis. As used herein, the term "soft tissue" can refer to those that connect, support, or surround other structures and organs of the body. For example, soft tissues described herein can include, but are not limited to, skin, dermal tissue, subdermal tissues, cutaneous tissue, subcutaneous tissue, intradural tissue, muscle, tendon, ligament, fibrous tissue, fat, blood vessels and arteries, nerves, and synovial (intradermal) tissue.
[0135] As used herein, the term "epoxy-derived crosslinker" refers to a molecular bridge between two moieties on the same or different polymer chains, obtained by using, for example, a crosslinking precursor containing an epoxide group, such as 1,4-butanediol diglycidyl ether (BDDE), polyethylene glycol diglycidyl ether (PEGDE, or PEGDGE), or a silk fibroin or silk fibroin fragment polyepoxy linker. Without wishing to be bound by any particular theory, the epoxide ring opens by reacting with a reactive center in the polymer chain, contained in a side chain of the polymer, to form a new bond with a secondary alcohol (Scheme 1). Reactive groups can include, but are not limited to, nucleophilic groups such as carboxyl, amino, or hydroxyl groups. [ka]
[0136] As used herein, "self-crosslinking" means either a) crosslinking between two strands of polymer of similar chemical nature, e.g., crosslinking between two strands of hyaluronic acid or crosslinking between two strands of SPF, or b) crosslinking between crosslinking groups on the same polymer chain to form cyclic esters (lactones), cyclic amides, cyclic constructs containing crosslinking moieties, etc., e.g., crosslinking between two groups on the same chain of hyaluronic acid or crosslinking between two groups on the same chain of SPF.
[0137] As used herein, "zero-length crosslinks" and / or "crosslinks involving bonds" and / or "crosslinks using an activating agent" refer to crosslinks between two groups, either on separate polymer chains or on the same polymer chain, where the groups react directly with each other and no additional crosslinking moiety is inserted between them. A crosslink between a carboxylic acid group and an amine or alcohol, where one of the groups is activated with an activating agent, e.g., a carbodiimide, is an example of a zero-length crosslink.
[0138] As used herein, "Tyndall phenomenon" and / or "Tindaling" are adverse events that occur in some patients who have received tissue fillers. The Tyndall phenomenon is characterized by the appearance of a blue discoloration at the skin site where the tissue filler is injected, which represents the visible dermal filler composition visible through the translucent epidermis. The Tyndall phenomenon is observed when light-scattering particulate matter is dispersed in a light-transmitting medium when the particle cross-section is within a certain range, usually somewhat shorter or closer than the wavelength of visible light. Under the Tyndall phenomenon, longer wavelength light (e.g., red) is transmitted to a greater extent through the medium, while shorter wavelength light (e.g., blue) is reflected to a greater extent through scattering, giving the overall impression that the medium is colored blue.
[0139] Silk protein fragments In some embodiments, silk protein-based compositions and silk protein fragments, or methods for their production, are described in U.S. Patent Application Publication Nos. 2015 / 00933340, 2015 / 0094269, 2016 / 0193130, 2016 / 0022560, 2016 / 0022561, and 2016 / 0022562, each of which is incorporated by reference in its entirety. , 2016 / 0022563, 2016 / 0222579, 2016 / 0281294, and U.S. Pat. Nos. 9,187,538, 9,522,107, 9,517,191, 9,522,108, 9,511,012, and 9,545,369.
[0140] As used herein, silk protein fragments (SPF) generally refers to a mixture, composition, or population of silk-derived peptides and / or proteins. In some embodiments, SPF is produced as a substantially pure and highly scalable SPF mixture solution that can be used across multiple industries for a variety of applications. The solution is generated from unprocessed, pure, intact silk protein material and processed to remove sericin and achieve a desired weight-average molecular weight (Mw) and polydispersity of the fragment mixture. Selected process parameters can be modified to achieve different final silk protein fragment properties depending on the intended use. The resulting final fragment solution is pure silk protein fragments and water with undetectable levels of process contaminants and PPM levels acceptable for pharmaceutical, medical, and consumer cosmetic markets. The concentration, size, and polydispersity of the silk protein fragments in the solution can be further modified depending on the desired application and performance requirements. In embodiments, the pure silk fibroin-based protein fragments in solution are substantially devoid of sericin and have an average weight average molecular weight of about 1 kDa to about 250 kDa and a polydispersity of about 1.5 to about 3.0. In embodiments, the pure silk fibroin-based protein fragments in solution are substantially devoid of sericin and have an average weight average molecular weight of about 5 kDa to about 150 kDa and a polydispersity of about 1.5 to about 3.0. In embodiments, the pure silk fibroin-based protein fragments in solution are substantially devoid of sericin and have an average weight average molecular weight of about 6 kDa to about 17 kDa and a polydispersity of about 1.5 to about 3.0. In embodiments, the pure silk fibroin-based protein fragments in solution are substantially devoid of sericin and have an average weight average molecular weight of about 17 kDa to about 39 kDa and a polydispersity of about 1.5 to about 3.0. In embodiments, the pure silk fibroin-based protein fragments in solution are substantially devoid of sericin and have an average weight average molecular weight of about 39 kDa to about 80 kDa and a polydispersity of about 1.5 to about 3.0. In embodiments, the pure silk fibroin-based protein fragments in solution are substantially devoid of sericin and have an average weight average molecular weight of about 80 kDa to about 150 kDa and a polydispersity of about 1.5 to about 3.0.
[0141] In embodiments, the silk protein fragments described herein can be prepared in solution or as a solid, which is suspended in a physiological solution (e.g., water, saline, etc.) or an HA gel, as described herein. In some embodiments, the silk protein fragments described herein can be prepared in liposomes or microspheres prior to loading them into an HA gel.
[0142] In embodiments, the silk solutions of the present disclosure can be used to produce the tissue filler compositions described herein. In embodiments, the solutions can be used to produce gels that can be homogenized with HA and additional agents to prepare the tissue fillers described herein. Depending on the silk solution and method utilized for casting the film or gel, different properties can be achieved.
[0143] In some embodiments, the SPF content (wt %) in the tissue fillers described herein is at least 0.01%, or at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0.8%, or at least 0.9%, or at least 1%, or at least 2%, or at least 3%, or at least 4%, or at least 5%, or at least 6%, or at least 7%, or at least 8%, or at least 9%, or at least 10%, or at least 11%, or at least 12%, or at least 13%, or at least 14%, or at least 15%, or at least 16%, or at least 17%, or at least 18%, or at least 19%, or at least 20%, or at least 21%, or at least 22%, or at least 23%, or at least 24%, or at least 25%, or at least 26%, or at least 27%, or at least 28%, or at least 29%, or at least 30%, or at least 31%, or less at least 32%, or at least 33%, or at least 34%, or at least 35%, or at least 36%, or at least 37%, or at least 38%, or at least 39%, or at least 40%, or at least 41%, or at least 42%, or at least 43%, or at least 44%, or at least 45%, or at least 46%, or at least 47%, or at least 48%, or at least 49%, or at least 50%, or at least 51%, or at least 52%, or at least 53%, or at least 54%, or at least 55%, or at least 56%, or at least 57%, or at least 58%, or at least 59%, or at least 60%, or at least 61%, or at least 62%, or at least 63%, or at least 64%, or at least 65%, or at least 66%, or at least 67%, or at least 68%, or at least 69%, or at least 70%, or at least 71%, or at least 72%, or at least 73%, or at least 74%, or at least 75%, or at least 76%, or at least 77%,Or at least 78%, or at least 79%, or at least 80%, or at least 81%, or at least 82%, or at least 83%, or at least 84%, or at least 85%, or at least 86%, or at least 87%, or at least 88%, or at least 89%, or at least 90%, or at least 91%, or at least 92%, or at least 93%, or at least 94%, or at least 95%, or at least 96%, or at least 97%, or at least 98%, or at least 99%, or at least 99.5%, or at least 99.9%.
[0144] In some embodiments, the SPF content (wt %) in the tissue fillers described herein is at most 0.01%, or at most 0.1%, or at most 0.2%, or at most 0.3%, or at most 0.4%, or at most 0.5%, or at most 0.6%, or at most 0.7%, or at most 0.8%, or at most 0.9%, or at most 1%, or at most 2%, or at most 3%, or at most 4%, or at most 5%, or at most 6%, or at most 7%, or at most 8%, or at most 9%, or at most 10%, or at most 11%, or at most 12%, or at most 13%, or at most 14%, or at most 15%, or at most 16%, or at most 17%, or at most 18%, or at most 19%, or at most 20%, or at most 21%, or at most 22%, or at most 23%, or at most 24%, or at most 25%, or at most 26%, or at most 27%, or at most 28%, or at most 29%, or at most 30%, or at most 31%, or at most 32%, or at most 33%, or at most 34%, or at most 35%, or at most 36%, or at most 37%, or at most 38%, or at most 39%, or at most 40%, or at most 41%, or at most 42%, or at most 43%, or at most 44%, or at most 45%, or at most 46%, or at most 47%, or at most 48%, or at most 49%, or at most 50%, or at most 51%, or at most 52%, or at most 53%, or at most 54%, or at most 55%, or at most 56%, or at most 57%, or at most 58%, or at most 59%, or at most 60 %, or up to 15%, or up to 16%, or up to 17%, or up to 18%, or up to 19%, or up to 20%, or up to 21%, or up to 22%, or up to 23%, or up to 24%, or up to 25%, or up to 26%, or up to 27%, or up to 28%, or up to 29%, or up to 30%, or up to 31%, or up to 32%, or up to 33%, or up to 34%, or up to 35%, or up to 36%, or up to 37%, or up to 38%, or up to 39%, or up to 40%, or up to 41%, or up to 42%, or up to 43%, or is up to 44%, or up to 45%, or up to 46%, or up to 47%, or up to 48%, or up to 49%, or up to 50%, or up to 51%, or up to 52%, or up to 53%, or up to 54%, or up to 55%, or up to 56%, or up to 57%, or up to 58%, or up to 59%, or up to 60%, or up to 61%, or up to 62%, or up to 63%, or up to 64%, or up to 65%, or up to 66%, or up to 67%, or up to 68%, or up to 69%, or up to 70%, or up to 71%, or up to 72%, or up to 73%, or up to 74%, or up to 75%, or up to 76%, or up to 77%, or up to 78%, or up to 79%, or up to 80%, or up to 81%, or up to 82%, or up to 83%, or up to 84%, or up to 85%, or up to 86%, or up to 87%, or up to 88%, or up to 89%, or up to 90%, or up to 91%, or up to 92%, or up to 93%, or up to 94%, or up to 95%, or up to 96%, or up to 97%, or up to 98%, or up to 99%, or up to 99.5%, or up to 99.9%.
[0145] In some embodiments, the SPF content (wt %) in the tissue fillers described herein is about 0.01%, or about 0.1%, or about 0.2%, or about 0.3%, or about 0.4%, or about 0.5%, or about 0.6%, or about 0.7%, or about 0.8%, or about 0.9%, or about 1%, or about 2%, or about 3%, or about 4%, or about 5%, or about 6%, or about 7%, or about 8%, or about 9%, or about 10%, or about 11%, or about 12%, or about 13%, or about 14%, or about 15%, or about 16%, or about 17%, or about 18%, or about 19%, or about 20%, or about 21%, or about 22%, or about 23%, or about 24%, or about 25%, or about 26%, or about 27%, or about 28%, or about 29%, or about 30%, or about 31%, or about 32%, or about 33%, or about 34%, or about 35%, or about 36%, or about 37%, or about 38%, or about 39%, or about 40%, or about 41%, or about 42%, or about 43% , or about 44%, or about 45%, or about 46%, or about 47%, or about 48%, or about 49%, or about 50%, or about 51%, or about 52%, or about 53%, or about 54%, or about 55%, or about 56%, or about 57%, or about 58%, or about 59%, or about 60%, or about 61%, or about 62%, or about 63%, or about 64%, or about 65%, or about 66%, or about 67%, or about 68%, or about 69%, or about 70%, or about 71%, or about 72%, or about 73%, or about 74%, or about 75%, or about 76%, or about 77%, or about 78%, or about 79%, or about 80%, or about 81%, or about 82%, or about 83%, or about 84%, or about 85%, or about 86%, or about 87%, or about 88%, or about 89%, or about 90%, or about 91%, or about 92%, or about 93%, or about 94%, or about 95%, or about 96%, or about 97%, or about 98%, or about 99%, or about 99.5%, or about 99.9%.
[0146] In some embodiments, the SPF content (wt %) in the tissue fillers described herein is from about 0.01% to about 100%, or from about 0.01% to about 99.9%, or from about 0.01% to about 75%, or from about 0.1% to about 95%, or from about 1% to about 95%, or from about 10% to about 95%, or from about 0.1% to about 1%, or from about 0.1% to about 2%, or from about 0.1% to about 3%, or from about 0.1% to about 4%, or from about 0.1% to about 5%, or from about 0.1% to about 6%, or from about 0.1% to about 7%, or from about 0.1% to about 8%, or 0.1% to about 9%, or about 0.1% to about 10%, or about 0.1% to about 11%, or about 0.1% to about 12%, or about 0.1% to about 13%, or about 0.1% to about 14%, or about 0.1% to about 15%, or about 0.1% to about 16%, or about 0.1% to about 17%, or about 0.1% to about 18%, or about 0.1% to about 19%, or about 0.1% to about 20%, or about 0.1% to about 21%, or about 0.1% to about 22%, or about 0.1% to about 23%, or about 0.1% to about 24%, or about 0.1% to about 25%, or about 1% to about 2%, or about 1% to about 3%, or about 1% to about 4%, or about 1% to about 5%, or about 1% to about 6%, or about 1% to about 7%, or about 1% to about 8%, or about 1% to about 9%, or about 1% to about 10%, or about 1% to about 11%, or about 1% to about 12%, or about 1% to about 13%, or about 1% to about 14%, or about 1% to about 15%, or about 1% to about 16%, or about 1% to about 17%, or about 1% to about 18%, or about 1% to about 19%, or about 1% to about 20%, or about 1% to about 21%, or about 1% to about 22%, or about 1% to It is about 23%, or about 1% to about 24%, or about 1% to about 25%, or about 10% to about 20%, or about 10% to about 25%, or about 10% to about 30%, or about 10% to about 35%, or about 10% to about 40%, or about 10% to about 45%, or about 10% to about 50%, or about 10% to about 55%, or about 10% to about 60%, or about 10% to about 65%, or about 10% to about 70%, or about 10% to about 75%, or about 10% to about 80%, or about 10% to about 85%, or about 10% to about 90%, or about 10% to 100%.
[0147] The SPFs described herein can have a variety of mechanical and physical properties depending on the crystallinity of the peptides and / or proteins in the SPF. In embodiments, the SPF compositions of the present disclosure are not soluble due to the crystallinity of the proteins. In embodiments, the SPF compositions of the present disclosure are soluble in aqueous solutions. In embodiments, the SPF of the compositions of the present disclosure comprises approximately two-thirds crystalline and approximately one-third amorphous regions. In embodiments, the SPF of the compositions of the present disclosure comprises approximately half crystalline and approximately half amorphous regions. In embodiments, the SPF of the compositions of the present disclosure comprises 99% crystalline and 1% amorphous regions. In embodiments, the SPF of the compositions of the present disclosure comprises 95% crystalline and 5% amorphous regions. In embodiments, the SPF of the compositions of the present disclosure comprises 90% crystalline and 10% amorphous regions. In embodiments, the SPF of the disclosed compositions comprises 85% crystalline fraction and 15% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 80% crystalline fraction and 20% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 75% crystalline fraction and 25% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 70% crystalline fraction and 30% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 65% crystalline fraction and 35% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 60% crystalline fraction and 40% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 50% crystalline fraction and 50% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 40% crystalline fraction and 60% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 35% crystalline fraction and 65% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 30% crystalline fraction and 70% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 25% crystalline fraction and 75% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 20% crystalline fraction and 80% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 15% crystalline fraction and 85% amorphous region.In embodiments, the SPF of the disclosed compositions comprises 10% crystalline fraction and 90% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 5% crystalline fraction and 95% amorphous region. In embodiments, the SPF of the disclosed compositions comprises 1% crystalline fraction and 99% amorphous region.
[0148] In some embodiments, the physical and mechanical properties of an SPF vary depending on the extent of α-helix and / or random coil regions present in the SPF composition. In some embodiments, the SPF hydrogels disclosed herein have a protein structure that is substantially free of α-helix and random coil regions. In aspects of these embodiments, the hydrogel has a protein structure that includes, for example, about 5% α-helix and random coil regions, about 10% α-helix and random coil regions, about 15% α-helix and random coil regions, about 20% α-helix and random coil regions, about 25% α-helix and random coil regions, about 30% α-helix and random coil regions, about 35% α-helix and random coil regions, about 40% α-helix and random coil regions, about 45% α-helix and random coil regions, or about 50% α-helix and random coil regions. In other aspects of these embodiments, the hydrogel has a protein structure that includes, for example, up to 5% alpha helix and random coil regions, up to 10% alpha helix and random coil regions, up to 15% alpha helix and random coil regions, up to 20% alpha helix and random coil regions, up to 25% alpha helix and random coil regions, up to 30% alpha helix and random coil regions, up to 35% helix and random coil regions, up to 40% alpha helix and random coil regions, up to 45% alpha helix and random coil regions, or up to 50% alpha helix and random coil regions.In still other aspects of these embodiments, the hydrogel has a protein structure comprising, for example, about 5% to about 10% alpha helix and random coil regions, about 5% to about 15% alpha helix and random coil regions, about 5% to about 20% alpha helix and random coil regions, about 5% to about 25% alpha helix and random coil regions, about 5% to about 30% alpha helix and random coil regions, about 5% to about 40% alpha helix and random coil regions, about 5% to about 50% alpha helix and random coil regions, about 10% to about 20% alpha helix and random coil regions, about 10% to about 30% alpha helix and random coil regions, about 15% to about 25% alpha helix and random coil regions, about 15% to about 30% alpha helix and random coil regions, or about 15% to about 35% alpha helix and random coil regions.
[0149] In some embodiments, the SPF solution compositions of the present disclosure have a storage stability of 10 days to 3 years (i.e., when stored in aqueous solution, they do not gradually or spontaneously gel and there is no obvious aggregation of fragments and / or increase in molecular weight over time), depending on storage conditions, percent silk, and number of shipments and shipping conditions. The pH can be further modified to prevent premature folding and aggregation of the silk, thereby extending shelf life and / or assisting shipping conditions. In embodiments, the SPF solution compositions of the present disclosure have a storage stability of up to 2 weeks at room temperature (RT). In embodiments, the SPF solution compositions of the present disclosure have a storage stability of up to 4 weeks at RT. In embodiments, the SPF solution compositions of the present disclosure have a storage stability of up to 6 weeks at RT. In embodiments, the SPF solution compositions of the present disclosure have a storage stability of up to 8 weeks at RT. In embodiments, the SPF solution compositions of the present disclosure have a storage stability of up to 10 weeks at RT. In embodiments, the SPF solution compositions of the present disclosure have a storage stability of up to 12 weeks at RT. In embodiments, the SPF solution compositions of the present disclosure have a storage stability of about 4 weeks to about 52 weeks at RT. Table 1 below shows storage stability test results for embodiments of the SPF compositions of the present disclosure. [Table 1]
[0150] Known additives, such as vitamins (e.g., vitamin C), can be added to the SPF liquid compositions of the present disclosure to produce gels stable at room temperature (RT) for 10 days to 3 years. Both the SPF composition and the SPF composition containing additives can be freeze-dried for improved shelf life of 10 days to 10 years, depending on storage and shipping conditions. Freeze-dried silk powder can also be used as a raw material for the medical, consumer, and electronic markets. Furthermore, freeze-dried silk powder can be resuspended in water, HFIP, or organic solutions after storage to produce silk solutions of various concentrations, including solutions with higher concentrations than those initially produced. In another embodiment, silk fibroin-based protein fragments are dried using a rototherm evaporator or other methods known in the art to produce a dry protein form containing less than 10% water by weight.
[0151] The SPF used in the tissue fillers and methods disclosed herein can be manipulated and contained in various ways (e.g., in solution form) and combined with other materials (e.g., HA) to prepare the tissue filler compositions described herein. The following are non-limiting examples of suitable ranges for various parameters in and for the preparation of the silk solutions of the present disclosure. The silk solutions of the present disclosure can include one or more (but not necessarily all) of these parameters and can be prepared using various combinations of such parameter ranges.
[0152] In embodiments, the % silk in solution is less than 30%. In embodiments, the % silk in solution is less than 25%. In embodiments, the % silk in solution is less than 20%. In embodiments, the % silk in solution is less than 19%. In embodiments, the % silk in solution is less than 18%. In embodiments, the % silk in solution is less than 17%. In embodiments, the % silk in solution is less than 16%. In embodiments, the % silk in solution is less than 15%. In embodiments, the % silk in solution is less than 14%. In embodiments, the % silk in solution is less than 13%. In embodiments, the % silk in solution is less than 12%. In embodiments, the % silk in solution is less than 11%. In embodiments, the % silk in solution is less than 10%. In embodiments, the % silk in solution is less than 9%. In embodiments, the % silk in solution is less than 8%. In embodiments, the % silk in solution is less than 7%. In embodiments, the % silk in solution is less than 6%. In embodiments, the % silk in solution is less than 5%. In embodiments, the % silk in solution is less than 4%. In embodiments, the % silk in solution is less than 3%. In embodiments, the % silk in solution is less than 2%. In embodiments, the % silk in solution is less than 1%. In embodiments, the % silk in solution is less than 0.9%. In embodiments, the % silk in solution is less than 0.8%. In embodiments, the % silk in solution is less than 0.7%. In embodiments, the % silk in solution is less than 0.6%. In embodiments, the % silk in solution is less than 0.5%. In embodiments, the % silk in solution is less than 0.4%. In embodiments, the % silk in solution is less than 0.3%. In embodiments, the % silk in solution is less than 0.2%. In embodiments, the % silk in solution is less than 0.1%. In embodiments, the % silk in solution is greater than 0.1%. In embodiments, the % silk in solution is greater than 0.2%. In embodiments, the % silk in solution is greater than 0.3%. In embodiments, the % silk in solution is greater than 0.4%. In embodiments, the % silk in solution is greater than 0.5%. In embodiments, the % silk in solution is greater than 0.6%. In embodiments, the % silk in solution is greater than 0.7%.In embodiments, the % silk in solution is greater than 0.8%. In embodiments, the % silk in solution is greater than 0.9%. In embodiments, the % silk in solution is greater than 1%. In embodiments, the % silk in solution is greater than 2%. In embodiments, the % silk in solution is greater than 3%. In embodiments, the % silk in solution is greater than 4%. In embodiments, the % silk in solution is greater than 5%. In embodiments, the % silk in solution is greater than 6%. In embodiments, the % silk in solution is greater than 7%. In embodiments, the % silk in solution is greater than 8%. In embodiments, the % silk in solution is greater than 9%. In embodiments, the % silk in solution is greater than 10%. In embodiments, the % silk in solution is greater than 11%. In embodiments, the % silk in solution is greater than 12%. In embodiments, the % silk in solution is greater than 13%. In embodiments, the % silk in solution is greater than 14%. In embodiments, the % silk in solution is greater than 15%. In embodiments, the % silk in solution is greater than 16%. In embodiments, the % silk in solution is greater than 17%. In embodiments, the % silk in solution is greater than 18%. In embodiments, the % silk in solution is greater than 19%. In embodiments, the % silk in solution is greater than 20%. In embodiments, the % silk in solution is greater than 25%. In embodiments, the % silk in solution is between 0.1% and 30%. In embodiments, the % silk in solution is between 0.1% and 25%. In embodiments, the % silk in solution is between 0.1% and 20%. In embodiments, the % silk in solution is between 0.1% and 15%. In embodiments, the % silk in solution is between 0.1% and 10%. In an embodiment, the silk (%) in solution is 0.1% to 9%. In an embodiment, the silk (%) in solution is 0.1% to 8%. In an embodiment, the silk (%) in solution is 0.1% to 7%. In an embodiment, the silk (%) in solution is 0.1% to 6.5%. In an embodiment, the silk (%) in solution is 0.1% to 6%. In an embodiment, the silk (%) in solution is 0.1% to 5.5%. In an embodiment, the silk (%) in solution is 0.1% to 5%. In an embodiment, the silk (%) in solution is 0.1% to 4.5%. In an embodiment, the silk (%) in solution is 0.1% to 4%. In an embodiment, the silk (%) in solution is 0.1% to 3.5%.In an embodiment, the silk (%) in solution is 0.1% to 3%. In an embodiment, the silk (%) in solution is 0.1% to 2.5%. In an embodiment, the silk (%) in solution is 0.1% to 2.0%. In an embodiment, the silk (%) in solution is 0.1% to 2.4%. In an embodiment, the silk (%) in solution is 0.5% to 5%. In an embodiment, the silk (%) in solution is 0.5% to 4.5%. In an embodiment, the silk (%) in solution is 0.5% to 4%. In an embodiment, the silk (%) in solution is 0.5% to 3.5%. In an embodiment, the silk (%) in solution is 0.5% to 3%. In an embodiment, the silk (%) in solution is 0.5% to 2.5%. In an embodiment, the silk (%) in solution is 1 to 4%. In an embodiment, the silk (%) in solution is 1 to 3.5%. In an embodiment, the silk (%) in solution is 1% to 3%. In an embodiment, the silk (%) in solution is 1% to 2.5%. In an embodiment, the silk (%) in solution is 1% to 2.4%. In an embodiment, the silk (%) in solution is 1% to 2%. In an embodiment, the silk (%) in solution is 20% to 30%. In an embodiment, the silk (%) in solution is 0.1% to 6%. In an embodiment, the silk (%) in solution is 6% to 10%. In an embodiment, the silk (%) in solution is 6% to 8%. In an embodiment, the silk (%) in solution is 6% to 9%. In an embodiment, the silk (%) in solution is 10% to 20%. In an embodiment, the silk (%) in solution is 11% to 19%. In an embodiment, the silk (%) in solution is 12% to 18%. In an embodiment, the silk (%) in solution is 13% to 17%. In an embodiment, the % silk in solution is 14% to 16%.
[0153] In embodiments, the silk compositions described herein can be combined with HA to form tissue filler compositions. In embodiments, the silk content (wt%) in the tissue filler composition is less than 30%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 25%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 20%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 19%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 18%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 17%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 16%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 15%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 14%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 13%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 12%. In embodiments, the tissue filler composition contains less than 11% silk by weight. In embodiments, the tissue filler composition contains less than 10% silk by weight. In embodiments, the tissue filler composition contains less than 9% silk by weight. In embodiments, the tissue filler composition contains less than 8% silk by weight. In embodiments, the tissue filler composition contains less than 7% silk by weight. In embodiments, the tissue filler composition contains less than 6% silk by weight. In embodiments, the tissue filler composition contains less than 5% silk by weight. In embodiments, the tissue filler composition contains less than 4% silk by weight. In embodiments, the tissue filler composition contains less than 3% silk by weight. In embodiments, the tissue filler composition contains less than 2% silk by weight. In embodiments, the tissue filler composition contains less than 1% silk by weight. In embodiments, the tissue filler composition contains less than 0.9% silk by weight. In embodiments, the silk (wt%) in the tissue filler composition is less than 0.8%. In embodiments, the silk (wt%) in the tissue filler composition is less than 0.7%. In embodiments, the silk (wt%) in the tissue filler composition is less than 0.6%. In embodiments, the silk (wt%) in the tissue filler composition is less than 0.5%.In embodiments, the silk content (wt%) in the tissue filler composition is less than 0.4%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 0.3%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 0.2%. In embodiments, the silk content (wt%) in the tissue filler composition is less than 0.1%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 0.1%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 0.2%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 0.3%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 0.4%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 0.5%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 0.6%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 0.7%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 0.8%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 0.9%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 1%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 2%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 3%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 4%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 5%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 6%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 7%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 8%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 9%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 10%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 11%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 12%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 13%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 14%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 15%. In embodiments, the silk (wt%) in the tissue filler composition is greater than 16%.In embodiments, the silk content (wt%) in the tissue filler composition is greater than 17%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 18%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 19%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 20%. In embodiments, the silk content (wt%) in the tissue filler composition is greater than 25%. In embodiments, the silk content (wt%) in the tissue filler composition is 0.1% to 30%. In embodiments, the silk content (wt%) in the tissue filler composition is 0.1% to 25%. In embodiments, the silk content (wt%) in the tissue filler composition is 0.1% to 20%. In embodiments, the silk content (wt%) in the tissue filler composition is 0.1% to 15%. In embodiments, the silk content (wt%) in the tissue filler composition is 0.1% to 10%. In embodiments, the silk content (wt%) in the tissue filler composition is 0.1% to 9%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 8%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 7%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 6.5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 6%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 5.5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 4.5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 4%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 3.5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 3%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 2.5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 2.0%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 2.4%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.5% to 5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.5% to 4.5%.In an embodiment, the silk content (wt%) in the tissue filler composition is 0.5% to 4%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.5% to 3.5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.5% to 3%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.5% to 2.5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 1 to 4%. In an embodiment, the silk content (wt%) in the tissue filler composition is 1% to 3.5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 1% to 3%. In an embodiment, the silk content (wt%) in the tissue filler composition is 1% to 2.5%. In an embodiment, the silk content (wt%) in the tissue filler composition is 1% to 2.4%. In an embodiment, the silk content (wt%) in the tissue filler composition is 1% to 2%. In an embodiment, the silk content (wt%) in the tissue filler composition is 20% to 30%. In an embodiment, the silk content (wt%) in the tissue filler composition is 0.1% to 6%. In an embodiment, the silk content (wt%) in the tissue filler composition is 6% to 10%. In an embodiment, the silk content (wt%) in the tissue filler composition is 6% to 8%. In an embodiment, the silk content (wt%) in the tissue filler composition is 6% to 9%. In an embodiment, the silk content (wt%) in the tissue filler composition is 10% to 20%. In an embodiment, the silk content (wt%) in the tissue filler composition is 11% to 19%. In an embodiment, the silk content (wt%) in the tissue filler composition is 12% to 18%. In an embodiment, the silk content (wt%) in the tissue filler composition is 13% to 17%. In an embodiment, the silk content (wt%) in the tissue filler composition is 14% to 16%.
[0154] In embodiments, the percentage of sericin in the solution or tissue filler composition is undetectable to 30%. In embodiments, the percentage of sericin in the solution or tissue filler composition is undetectable to 5%. In embodiments, the percentage of sericin in the solution or tissue filler composition is 1%. In embodiments, the percentage of sericin in the solution or tissue filler composition is 2%. In embodiments, the percentage of sericin in the solution or tissue filler composition is 3%. In embodiments, the percentage of sericin in the solution or tissue filler composition is 4%. In embodiments, the percentage of sericin in the solution or tissue filler composition is 5%. In embodiments, the percentage of sericin in the solution or tissue filler composition is 10%. In embodiments, the percentage of sericin in the solution or tissue filler composition is 30%.
[0155] In embodiments, the stability of the LiBr-silk fragment solution is 0 to 1 year. In embodiments, the stability of the LiBr-silk fragment solution is 0 to 2 years. In embodiments, the stability of the LiBr-silk fragment solution is 0 to 3 years. In embodiments, the stability of the LiBr-silk fragment solution is 0 to 4 years. In embodiments, the stability of the LiBr-silk fragment solution is 0 to 5 years. In embodiments, the stability of the LiBr-silk fragment solution is 1 to 2 years. In embodiments, the stability of the LiBr-silk fragment solution is 1 to 3 years. In embodiments, the stability of the LiBr-silk fragment solution is 1 to 4 years. In embodiments, the stability of the LiBr-silk fragment solution is 1 to 5 years. In embodiments, the stability of the LiBr-silk fragment solution is 2 to 3 years. In embodiments, the stability of the LiBr-silk fragment solution is 2 to 4 years. In embodiments, the stability of the LiBr-silk fragment solution is 2 to 5 years. In an embodiment, the stability of the LiBr-silk fragment solution is 3 to 4 years. In an embodiment, the stability of the LiBr-silk fragment solution is 3 to 5 years. In an embodiment, the stability of the LiBr-silk fragment solution is 4 to 5 years.
[0156] In an embodiment, the stability of the silk fibroin-based protein fragment composition that may be included in the tissue filler of the present disclosure is between 10 days and 6 months. In an embodiment, the stability of the silk fibroin-based protein fragment composition that may be included in the tissue filler of the present disclosure is between 6 months and 12 months. In an embodiment, the stability of the silk fibroin-based protein fragment composition that may be included in the tissue filler of the present disclosure is between 12 months and 18 months. In an embodiment, the stability of the silk fibroin-based protein fragment composition that may be included in the tissue filler of the present disclosure is between 18 months and 24 months. In an embodiment, the stability of the silk fibroin-based protein fragment composition that may be included in the tissue filler of the present disclosure is between 24 months and 30 months. In an embodiment, the stability of the silk fibroin-based protein fragment composition that may be included in the tissue filler of the present disclosure is between 30 months and 36 months. In an embodiment, the stability of the silk fibroin-based protein fragment composition that may be included in the tissue filler of the present disclosure is between 36 months and 48 months. In embodiments, the silk fibroin-based protein fragment compositions that may be included in the tissue fillers of the present disclosure have a stability of 48 to 60 months.
[0157] In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 250 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 5 kDa to 150 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 6 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 6 kDa to 17 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 17 kDa to 39 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 39 kDa to 80 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of between 80 kDa and 150 kDa.
[0158] In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 250 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 240 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 230 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 220 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 210 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 200 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 190 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 180 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 170 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 160 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 150 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 140 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of between 1 kDa and 130 kDa.In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 120 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 110 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 100 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 90 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 80 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 70 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 60 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 50 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 40 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 30 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 20 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 kDa to 10 kDa.
[0159] In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 1 to 5 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 5 to 10 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 10 to 15 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 15 to 20 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 20 to 25 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 25 to 30 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 30 to 35 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 35 to 40 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 40 to 45 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 45 to 50 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 50 to 55 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 55 to 60 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 60 to 65 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 65 to 70 kDa.In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 70 to 75 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 75 to 80 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 80 to 85 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 85 to 90 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 90 to 95 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 95 to 100 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 100 to 105 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 105 to 110 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 110 to 115 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 115 to 120 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 120 to 125 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 125 to 130 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 130 to 135 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 135-140 kDa.In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 140 to 145 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 145 to 150 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 150 to 155 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 155 to 160 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 160 to 165 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 165 to 170 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 170 to 175 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 175 to 180 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 180 to 185 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 185 to 190 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 190 to 195 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 195 to 200 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 200-205 kDa.In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 205 to 210 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 210 to 215 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 215 to 220 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 220 to 225 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 225 to 230 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 230 to 235 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 235 to 240 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 240 to 245 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 245 to 250 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 250 to 255 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 255 to 260 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 260 to 265 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 265-270 kDa.In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 270 to 275 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 275 to 280 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 280 to 285 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 285 to 290 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 290 to 295 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 295 to 300 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 300 to 305 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 305 to 310 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 310 to 315 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 315 to 320 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 320 to 325 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 325 to 330 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 330-335 kDa.In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 35 to 340 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 340 to 345 kDa. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have an average weight average molecular weight of 345 to 350 kDa.
[0160] In embodiments, the tissue fillers described herein may comprise silk proteins, including one or more of low molecular weight silk, medium molecular weight silk, and high molecular weight silk.
[0161] In embodiments, the tissue fillers described herein can comprise silk proteins comprising one or more of low molecular weight silk, medium molecular weight silk, and high molecular weight silk. In embodiments, the tissue fillers described herein can comprise silk proteins comprising low molecular weight silk and medium molecular weight silk. In embodiments, the tissue fillers described herein can comprise silk proteins comprising low molecular weight silk and high molecular weight silk. In embodiments, the tissue fillers described herein can comprise silk proteins comprising medium molecular weight silk and high molecular weight silk. In embodiments, the tissue fillers described herein can comprise silk proteins comprising low molecular weight silk, medium molecular weight silk, and high molecular weight silk.
[0162] In embodiments, the tissue fillers described herein can comprise silk proteins, including low and medium molecular weight silks. In some embodiments, the w / w ratio between the low and medium molecular weight silks is about 99:1 to about 1:99, about 95:5 to about 5:95, about 90:10 to about 10:90, about 75:25 to about 25:75, about 65:35 to about 35:65, or about 55:45 to about 45:55. In some embodiments, the w / w ratio between the low and medium molecular weight silks is about 99:1 to about 55:45, about 95:5 to about 45:55, about 90:10 to about 35:65, about 75:25 to about 15:85, about 65:35 to about 10:90, or about 55:45 to about 1:99.In some embodiments, the w / w ratio between the low molecular weight silk and the medium molecular weight silk is about 99:1, about 98:2, about 97:3, about 96:4, about 95:5, about 94:6, about 93:7, about 92:8, about 91:9, about 90:10, about 89:11, about 88:12, about 87:13, about 86:14, about 85:15, about 84:16, about 83:17, about 82:18, about 81:19, about 80:20, about 79:21, about 78:22 , approximately 77:23, approximately 76:24, approximately 75:25, approximately 74:26, approximately 73:27, approximately 72:28, approximately 71:29, approximately 70:30, approximately 69:31, approximately 68:32, approximately 67:33, approximately 66:34, approximately 65:35, approximately 64:36, approximately 63:37, approximately 62:38, approximately 61:39, approximately 60:40, approximately 59:41, approximately 58:42, approximately 57:43, approximately 56:44, approximately 55:45, approximately 54:46, approximately 53:47, approximately 52 :48, approximately 51:49, approximately 50:50, approximately 49:51, approximately 48:52, approximately 47:53, approximately 46:54, approximately 45:55, approximately 44:56, approximately 43:57, approximately 42:58, approximately 41:59, approximately 40:60, approximately 39:61, approximately 38:62, approximately 37:63, approximately 36:64, approximately 35:65, approximately 34:66, approximately 33:67, approximately 32:68, approximately 31:69, approximately 30:70, approximately 29:71, approximately 28:72, approximately 27:73 , about 26:74, about 25:75, about 24:76, about 23:77, about 22:78, about 21:79, about 20:80, about 19:81, about 18:82, about 17:83, about 16:84, about 15:85, about 14:86, about 13:87, about 12:88, about 11:89, about 10:90, about 9:91, about 8:92, about 7:93, about 6:94, about 5:95, about 4:96, about 3:97, about 2:98, or about 1:99. In embodiments, the w / w ratio between the low molecular weight silk and the medium molecular weight silk is about 9:1, about 8:1, about 7:1, about 6:1, about 5:1, about 4:1, about 3:1, about 2:1, or about 1:1. In embodiments, the w / w ratio between the low molecular weight silk and the medium molecular weight silk is about 1:9, about 1:8, about 1:7, about 1:6, about 1:5, about 1:4, about 1:3, about 1:2, or about 1:1.
[0163] In embodiments, the tissue fillers described herein can comprise silk proteins, including low molecular weight silk and high molecular weight silk. In some embodiments, the w / w ratio between the low molecular weight silk and the high molecular weight silk is about 99:1 to about 1:99, about 95:5 to about 5:95, about 90:10 to about 10:90, about 75:25 to about 25:75, about 65:35 to about 35:65, or about 55:45 to about 45:55. In some embodiments, the w / w ratio between the low molecular weight silk and the high molecular weight silk is about 99:1 to about 55:45, about 95:5 to about 45:55, about 90:10 to about 35:65, about 75:25 to about 15:85, about 65:35 to about 10:90, or about 55:45 to about 1:99.In some embodiments, the w / w ratio between the low molecular weight silk and the high molecular weight silk is about 99:1, about 98:2, about 97:3, about 96:4, about 95:5, about 94:6, about 93:7, about 92:8, about 91:9, about 90:10, about 89:11, about 88:12, about 87:13, about 86:14, about 85:15, about 84:16, about 83:17, about 82:18, about 81:19, about 80:20, about 79:21, about 78:22 , approximately 77:23, approximately 76:24, approximately 75:25, approximately 74:26, approximately 73:27, approximately 72:28, approximately 71:29, approximately 70:30, approximately 69:31, approximately 68:32, approximately 67:33, approximately 66:34, approximately 65:35, approximately 64:36, approximately 63:37, approximately 62:38, approximately 61:39, approximately 60:40, approximately 59:41, approximately 58:42, approximately 57:43, approximately 56:44, approximately 55:45, approximately 54:46, approximately 53:47, approximately 52 :48, approximately 51:49, approximately 50:50, approximately 49:51, approximately 48:52, approximately 47:53, approximately 46:54, approximately 45:55, approximately 44:56, approximately 43:57, approximately 42:58, approximately 41:59, approximately 40:60, approximately 39:61, approximately 38:62, approximately 37:63, approximately 36:64, approximately 35:65, approximately 34:66, approximately 33:67, approximately 32:68, approximately 31:69, approximately 30:70, approximately 29:71, approximately 28:72, approximately 27:73 , about 26:74, about 25:75, about 24:76, about 23:77, about 22:78, about 21:79, about 20:80, about 19:81, about 18:82, about 17:83, about 16:84, about 15:85, about 14:86, about 13:87, about 12:88, about 11:89, about 10:90, about 9:91, about 8:92, about 7:93, about 6:94, about 5:95, about 4:96, about 3:97, about 2:98, or about 1:99.
[0164] In embodiments, the tissue fillers described herein can comprise silk proteins, including medium molecular weight silk and high molecular weight silk. In some embodiments, the w / w ratio between the medium molecular weight silk and the high molecular weight silk is about 99:1 to about 1:99, about 95:5 to about 5:95, about 90:10 to about 10:90, about 75:25 to about 25:75, about 65:35 to about 35:65, or about 55:45 to about 45:55. In some embodiments, the w / w ratio between the medium molecular weight silk and the high molecular weight silk is about 99:1 to about 55:45, about 95:5 to about 45:55, about 90:10 to about 35:65, about 75:25 to about 15:85, about 65:35 to about 10:90, or about 55:45 to about 1:99.In some embodiments, the w / w ratio between the medium molecular weight silk and the high molecular weight silk is about 99:1, about 98:2, about 97:3, about 96:4, about 95:5, about 94:6, about 93:7, about 92:8, about 91:9, about 90:10, about 89:11, about 88:12, about 87:13, about 86:14, about 85:15, about 84:16, about 83:17, about 82:18, about 81:19, about 80:20, about 79:21, about 78:22 , approximately 77:23, approximately 76:24, approximately 75:25, approximately 74:26, approximately 73:27, approximately 72:28, approximately 71:29, approximately 70:30, approximately 69:31, approximately 68:32, approximately 67:33, approximately 66:34, approximately 65:35, approximately 64:36, approximately 63:37, approximately 62:38, approximately 61:39, approximately 60:40, approximately 59:41, approximately 58:42, approximately 57:43, approximately 56:44, approximately 55:45, approximately 54:46, approximately 53:47, approximately 52 :48, approximately 51:49, approximately 50:50, approximately 49:51, approximately 48:52, approximately 47:53, approximately 46:54, approximately 45:55, approximately 44:56, approximately 43:57, approximately 42:58, approximately 41:59, approximately 40:60, approximately 39:61, approximately 38:62, approximately 37:63, approximately 36:64, approximately 35:65, approximately 34:66, approximately 33:67, approximately 32:68, approximately 31:69, approximately 30:70, approximately 29:71, approximately 28:72, approximately 27:73 , about 26:74, about 25:75, about 24:76, about 23:77, about 22:78, about 21:79, about 20:80, about 19:81, about 18:82, about 17:83, about 16:84, about 15:85, about 14:86, about 13:87, about 12:88, about 11:89, about 10:90, about 9:91, about 8:92, about 7:93, about 6:94, about 5:95, about 4:96, about 3:97, about 2:98, or about 1:99.
[0165] In embodiments, the tissue fillers described herein can include silk proteins, including low molecular weight silk, medium molecular weight silk, and high molecular weight silk. In embodiments, the w / w ratio between the low molecular weight silk, the medium molecular weight silk, and the high molecular weight silk is about 1:1:8, 1:2:7, 1:3:6, 1:4:5, 1:5:4, 1:6:3, 1:7:2, 1:8:1, 2:1:7, 2:2:6, 2:3:5, 2:4:4, 2:5:3, 2:6:2, 2:7:1, 3:1:6, 3:2:5, 3:3:4, 3:4:3, 3:5:2, 3:6:1, 4:1:5, 4:2:4, 4:3:3, 4:4:2, 4:5:1, 5:1:4, 5:2:3, 5:3:2, 5:4:1, 6:1:3, 6:2:2, 6:3:1, 7:1:2, 7:2:1, or 8:1:1. In embodiments, the w / w ratio between the low molecular weight silk, the medium molecular weight silk, and the high molecular weight silk is about 3:0.1:0.9, 3:0.2:0.8, 3:0.3:0.7, 3:0.4:0.6, 3:0.5:0.5, 3:0.6:0.4, 3:0.7:0.3, 3:0.8:0.2, or 3:0.9:0.1.
[0166] In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have a polydispersity of about 1 to about 5.0. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have a polydispersity of about 1.5 to about 3.0. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have a polydispersity of about 1 to about 1.5. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have a polydispersity of about 1.5 to about 2.0. In embodiments, the silk fibroin-based protein fragments contained in the tissue fillers described herein have a polydispersity of about 2.0 to about 2.5. In embodiments, compositions of the present disclosure comprising pure silk fibroin-based protein fragments have a polydispersity of about 2.0 to about 3.0. In embodiments, compositions of the present disclosure comprising pure silk fibroin-based protein fragments have a polydispersity of about 2.5 to about 3.0.
[0167] In embodiments, tissue fillers described herein that include SPF contain undetectable levels of LiBr residue. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is between 10 ppm and 1000 ppm. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is between 10 ppm and 300 ppm. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is less than 25 ppm. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is less than 50 ppm. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is less than 75 ppm. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is less than 100 ppm. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is less than 200 ppm. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is less than 300 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is less than 400 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is less than 500 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is less than 600 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is less than 700 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is less than 800 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is less than 900 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is less than 1000 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is between undetectable and 500 ppm. In embodiments, the amount of LiBr residue in the tissue fillers described herein that include SPF is between undetectable and 450 ppm. In embodiments, the amount of LiBr residue in the tissue fillers described herein that include SPF is between undetectable and 400 ppm.In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is between undetectable and 350 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is between undetectable and 300 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is between undetectable and 250 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is between undetectable and 200 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is between undetectable and 150 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is between undetectable and 100 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is between 100 ppm and 200 ppm. In embodiments, the amount of LiBr residual in tissue fillers described herein that include SPF is between 200 ppm and 300 ppm. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is between 300 ppm and 400 ppm. In embodiments, the amount of LiBr residue in tissue fillers described herein that include SPF is between 400 ppm and 500 ppm.
[0168] In embodiments, tissue fillers described herein that include SPF with pure silk fibroin-based protein fragments contain undetectable levels of Na2CO3 residue. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 100 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 200 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 300 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 400 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 500 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 600 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 700 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 800 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 900 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is less than 1000 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is undetectable to 500 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is undetectable to 450 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is undetectable to 400 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is undetectable to 350 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is undetectable to 300 ppm. In embodiments, the amount of Na2CO3 residual in the tissue fillers described herein that include SPF is between undetectable and 250 ppm. In embodiments, the amount of Na2CO3 residual in the tissue fillers described herein that include SPF is between undetectable and 200 ppm.In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is between undetectable and 150 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is between undetectable and 100 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is between 100 ppm and 200 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is between 200 ppm and 300 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is between 300 ppm and 400 ppm. In embodiments, the amount of Na2CO3 residue in tissue fillers described herein that include SPF is between 400 ppm and 500 ppm.
[0169] In an embodiment, the water solubility of the pure silk fibroin-based protein fragment of the present disclosure is 50-100%. In an embodiment, the water solubility of the pure silk fibroin-based protein fragment of the present disclosure is 60-100%. In an embodiment, the water solubility of the pure silk fibroin-based protein fragment of the present disclosure is 70-100%. In an embodiment, the water solubility of the pure silk fibroin-based protein fragment of the present disclosure is 80-100%. In an embodiment, the water solubility is 90-100%. In an embodiment, the silk fibroin-based fragment of the present disclosure is insoluble in aqueous solution.
[0170] In an embodiment, the solubility of the pure silk fibroin-based protein fragment of the present disclosure in an organic solution is 50-100%. In an embodiment, the solubility of the pure silk fibroin-based protein fragment of the present disclosure in an organic solution is 60-100%. In an embodiment, the solubility of the pure silk fibroin-based protein fragment of the present disclosure in an organic solution is 70-100%. In an embodiment, the solubility of the pure silk fibroin-based protein fragment of the present disclosure in an organic solution is 80-100%. In an embodiment, the solubility of the pure silk fibroin-based protein fragment of the present disclosure in an organic solution is 90-100%. In an embodiment, the silk fibroin-based fragment of the present disclosure is insoluble in an organic solution.
[0171] Methods for producing silk protein fragments for use in the compositions of the present disclosure are described in U.S. Patent Application Publication Nos. 2015 / 00933340, 2015 / 0094269, 2016 / 0193130, 2016 / 0022560, 2016 / 0022561, 2016 / 0022562, 2016 / 0022563, Nos. 2016 / 0222579 and 2016 / 0281294, as well as U.S. Patent Nos. 9,187,538, 9,522,107, 9,517,191, 9,522,108, 9,511,012, and 9,545,369, which are incorporated herein by reference in their entireties. However, an exemplary method is shown in FIG. 1, which is a flow chart illustrating various embodiments for producing pure silk fibroin-based protein fragments (SPF) of the present disclosure. It should be understood that not all of the illustrated steps are necessarily required to process all silk solutions of the present disclosure. As illustrated in FIG. 1, Step A, silk cocoons (heat-treated or not), silk fibers, silk powder, or spider silk can be used as the silk source. Starting with raw silk cocoons from silkworms, the cocoons can be cut into small pieces, e.g., roughly equal-sized pieces (step B1). The raw silk is then extracted and rinsed to remove sericin (step C1a). This results in raw silk that is substantially free of sericin. In one embodiment, water is heated to a temperature of 84°C to 100°C (ideally boiling), and then Na2CO3 (sodium carbonate) is added to the boiling water to completely dissolve the Na2CO3. The raw silk is added to the boiling water / Na2CO3 (100°C) and allowed to soak for about 15 to 90 minutes; boiling for longer periods results in smaller silk protein fragments. In one embodiment, the volume of water is equal to about 0.4 x the weight of the raw silk, and the volume of Na2CO3 is equal to about 0.848 x the weight of the raw silk. In one embodiment, the volume of water is equal to 0.1 x raw silk weight and the volume of Na2CO3 is maintained at 2.12 g / L.This is shown in Figures 6 and 7: sericin removal (substantially free of sericin) was achieved by varying the silk mass (x-axis) in the same volume of extraction solution (i.e., the same volume of water and Na2CO3 concentration), as evidenced by an overall silk mass loss (y-axis) of 26 to 31 percent. The aqueous Na2CO3 solution is then drained, and excess water / Na2CO3 is removed from the silk fibroin fibers (e.g., by ringing out the fibroin extract, such as by manual or mechanical dehydration cycles). The resulting silk fibroin extract is rinsed with warm to hot water, typically at a temperature ranging from about 40°C to about 80°C, with at least one change in water volume (repeated as many times as necessary) to remove adsorbed sericin or contaminants. The resulting silk fibroin extract is silk fibroin substantially depleted of sericin. In one embodiment, the resulting silk fibroin extract is rinsed with water at a temperature of about 60°C. In one embodiment, the volume of rinsing water for each cycle is equal to 0.1 L to 0.2 L times the raw silk weight. To maximize the rinsing effect, it may be advantageous to agitate, rotate, or circulate the rinsing water. After rinsing, excess water is removed from the extracted silk fibroin fibers (e.g., manually or mechanically ringing out the fibroin extract). Alternatively, methods known to those skilled in the art, such as pressure, temperature, or other reagents, or a combination thereof, can be used for sericin extraction. Alternatively, silk glands (100% sericin-free silk protein) can be directly removed from the silkworm. This will result in sericin-free liquid silk protein without any modification of the protein structure.
[0172] The extracted fibroin fibers are then completely dried. Once dry, the extracted silk fibroin is dissolved using a solvent added to the silk fibroin at ambient to boiling temperatures (step C1b). In one embodiment, the solvent is a solution of lithium bromide (LiBr) (the boiling point for LiBr is 140°C). Alternatively, the extracted fibroin fibers are not dried but placed in the solvent wet; the solvent concentration can then be varied to achieve a concentration similar to that of dried silk added to the solvent. The final LiBr solvent concentration can range from 0.1 M to 9.3 M. Figure 8 is a table summarizing the molecular weight of silk dissolved from different concentrations of lithium bromide (LiBr) and different extraction and dissolution sizes. Complete dissolution of the extracted fibroin fibers can be achieved by varying the treatment time and temperature, along with the concentration of the dissolving solvent. Other solvents can be used, including, but not limited to, phosphate phosphoric acid, calcium nitrate, calcium chloride solution, or concentrated aqueous solutions of other inorganic salts. To ensure complete dissolution, the silk fibers should be thoroughly immersed in the preheated solvent solution and then maintained at a temperature ranging from about 60° C. to about 140° C. for 1 to 168 hours. In one embodiment, the silk fibers should be thoroughly immersed in the solvent solution and then placed in a drying oven at a temperature of about 100° C. for about 1 hour.
[0173] The temperature at which the silk fibroin extract is added to the LiBr solution (or vice versa) affects the time required to completely dissolve the fibroin, as well as the molecular weight and polydispersity of the resulting final SPF mixture solution. In one embodiment, the silk solvent solution concentration is 20% w / v or less. Furthermore, stirring can be used during addition or dissolution to facilitate dissolution at various temperatures and concentrations. The temperature of the LiBr solution provides control over the molecular weight and polydispersity of the resulting silk protein fragment mixture. In one embodiment, a higher temperature dissolves the silk more quickly, resulting in greater process scalability and mass production of the silk solution. In one embodiment, using a LiBr solution heated to a temperature between 80°C and 140°C reduces the time required in the oven to achieve complete dissolution. Varying the time and temperature of the dissolution solvent at 60°C or above changes and controls the MW and polydispersity of the SPF mixture solution formed from native silk fibroin protein of the original molecular weight.
[0174] Alternatively, whole cocoons can be placed directly into a solvent such as LiBr, bypassing the extraction step (step B2). This requires subsequent filtration of the silkworm particles from the silk and solvent solution and removal of sericin (step C2) using methods known in the art for separating hydrophobic and hydrophilic proteins, such as column separation and / or chromatography, ion exchange, chemical precipitation with salt and / or pH, and / or enzymatic digestion and filtration or extraction (all methods are general examples of standard protein separation methods, but are not limited thereto). Alternatively, non-heat-treated cocoons from which the silkworms have been removed can be placed directly into a solvent such as LiBr, bypassing the extraction step. The above method can be used for sericin isolation, which has the advantage that non-heat-treated cocoons contain significantly less silkworm debris.
[0175] Dialysis can be used to remove the dissolving solvent from the resulting dissolved fibroin protein fragment solution (step E1) by dialyzing the solution against a volume of water. Pre-filtration prior to dialysis helps remove debris (i.e., silkworm remains) from the silk and LiBr solution (step D). In one example, a 3 μm or 5 μm filter is used at a flow rate of 200-300 mL / min to filter a 0.1%-1.0% silk-LiBr solution prior to dialysis and possible concentration, if desired. As discussed above, a key feature of the methods disclosed herein, particularly in terms of providing a scalable process, is the use of time and / or temperature to reduce the concentration from 9.3 M LiBr to a range of 0.1 M-9.3 M to facilitate filtration and downstream dialysis. Alternatively, the 9.3 M LiBr-silk protein fragment solution can be diluted with water to facilitate debris filtration and dialysis without additional time or temperature. The result of dissolution, upon filtration for the desired time and temperature, is a translucent, particle-free, shelf-stable silk protein fragment LiBr solution of known MW and polydispersity at room temperature. It is advantageous to periodically change the dialysis water (e.g., change the water after 1 hour, 4 hours, then every 12 hours for a total of six changes) until the solvent is removed. The total number of water volume changes can be varied based on the resulting concentration of the solvent used for silk protein dissolution and fragmentation. After dialysis, the final silk solution can be further filtered to remove any remaining debris (i.e., silkworm remains).
[0176] Alternatively, tangential flow filtration (TFF), a rapid and efficient method for the separation and purification of biomolecules, can be used to remove the solvent from the resulting dissolved fibroin solution (step E2). TFF provides a highly pure aqueous solution of silk protein fragments, enabling the process to be scaled up to large volumes in a controlled and repeatable manner. Prior to TFF, the silk and LiBr solution can be diluted (from 20% to 0.1% silk in either water or LiBr). Pre-filtration, as described above, prior to TFF processing can maintain filter efficiency and potentially avoid the development of a silk gel boundary layer on the filter surface as a result of the presence of debris particles. Pre-filtration prior to TFF also helps remove residual debris (i.e., silkworm remains) from the silk and LiBr solution (step D), which could cause spontaneous or long-term gelation of the resulting water-only solution. Recirculating or single-pass TFF can be used to generate water-silk protein fragment solutions ranging from 0.1% silk to 30.0% silk (more preferably, 0.1% to 6.0% silk). Different cutoff size TFF membranes may be required based on the desired concentration, molecular weight, and polydispersity of the silk protein fragment mixture in solution. Membranes ranging from 1 to 100 kDa may be required to generate varying molecular weight silk solutions, for example, by varying the length of extraction boiling time or the time and temperature in the dissolution solvent (e.g., LiBr). In one embodiment, TFF 5 or 10 kDa membranes are used to purify the silk protein fragment mixture solution to achieve the final desired silk-to-water ratio. Additionally, TFF single-pass, TFF, and other methods known in the art, such as falling film evaporators, can be used to concentrate the solution (to obtain a desired concentration ranging from 0.1% to 30% silk) following removal of the dissolution solvent (e.g., LiBr). This can be used as an alternative to the standard HFIP concentration method known in the art for making water-based solutions. Larger pore membranes can also be utilized to filter out smaller silk protein fragments and make higher molecular weight silk solutions with and / or without tighter polydispersity values.Figure 5 is a table summarizing molecular weights for several embodiments of silk protein solutions of the present disclosure. Silk protein solution processing conditions were as follows: 20 min of 100°C extraction, room temperature rinse, and 4-6 hours with LiBr in a 60°C oven. Water-soluble film processing conditions were as follows: 60 min of 100°C extraction, 60°C rinse, and 60 min of 100°C LiBr in a 100°C oven. Figures 12-23 further illustrate the extraction times, LiBr dissolution conditions, and TFF processing procedures, as well as the resulting exemplary molecular weights and polydispersities. These examples are not intended to be limiting and demonstrate the feasibility of specifying parameters for specific molecular weight silk fragment solutions.
[0177] Assays for LiBr and Na2CO3 detection were performed using an HPLC system equipped with an evaporative light scattering detector (ELSD). Calculations were performed by linear regression of the resulting peak areas for the analytes plotted against concentration. Two or more samples of several formulations of this disclosure were used for sample preparation and analysis. Typically, four samples of different formulations were weighed directly into a 10 mL volumetric flask. The sample was suspended in 5 mL of 20 mM ammonium formate (pH 3.0) and maintained at 2-8 °C for 2 hours with occasional shaking to extract the analytes from the film. After 2 hours, the solution was diluted with 20 mM ammonium formate (pH 3.0). The sample solution in the volumetric flask was transferred to an HPLC vial and injected into the HPLC-ELSD system for estimation of sodium carbonate and lithium bromide.
[0178] The analytical method developed for quantifying Na2CO3 and LiBr in silk protein formulations was found to be linear in the range of 10-165 μg / mL. The RSDs of the injection precision were 2% and 1% for area and 0.38% and 0.19% for retention time for sodium carbonate and lithium bromide, respectively. This analytical method can be applied for the quantitative determination of sodium carbonate and lithium bromide in silk protein formulations.
[0179] The final silk protein fragment solution is pure silk protein fragments and water, containing non-detectable levels of particulate debris and / or process contaminants, including LiBr and Na2CO3, at ppm to ppm. Figures 3 and 4 are tables summarizing the LiBr and Na2CO3 concentrations in the solutions of the present disclosure. In Figure 3, processing conditions included 60 min of 100°C extraction, a 60°C rinse, and 60 min of 100°C LiBr in a 100°C oven. TFF conditions, including pressure differential and number of diafiltration volumes, were varied. In Figure 4, processing conditions included 60 min of boiling at 100°C, a 60°C rinse, and 4-6 hours of LiBr in a 60°C oven.
[0180] Aqueous silk fragment solutions, lyophilized silk protein fragment mixtures, or any other compositions containing SPF can be sterilized according to standard methods in the art, such as filtration, heating, radiation, or electron beam sterilization. Due to its shorter protein polymer length, silk protein fragment mixtures are expected to withstand sterilization better than intact silk protein solutions described in the art. Furthermore, silk articles made from the SPF mixtures described herein can be sterilized depending on the intended use. For example, molecule-loaded SPF dermal fillers used in medical applications involving open wounds / incisions can be sterilized using standard methods, such as radiation or electron beam sterilization.
[0181] 2 is a flow chart illustrating various parameters that can be modified during the extraction and dissolution steps of the process of making the silk protein fragment solution of the present disclosure. Selected method parameters can be altered to achieve distinct final solution characteristics depending on the intended application, such as molecular weight and polydispersity. It should be understood that not all of the illustrated steps are necessarily required to process all silk solutions of the present disclosure.
[0182] In one embodiment, the process for producing the silk protein fragment solution of the present disclosure includes forming silk cocoon pieces from silkworms, extracting the pieces in a solution of water and Na2CO3 at about 100°C for about 60 minutes (wherein the volume of water is equal to about 0.4 x the raw silk weight and the amount of Na2CO3 is about 0.848 x the amount of pieces to form the silk fibroin extract); rinsing the silk fibroin extract three times with a volume of rinse water at about 60°C for about 20 minutes per rinse (wherein the rinse water for each cycle is equal to about 0.2 L x the weight of the pieces); removing excess water from the silk fibroin extract; The method includes drying the silk fibroin extract, dissolving the dried silk fibroin extract in a LiBr solution (the LiBr solution is first heated to about 100°C to create and maintain a silk and LiBr solution), placing the silk and LiBr solution in a drying oven at about 100°C for about 60 minutes to achieve complete dissolution and further fragmentation of the native silk protein structure into a mixture with the desired molecular weight and polydispersity, filtering the solution to remove any remaining debris from the silkworm, diluting the solution with water to obtain a 1% silk solution, and removing the solvent from the solution using tangential flow filtration (TFF). In one embodiment, a 10 kDa membrane is used to purify the silk solution to achieve the final desired silk-to-water ratio. TFF can then be used to further concentrate the pure silk solution to a concentration of 2% silk in water.
[0183] Each process step, from raw cocoons to dialysis, can be scaled up to increase production efficiency. Whole cocoons are currently purchased as raw material, but pre-cleaned or non-heat-treated cocoons are also used (silkworm removal leaves behind trace amounts of debris). While cocoon cutting and cleaning is a manual process, scalability could make the process less labor-intensive, for example, by using automated machinery in combination with compressed air to remove the silkworms and any particulates, or by using a cutting mill to cut the cocoons into smaller pieces. The extraction step, currently performed in small batches, could be performed in a larger vessel, such as an industrial washing machine, in which a temperature of 60°C to 100°C is maintained. The rinsing step could also be performed in an industrial washing machine, eliminating the manual rinsing cycle. Dissolving silk in LiBr solution could be performed in a vessel other than a convection oven, such as a stirred-tank reactor. Dialyzing silk through a series of water changes is a manual and time-intensive process. This can be accelerated by modifying certain parameters, for example, by diluting the silk solution before dialysis. The dialysis process can be scaled up for manufacturing by using semi-automated equipment, for example, a tangential flow filtration system.
[0184] Varying the extraction (i.e., time and temperature), LiBr (i.e., temperature of the LiBr solution added to the silk fibroin extract or vice versa), and dissolution (i.e., time and temperature) parameters results in solvent and silk solutions with different viscosities, uniformities, and colors. Increasing the temperature for extraction, extending the extraction time, using higher temperatures of LiBr solution, both initially and over time, when dissolving the silk, and increasing the time at temperature (e.g., in an oven as shown here or with an alternative heat source) all result in solvent and silk solutions with lower viscosities and more uniformity. While nearly all parameters result in viable silk solutions, methods that achieve complete dissolution in less than 4-6 hours are preferred for process scalability.
[0185] The molecular weight of the silk protein fragments can be controlled based on specific parameters used during the extraction step, including extraction time and temperature; specific parameters used during the dissolution step, including the LiBr temperature at the time of immersion of the silk in lithium bromide and the time the solution is maintained at a specific temperature; and specific parameters used during the filtration step. By controlling process parameters using the disclosed method, SPF mixture solutions with polydispersities of 2.5 or less can be produced at a variety of different molecular weights, ranging from 1 kDa to 250 kDa, 5 kDa to 200 kDa, 5 kDa to 150 kDa, 10 kDa to 150 kDa, or 10 kDa to 80 kDa. By varying process parameters to achieve silk solutions with different molecular weights, a range of fragment mixture final products with desired polydispersities of 2.5 or less can be targeted based on desired performance requirements. For example, low-molecular-weight silk films containing drugs may have a faster release rate compared to high-molecular-weight SPF formulations. Furthermore, SPF mixture solutions with polydispersities greater than 2.5 can be achieved. Furthermore, two solutions with different average molecular weights and polydispersities can be mixed to create a combination solution. Alternatively, liquid silk glands (100% sericin-free silk protein) extracted directly from silkworms can be used in combination with any of the SPF mixture solutions disclosed herein. The molecular weights of pure silk fibroin-based protein fragment compositions were determined using high-pressure liquid chromatography (HPLC) equipped with a refractive index detector (RID). Polydispersity was calculated using Cirrus GPC Online GPC / SEC software version 3.3 (Agilent).
[0186] Parameters were varied during the processing of raw silk cocoons into silk solution. Varying these parameters affected the MW of the resulting silk solution. The parameters manipulated included: (i) extraction time and temperature, (ii) LiBr temperature, (iii) dissolution oven temperature, and (iv) dissolution time. The molecular weight was determined by mass spectrometry (spec), as shown in Figures 9-25.
[0187] Experiments were conducted to determine the effect of varying the extraction time. Figures 9-15 are graphs showing these results, and Tables 2-8 summarize the results, which are summarized below: - 30 min sericin extraction time resulted in a larger MW than 60 min sericin extraction time - MW decreases with time in the oven - 140°C LiBr and oven resulted in a low end of the confidence interval below MW 9500 Da. - 30 min extraction at 1 hour and 4 hours left the silk undigested - The 30 min extraction at the 1 hour time point resulted in a significantly higher molecular weight with the low end of the confidence interval at 35,000 Da. - The MW range that reached the high end of the confidence interval was 18,000–216,000 Da (which is important for providing solutions with specific upper limits). [Table 2] [Table 3] [Table 4] [Table 5] [Table 6] [Table 7] [Table 8]
[0188] Experiments were conducted to determine the effect of varying the extraction temperature. Figure 16 is a graph showing these results, and Table 9 summarizes the results, which are summarized as follows: -Sericin extraction at 90°C resulted in a higher MW than sericin extraction at 100°C - Both 90°C and 100°C show a decrease in MW over time in the oven. [Table 9]
[0189] Experiments were conducted to determine the effect of varying the temperature of lithium bromide (LiBr) when added to silk. Figures 17-18 are graphs showing these results, and Tables 10-11 summarize the results, which are summarized below: - No effect on MW or confidence intervals (all, CI ~ 10500 ~ 6500 Da) - Tests have shown that once LiBr is added and begins to dissolve, the temperature of the LiBr-silk solution drops sharply below the original LiBr temperature because at room temperature most of the mass is silk. [Table 10] [Table 11]
[0190] Experiments were conducted to determine the effect of varying oven / melt temperatures. Figures 19-23 are graphs showing these results, and Tables 12-16 summarize the results, as follows: - Oven temperature has a lesser effect on the 60 min extracted silk than the 30 min extracted silk. Without being bound by theory, it is believed that the 30 min silk decomposes less during extraction and therefore oven temperature has a greater effect on the larger MW silk, which decomposes less of the silk. - For 60°C vs. 140°C ovens, the 30-min extracted silk showed a very significant effect of the higher oven temperature and lower MW, while the 60-min extracted silk had an effect but it was much smaller. - The 140°C oven yielded the low end of the confidence interval at ~6000 Da. [Table 12] [Table 13] [Table 14] [Table 15] [Table 16]
[0191] In embodiments, the methods disclosed herein result in solutions with manufacturing-controllable characteristics, including, but not limited to, MW (which can be varied by varying extraction and / or dissolution time and temperature (e.g., LiBr temperature), pressure, and filtration (e.g., size exclusion chromatography)); structure (removal or cleavage of heavy or light chains of fibroin protein polymers); purity (hot water rinse temperature for improved sericin removal, or filter capacity for improved particulate removal that adversely affects the storage stability of the silk fragment protein mixture solution); color (solution color can be controlled, for example, by LiBr temperature and time); viscosity; clarity; and solution stability. The pH of the resulting solution is generally about 7 and can be altered using acid or base depending on storage conditions.
[0192] The SPF mixed solution can be used to make the SPF-containing tissue fillers described herein.
[0193] A method for preparing an aqueous solution of pure silk fibroin-based protein fragments having an average weight-average molecular weight in the range of about 1 kDa to about 250 kDa includes the steps of degumming the silk source by adding the silk source to a boiling (100°C) aqueous solution of sodium carbonate for a treatment time of about 30 minutes to about 60 minutes, removing sericin from the solution to produce a silk fibroin extract containing undetectable levels of sericin, draining the solution from the silk fibroin extract, and subjecting the silk fibroin extract to lithium bromide treatment in the range of about 60°C to about 140°C. The method includes dissolving the silk fibroin extract in a lithium bromide solution having a starting temperature equal to that of the silk fibroin extract in the lithium bromide solution; maintaining the silk fibroin-lithium bromide solution in an oven having a temperature of about 140°C for at least one hour; removing the lithium bromide from the silk fibroin extract; and producing an aqueous solution of silk protein fragments, the aqueous solution comprising fragments having an average weight-average molecular weight ranging from about 1 kDa to about 250 kDa. The aqueous solution of pure silk fibroin-based protein fragments comprises a polydispersity ranging from about 1.5 to about 3.0. The method may further comprise drying the silk fibroin extract prior to the dissolving step. The aqueous solution of pure silk fibroin-based protein fragments may contain less than 300 ppm of lithium bromide residue as measured using a high-performance liquid chromatography lithium bromide assay. The aqueous solution of pure silk fibroin-based protein fragments may contain less than 100 ppm of sodium carbonate residue as measured using a high-performance liquid chromatography sodium carbonate assay. The method may further comprise the step of adding a therapeutic agent to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further comprise the step of adding a molecule selected from one of an antioxidant or an enzyme to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further comprise the step of adding a vitamin to the aqueous solution of the pure silk fibroin-based protein fragments. The vitamin may be vitamin C or a derivative thereof. The aqueous solution of the pure silk fibroin-based protein fragments may be lyophilized. The method may further comprise the step of adding an alpha hydroxy acid to the aqueous solution of the pure silk fibroin-based protein fragments.The alpha hydroxy acid may be selected from the group consisting of glycolic acid, lactic acid, tartaric acid, and citric acid. This method may further comprise adding hyaluronic acid or a salt form thereof at a concentration of about 0.5% to about 10.0% to the aqueous solution of pure silk fibroin-based protein fragments. This method may further comprise adding at least one of zinc oxide and titanium dioxide. A film may be prepared from the aqueous solution of pure silk fibroin-based protein fragments produced by this method. The film may contain about 1.0% to about 50.0% by weight of vitamin C or a derivative thereof. The film may have a water content of about 2.0% to about 20.0% by weight. The film may contain about 30.0% to about 99.5% by weight. A gel may be prepared from the aqueous solution of pure silk fibroin-based protein fragments produced by this method. The gel may contain about 0.5% to about 20.0% by weight of vitamin C or a derivative thereof. The gel may have a silk content of at least 2% and a vitamin content of at least 20%.
[0194] A method for preparing an aqueous solution of pure silk fibroin-based protein fragments having an average weight-average molecular weight in the range of about 5 kDa to about 150 kDa includes the steps of degumming the silk source by adding the silk source to a boiling (100°C) aqueous solution of sodium carbonate for a treatment time of about 30 minutes to about 60 minutes, removing sericin from the solution to produce a silk fibroin extract containing undetectable levels of sericin, draining the solution from the silk fibroin extract, and subjecting the silk fibroin extract to a lithium bromide treatment in the range of about 60°C to about 140°C. The method includes the steps of dissolving the silk fibroin extract in a lithium bromide solution having a starting temperature equal to that of the silk fibroin extract in the lithium bromide solution; maintaining the silk fibroin-lithium bromide solution in an oven having a temperature of about 140°C for at least one hour; removing the lithium bromide from the silk fibroin extract; and producing an aqueous solution of silk protein fragments, the aqueous solution comprising fragments having an average weight-average molecular weight ranging from about 5 kDa to about 150 kDa, and the aqueous solution of pure silk fibroin-based protein fragments comprising a polydispersity ranging from about 1.5 to about 3.0. The method may further comprise the step of drying the silk fibroin extract prior to the dissolving step. The aqueous solution of pure silk fibroin-based protein fragments may contain less than 300 ppm of lithium bromide residue as measured using a high-performance liquid chromatography lithium bromide assay. The aqueous solution of pure silk fibroin-based protein fragments may contain less than 100 ppm of sodium carbonate residue as measured using a high-performance liquid chromatography sodium carbonate assay. The method may further comprise the step of adding a therapeutic agent to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further comprise the step of adding a molecule selected from one of an antioxidant or an enzyme to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further comprise the step of adding a vitamin to the aqueous solution of the pure silk fibroin-based protein fragments. The vitamin may be vitamin C or a derivative thereof. The aqueous solution of the pure silk fibroin-based protein fragments may be lyophilized. The method may further comprise the step of adding an alpha hydroxy acid to the aqueous solution of the pure silk fibroin-based protein fragments.The alpha hydroxy acid may be selected from the group consisting of glycolic acid, lactic acid, tartaric acid, and citric acid. This method may further comprise adding hyaluronic acid or a salt form thereof at a concentration of about 0.5% to about 10.0% to the aqueous solution of pure silk fibroin-based protein fragments. This method may further comprise adding at least one of zinc oxide and titanium dioxide. A film may be prepared from the aqueous solution of pure silk fibroin-based protein fragments produced by this method. The film may contain about 1.0% to about 50.0% by weight of vitamin C or a derivative thereof. The film may have a water content of about 2.0% to about 20.0% by weight. The film may contain about 30.0% to about 99.5% by weight. A gel may be prepared from the aqueous solution of pure silk fibroin-based protein fragments produced by this method. The gel may contain about 0.5% to about 20.0% by weight of vitamin C or a derivative thereof. The gel may have a silk content of at least 2% and a vitamin content of at least 20%.
[0195] A method for preparing an aqueous solution of pure silk fibroin-based protein fragments having an average weight-average molecular weight in the range of about 6 kDa to about 17 kDa includes the steps of degumming the silk source by adding the silk source to a boiling (100°C) aqueous solution of sodium carbonate for a treatment time of about 30 minutes to about 60 minutes, removing sericin from the solution to produce a silk fibroin extract containing undetectable levels of sericin, draining the solution from the silk fibroin extract, and subjecting the silk fibroin extract to a lithium bromide bath in the range of about 60°C to about 140°C. The method includes dissolving the silk fibroin extract in a lithium bromide solution having a starting temperature equal to that of the silk fibroin extract in the lithium bromide solution; maintaining the silk fibroin-lithium bromide solution in an oven having a temperature of about 140°C for at least one hour; removing the lithium bromide from the silk fibroin extract; and producing an aqueous solution of silk protein fragments, the aqueous solution comprising fragments having an average weight-average molecular weight in the range of about 6 kDa to about 17 kDa, and the aqueous solution of pure silk fibroin-based protein fragments having a polydispersity in the range of about 1.5 to about 3.0. The method may further comprise drying the silk fibroin extract prior to the dissolving step. The aqueous solution of pure silk fibroin-based protein fragments may contain less than 300 ppm of lithium bromide residue as measured using a high-performance liquid chromatography lithium bromide assay. The aqueous solution of pure silk fibroin-based protein fragments may contain less than 100 ppm of sodium carbonate residue as measured using a high-performance liquid chromatography sodium carbonate assay. The method may further comprise the step of adding a therapeutic agent to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further comprise the step of adding a molecule selected from one of an antioxidant or an enzyme to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further comprise the step of adding a vitamin to the aqueous solution of the pure silk fibroin-based protein fragments. The vitamin may be vitamin C or a derivative thereof. The aqueous solution of the pure silk fibroin-based protein fragments may be lyophilized. The method may further comprise the step of adding an alpha hydroxy acid to the aqueous solution of the pure silk fibroin-based protein fragments.The alpha hydroxy acid may be selected from the group consisting of glycolic acid, lactic acid, tartaric acid, and citric acid. This method may further comprise adding hyaluronic acid or a salt form thereof at a concentration of about 0.5% to about 10.0% to the aqueous solution of pure silk fibroin-based protein fragments. This method may further comprise adding at least one of zinc oxide and titanium dioxide. A film may be prepared from the aqueous solution of pure silk fibroin-based protein fragments produced by this method. The film may contain about 1.0% to about 50.0% by weight of vitamin C or a derivative thereof. The film may have a water content of about 2.0% to about 20.0% by weight. The film may contain about 30.0% to about 99.5% by weight. A gel may be prepared from the aqueous solution of pure silk fibroin-based protein fragments produced by this method. The gel may contain about 0.5% to about 20.0% by weight of vitamin C or a derivative thereof. The gel may have a silk content of at least 2% and a vitamin content of at least 20%.
[0196] A method for preparing an aqueous solution of pure silk fibroin-based protein fragments having an average weight-average molecular weight in the range of about 17 kDa to about 39 kDa includes the steps of adding a silk source to a boiling (100°C) aqueous solution of sodium carbonate for a treatment time of about 30 minutes to about 60 minutes to degumm the silk source, removing sericin from the solution to produce a silk fibroin extract containing undetectable levels of sericin, draining the solution from the silk fibroin extract, dissolving the silk fibroin extract in a lithium bromide solution having a starting temperature in the range of about 80°C to about 140°C, and then heating the silk fibroin-lithium bromide solution to about 60°C. The method may further comprise the steps of: maintaining the silk fibroin extract in a drying oven having a temperature of about 100°C to about 100°C for at least one hour; removing lithium bromide from the silk fibroin extract; and producing an aqueous solution of pure silk fibroin-based protein fragments, wherein the aqueous solution of pure silk fibroin-based protein fragments contains about 10 ppm to about 300 ppm of lithium bromide residue; the aqueous solution of pure silk fibroin-based protein fragments contains about 10 ppm to about 100 ppm of sodium carbonate residue; the aqueous solution of pure silk fibroin-based protein fragments contains fragments having an average weight-average molecular weight in the range of about 17 kDa to about 39 kDa; and the aqueous solution of pure silk fibroin-based protein fragments contains a polydispersity in the range of about 1.5 to about 3.0. The method may further comprise the step of drying the silk fibroin extract prior to the dissolving step. The aqueous solution of pure silk fibroin-based protein fragments may contain less than 300 ppm of lithium bromide residue as measured using a high-performance liquid chromatography lithium bromide assay. The aqueous solution of the pure silk fibroin-based protein fragments may contain less than 100 ppm of residual sodium carbonate as measured using a high-performance liquid chromatography sodium carbonate assay. The method may further include adding a therapeutic agent to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further include adding a molecule selected from one of an antioxidant or an enzyme to the aqueous solution of the pure silk fibroin-based protein fragments.The method may further include adding a vitamin to the aqueous solution of the pure silk fibroin-based protein fragments. The vitamin may be vitamin C or a derivative thereof. The aqueous solution of the pure silk fibroin-based protein fragments may be lyophilized. The method may further include adding an alpha hydroxy acid to the aqueous solution of the pure silk fibroin-based protein fragments. The alpha hydroxy acid may be selected from the group consisting of glycolic acid, lactic acid, tartaric acid, and citric acid. The method may further include adding hyaluronic acid or a salt form thereof at a concentration of about 0.5% to about 10.0% to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further include adding at least one of zinc oxide and titanium dioxide.
[0197] A gel can be made from an aqueous solution of the pure silk fibroin-based protein fragments produced by this method. The gel may contain about 0.5% to about 20.0% by weight of vitamin C or a derivative thereof. The gel may have a silk content of at least 2% and a vitamin content of at least 20%.
[0198] According to an embodiment described herein, a method for preparing an aqueous solution of pure silk fibroin-based protein fragments having an average weight-average molecular weight in the range of about 39 kDa to about 80 kDa is disclosed, the method comprising the steps of adding a silk source to a boiling (100°C) aqueous solution of sodium carbonate for a treatment time of about 30 minutes to degumm the silk source, removing sericin from the solution to produce a silk fibroin extract containing undetectable levels of sericin, draining the solution from the silk fibroin extract, and placing the silk fibroin extract in a lithium bromide solution having a starting temperature in the range of about 80°C to about 140°C. The method includes dissolving the silk fibroin-lithium bromide extract in a solution of sodium bromide; maintaining the silk fibroin-lithium bromide solution in a drying oven having a temperature of about 60°C to about 100°C for at least one hour; removing the lithium bromide from the silk fibroin extract; and producing an aqueous solution of pure silk fibroin-based protein fragments, wherein the aqueous solution of pure silk fibroin-based protein fragments contains about 10 ppm to about 300 ppm of lithium bromide residue, about 10 ppm to about 100 ppm of sodium carbonate residue, fragments having an average weight-average molecular weight in the range of about 40 kDa to about 65 kDa, and a polydispersity in the range of about 1.5 to about 3.0. The method may further include drying the silk fibroin extract prior to the dissolving step. The aqueous solution of pure silk fibroin-based protein fragments may contain less than 300 ppm of lithium bromide residue as measured using a high-performance liquid chromatography lithium bromide assay. The aqueous solution of the pure silk fibroin-based protein fragments may contain less than 100 ppm of residual sodium carbonate as measured using a high-performance liquid chromatography sodium carbonate assay. The method may further include adding a therapeutic agent to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further include adding a molecule selected from one of an antioxidant or an enzyme to the aqueous solution of the pure silk fibroin-based protein fragments. The method may further include adding a vitamin to the aqueous solution of the pure silk fibroin-based protein fragments.The vitamin may be vitamin C or a derivative thereof. The aqueous solution of pure silk fibroin-based protein fragments may be freeze-dried. The method may further comprise the step of adding an alpha hydroxy acid to the aqueous solution of pure silk fibroin-based protein fragments. The alpha hydroxy acid may be selected from the group consisting of glycolic acid, lactic acid, tartaric acid, and citric acid. The method may further comprise adding hyaluronic acid or a salt form thereof at a concentration of about 0.5% to about 10.0% to the aqueous solution of pure silk fibroin-based protein fragments. The method may further comprise adding at least one of zinc oxide and titanium dioxide.
[0199] A gel can be made from an aqueous solution of the pure silk fibroin-based protein fragments produced by this method. The gel may contain about 0.5% to about 20.0% by weight of vitamin C or a derivative thereof. The gel may have a silk content of at least 2% and a vitamin content of at least 20%.
[0200] Hyaluronic acid and hyaluronic acid gel The biodegradable polymer component of the present invention is hyaluronate, also known as hyaluronic acid (HA). HA is composed of alternating residues of D-glucuronic acid and N-acetyl-D-glucosamine. This water-soluble polymer is naturally present in almost all tissues, particularly in the extracellular matrix, the eye, and synovial fluid of joints. HA is commercially available in pure form. Gel small particle HA fillers can be used to stimulate natural collagen production, which is presumably induced by mechanical stretching of the dermis and activation of dermal fibroblasts.
[0201] The concentration of HA in the resulting dermal fillers of the present invention contributes to the stiffness and longevity of the dermal filler, and in some embodiments, higher concentrations of HA in the resulting dermal fillers described herein may increase the stiffness and / or longevity of the resulting dermal filler compared to dermal fillers with relatively lower concentrations of HA.
[0202] In some embodiments, the HA contained in the tissue fillers described herein has a molecular weight of 100,000 daltons or more, 150,000 daltons or more, 1 million daltons or more, or 2 million daltons or more. In some embodiments, the HA contained in the tissue fillers described herein has a molecular weight of 100,000 daltons or less, 150,000 daltons or less, 1 million daltons or less, or 2 million daltons or less. In some embodiments, the HA contained in the tissue fillers described herein has a high molecular weight (e.g., an HA molecular weight of about 1 MDa to about 4 MDa). In some embodiments, the HA contained in the tissue fillers described herein has a low molecular weight (e.g., an HA molecular weight of less than about 1 MDa).
[0203] In some embodiments, the HA source may be a hyaluronate, such as sodium hyaluronate. In some embodiments, the HA is crosslinked. The crosslinked HA can be formed into various shapes, such as a membrane, gel, semi-gel, sponge, or microsphere. In some embodiments, the crosslinked HA is in a fluid gel form, i.e., it assumes the shape of its container. The viscosity of the HA gel or semi-gel can be altered by adding unconjugated HA and / or hyaluronate. Viscosity can also be adjusted by varying the degree of SPF-SPF, SPF-HA, and / or HA-HA crosslinking, as described herein. In some embodiments, about 4% to about 12% of the HA can be crosslinked in the HA-HA or HA-SPF formulation.
[0204] In embodiments, the SPF compositions described herein can be combined with HA to form tissue filler compositions. In embodiments, the HA (wt%) in the tissue filler composition is less than 99%. In embodiments, the HA (wt%) in the tissue filler composition is less than 98%. In embodiments, the HA (wt%) in the tissue filler composition is less than 97%. In embodiments, the HA (wt%) in the tissue filler composition is less than 96%. In embodiments, the HA (wt%) in the tissue filler composition is less than 95%. In embodiments, the HA (wt%) in the tissue filler composition is less than 94%. In embodiments, the HA (wt%) in the tissue filler composition is less than 93%. In embodiments, the HA (wt%) in the tissue filler composition is less than 92%. In embodiments, the HA (wt%) in the tissue filler composition is less than 91%. In embodiments, the HA (wt%) in the tissue filler composition is less than 90%. In embodiments, the HA (wt%) in the tissue filler composition is less than 85%. In embodiments, the HA (wt%) in the tissue filler co...
Claims
1. A biocompatible tissue filler for use in treating a soft tissue condition, comprising: hyaluronic acid (HA), anesthetics, and A silk protein fragment (SPF) containing fibroin, the SPF having a weight average molecular weight selected from about 1 kDa to about 250 kDa. Including, the HA portion, the SPF portion, or both are modified or crosslinked with one or more linker moieties comprising one or more of an alkane or alkyl chain, and / or an ether group; the modified or cross-linked HA and / or SPF comprises a linker or cross-linking moiety comprising a polyethylene glycol (PEG) chain; the modification or crosslinking is achieved using a crosslinking agent that is a polyethylene glycol diglycidyl ether containing from about 2 to about 25 ethylene glycol groups; the tissue filler has a storage modulus (G') of 25 Pa to 1500 Pa; and The tissue filler has a degree of modification (MoD) of 1% to 25%; and The soft tissue is selected from the group consisting of dermal tissue, subdermal tissue, skin tissue, subcutaneous tissue, intradural tissue, muscle, tendon, ligament, fibrous tissue, adipose tissue, blood vessel, nerve, and synovial tissue. Tissue filler.
2. A tissue filler as described in claim 1, which is deliverable to voids within or around soft tissue.
3. A tissue filler as described in claim 1, which is biodegradable.
4. A tissue filler as described in claim 1, which is injectable.
5. The tissue filler described in claim 1, wherein the soft tissue condition is a skin condition.
6. The tissue filler of claim 1, wherein the skin condition is selected from the group consisting of skin dehydration, lack of skin elasticity, rough skin, lack of skin firmness, skin stretch lines, skin stretch marks, skin pallor, skin divots, sunken cheeks, thin lips, retro-orbital defects, facial creases, and wrinkles.
7. The tissue filler described in claim 1, administered to the dermal region of a subject.
8. The tissue filler of claim 1, for administration by injection into the epidermal-dermal junction region, the papillary region, the reticular region, or any combination thereof.
9. A tissue filler as described in claim 1 for use in soft tissue augmentation, soft tissue reconstruction, treatment of soft tissue disease, treatment of soft tissue disorders, treatment of soft tissue defects or imperfections in a part, portion or area of the body.
10. A tissue filler as described in claim 1 for use in facial augmentation, facial reconstruction, treatment of facial disease, treatment of facial disorders, treatment of facial defects, or treatment of facial imperfections.
11. A tissue filler described in any one of claims 1 to 10, which is resistant to biodegradation, bioerosion, bioabsorption, and / or bioresorption for at least about 3 days, about 7 days, about 14 days, about 21 days, about 28 days, about 1 month, about 2 months, about 3 months, about 4 months, about 5 months, or about 6 months.
12. A tissue filler described in any one of claims 1 to 10, which shows that administration of the tissue filler to the subject reduces the inflammatory response compared to the inflammatory response induced by a control tissue filler comprising HA and lidocaine but not SPF.
13. A tissue filler described in any one of claims 1 to 10, wherein administration of the tissue filler to the subject shows increased new collagen production compared to the same or similar tissue filler containing HA but not SPF.
14. A biocompatible injectable tissue filler comprising silk protein fragments (SPF), hyaluronic acid (HA), and an anesthetic, comprising: the HA portion, the SPF portion, or both are modified or crosslinked with one or more linker moieties comprising one or more of an alkane or alkyl chain, and / or an ether group; The degree of modification (MoD) is about 1.0% to about 25.0%; The modification or crosslinking is achieved using a polyethylene glycol diglycidyl ether containing from about 2 to about 25 ethylene glycol groups; and The total concentration of SPF in the tissue filler is about 0.1 mg / mL to about 15 mg / mL; Tissue filler.
15. The tissue filler described in claim 14, wherein the total concentration of HA in the tissue filler is from about 10 mg / mL to about 50 mg / mL.
16. The tissue filler described in claim 14, wherein the SPF has an average weight average molecular weight selected from about 1 kDa to about 250 kDa.
17. The tissue filler described in claim 14, wherein the SPF has an average weight average molecular weight selected from about 5 kDa to about 150 kDa.
18. The tissue filler described in claim 14, wherein the SPF has an average weight average molecular weight selected from about 6 kDa to about 17 kDa.
19. The tissue filler described in claim 14, wherein the SPF has an average weight average molecular weight selected from about 17 kDa to about 39 kDa.
20. The tissue filler described in claim 14, wherein the SPF has an average weight average molecular weight selected from about 39 kDa to about 80 kDa.
21. A tissue filler described in any one of claims 14 to 20 for use as a pharmaceutical.
22. The tissue filler of claim 21 for use in treating a soft tissue condition.
23. A tissue filler described in any one of claims 14 to 20 for use in improving, strengthening, and / or altering soft tissue in a subject.
24. The improvement, enhancement, and / or change is: Increased soft tissue size; Improved soft tissue shape and contouring of facial features; Increased size, shape and / or contour of the lips, increased size, shape and / or contour of the cheeks, increased size, shape and / or contour of the temples, increased size, shape and / or contour of the eye area; changes in size, shape, and / or contour of facial features, lips, cheeks, temples, and / or eye area; Reduction or elimination of wrinkles, folds, and / or lines on the skin; Resistance to wrinkles, creases, and / or lines on the skin; Skin hydration; Increased skin elasticity; Reduction or elimination of rough skin; Increased and / or improved skin firmness; Reduce or eliminate stretch lines or stretch marks; Increased and / or improved skin tone, radiance, brightness, and / or radiance; Enhancement and / or improvement of skin color; and / or Reduction or elimination of skin paleness; Including, 24. The tissue filler of claim 23, wherein administration of the tissue filler exhibits sustained engraftment of the composition, reduced side effects, and improved subject satisfaction and / or quality of life compared to a comparable tissue filler that does not contain SPF.